Supplementation of IVM media with equine follicular fluid of large follicles increases blastocyst yield in equine ICSI programs - Luciana Ribeiro Peixoto; Marcos Antônio Gonçalves; José Henrique Fortes Pontes; Perla Dagher Cassoli Fleury; Gustavo Pulzatto Merlini; Thiago Alexandre Robilotta de Oliveira; Victoria Martins Braghetto Barillari; Cláudia Barbosa Fernandes; José Buratini; Vilceu Bordignon; Felipe Perecin (Theriogenology, 2026)

FORMSpoT: Revealing fine-scale forest disturbances from nation-wide 1.5 m forest canopy height time series - Martin Schwartz; Fajwel Fogel; Nikola Besic; Damien Robert; Louis Geist; Jean-Pierre Renaud; Jean-Matthieu Monnet; Clemens Mosig; Cédric Vega; Alexandre d’Aspremont; Loic Landrieu; Philippe Ciais (Remote Sensing of Environment, 2026)

Salience Network Dynamics Across Spontaneous Attacks, Interictal Rest and Interictal Pain Imagery in Menstrually Related Migraine - Inês Esteves; Alexandre Perdigão; Ana R. Fouto; Amparo Ruiz-Tagle; Gina Caetano; Joana Cabral; Isabel Pavão Martins; Raquel Gil-Gouveia; César Caballero-Gaudes; Patrícia Figueiredo (Brain Topography, 2026)

Formation and geological significance of carbonate firmgrounds and hardgrounds on the Rio Grande Rise (South Atlantic) - Alexandre Henrique Ferraz; Rafael Oliveira Silva; Pedro Walfir Martins e Souza Neto; Carina Ulsen; Lucy Gomes Sant'Anna; Paulo César Fonseca Giannini; Eugenio Pires Frazão; Victor Hugo Rocha Lopes; Luigi Jovane; Bramley J. Murton; Christian Millo (Sedimentary Geology, 2026)

Flexural behavior and stability of continuous composite beams using NSS and HSS castellated I-sections and slabs of NSC and UHPC - Vinicius Moura de Oliveira; Vinicius Brother dos Santos; Alexandre Rossi; Luciano Rodrigues Ornelas de Lima; Carlos Humberto Martins (Engineering Structures, 2026)

Dynamics of forest restoration in riparian ecosystems following tin mining in the Central Amazon - Marcele Farias Pereira; Marciel José Ferreira; Rodrigo de Souza Barbosa; Carlos Alexandre Costa Coelho; Wyler Frank Siqueira do Carmo; Gabriel dos Santos Cardoso; Julia Isabella de Matos Rodrigues; Walmer Bruno Rocha Martins (Ecological Engineering, 2026)

When Herbicides Interact: Synergistic, Additive, and Antagonistic Effects of 2,4-D- and Glyphosate-Based Herbicides in Physalaemus cuvieri Tadpoles - Vrandrieli Jucieli Skovronski; Aline Pompermaier; Camila Fátima Rutkoski; Natani Macagnan; Alexandre Folador; Gilcinéia dos Santos; Márcio Borges-Martins; Paulo Afonso Hartmann; Marilia Hartmann (Water, Air, & Soil Pollution, 2026)
Considering the ecological relevance of amphibians and the widespread agricultural use of herbicide mixtures, investigations addressing their joint toxicological effects are increasingly necessary. Here, we investigated the effects of a mixture of two commercially formulated herbicides widely used in combination in agriculture—2,4-D-based herbicide (DBH) and a glyphosate-based herbicide (GBH)—on tadpoles of Physalaemus cuvieri , a bioindicator amphibian species. Chronic tests were performed using environmentally relevant concentrations and the maximum concentrations permitted in water bodies by current legislation. The mixture of these two pesticides impaired tadpole survival and induced abnormal behavior, characterized by distinct responses patterns. Nearly half of the analyzed tadpoles exhibited malformation by the end of assay. The integrated analysis of survival, behavior, and malformation data revealed antagonistic, additive and synergistic interactions between DBH and GBH in Physalaemus cuvieri tadpoles. These findings demonstrate that the herbicide mixture is nonetheless lethal to the tested species, inducing changes that can compromise its survival and overall living conditions, which may lead to significant biological impacts.

Cover crops shape soil microbiome and ecological interactions in the soybean rhizosphere under long-term no-till - Caio César Gomes Freitas; Carolinne Rosa de Carvalho; Nariane de Andrade; Rafael Lima Oliveira; Victor Lucas Vieira Prudêncio Araújo; Felipe Martins do Rêgo Barros; João Henrique dos Santos Ferreira; José Roberto Portugal; Carlos Alexandre Costa Crusciol; Fernando Dini Andreote (Soil and Tillage Research, 2026)

Permanent land use and microbial contributions shape soil organic carbon stabilization in lake floodplains - Toky Jeriniaina Rabearison; Jim Félix-Faure; François Guillemette; Michelle Garneau; Christine Martineau; Louis Astorg; Martin Chantigny; Virginie Favreau; Jessika Malko; Alexandre Roy; Vincent Maire (Soil Biology and Biochemistry, 2026)

The alginate-carrageenan blend exhibits good printability and supports adhesion of ovarian stromal cells in bioprinted scaffolds - Solano Dantas Martins; Iana Lira Nogueira; Maria Alice Felipe Oliveira; Pedro Everson Alexandre De Aquino; Marjory Lima Holanda Araújo; Vânia Marilande Ceccatto; Valdevane Rocha Araújo (Reproductive Biology, 2026)

Productive, physiological, and biochemical responses of elephant grass ‘BRS Capiaçu’ (Pennisetum purpureum Schumach.) under different water regimes with brackish water in a semi-arid environment - Lara Rosa de Lima-Silva; Lady Daiane Costa de Sousa Martins; Alexandre Maniçoba da Rosa Ferraz Jardim; Wagner Martins dos Santos; Pedro Paulo Santos de Souza; Luciana Sandra Bastos de Souza; Cleber Pereira Alves; Agda Raiany Mota dos Santos; Ênio Farias de França e Silva; Hugo Rafael Bentzen Santos; Wilma Roberta dos Santos; Carlos André Alves de Souza; et al. (Physiology and Molecular Biology of Plants, 2026)
The seasonality of forage production is one of the main challenges in semi-arid regions, where environmental conditions limit agricultural productivity. One promising option is the use of elephant grass ‘BRS Capiaçu’, together with deficit irrigation. This study evaluated the impact of different irrigation depths with brackish water (50%, 75%, 100% and 125% of the reference evapotranspiration – ET 0 ) on the productive, physiological, photochemical and biochemical aspects of ‘BRS Capiaçu’ over two cycles. Irrigation with 50% of the ET 0 resulted in lower rates of net photosynthesis (P n ), with a reduction in photosystem II quantum yield (ΔF/Fm’), qP, NPQ and the electron transport rate (ETR), in addition to greater activity of the antioxidant enzymes superoxide dismutase (SOD), catalase (CAT) and ascorbate peroxidase (APX), indicating oxidative stress. The depths of 50% and 100% of the ET 0 resulted in greater dry matter production, for Cycles 1 and 2, respectively, demonstrating the resilience of the crop to water stress, attributed to such mechanisms of acclimatisation as a reduction in transpiration (T r ) and an increase in water use efficiency. These physiological changes were more obvious during Cycle 2, in which the crop was subjected to lower rainfall (47.8 mm), while salt stress was also more pronounced during this period, in response, the plants showed less water loss through transpiration and larger WUE inst . It was concluded that ‘BRS Capiaçu’ has a high capacity for acclimatisation to semi-arid conditions, and stands out as a viable alternative for mitigating the seasonality of forage production and promoting sustainable livestock farming in the region.

A combination of resilient practices maximizes productivity and water, carbon, and nutrient stocks in forage species systems in the Brazilian semi-arid region - Marcelo José da Silva; Wilma Roberta dos Santos; Cleber Pereira Alves; Alexandre Maniçoba da Rosa Ferraz Jardim; Agda Raiany Mota dos Santos; Álefe Chagas de Lima Costa; Carlos André Alves de Souza; José Edson Florentino de Morais; Luciana Sandra Bastos de Souza; João Pedro Alves de Souza Santos; Ênio Farias de França e Silva; Fleming Sena Campos; et al. (International Journal of Plant Production, 2026)
Adopting resilient practices is crucial to balancing food production and crop sustainability in semiarid regions. Therefore, adopting systems that provide greater stocks of water, carbon, and nutrients at the soil-plant interface is crucial. The objective of this study was to assess water, carbon, and nutrient stocks in the soil-plant systems of irrigated forage crops in the semiarid region of Brazil. The study was conducted in Serra Talhada, Pernambuco, Brazil. Four production cycles were evaluated between January 2017 and January 2022, comprising seven cropping systems: pigeon pea (S1), millet (S2), sorghum (S3), cactus forage (S4), cactus forage-sunflower-pigeon pea (S5), cactus forage-sorghum-millet (S6), and cactus forage-sorghum (S7). The following parameters were evaluated: fresh matter (FM) and dry matter (DM) productivity, as well as water, organic carbon (OC), and nutrient (N, P, K + , Ca 2+ , Mg 2+ , and Na + ) stocks in the plant and soil at depths of 0–20 and 20–40 cm. The intercropping systems presented the highest mean values for each of the plant variables. Among the single systems, forage cactus did not differ from the intercropped systems for FM, plant stocks of P, Ca 2+ , Mg 2+ , and water. The single sorghum presented higher values for plant DM (44.0 Mg ha −1 ) and plant OC (18.7 Mg ha −1 ). For soil variables, only the levels of P, K + , Na +, and OC showed significant differences ( p < 0.05). The single forage cactus had the highest average soil OC value (14.5 Mg ha −1 ). The cactus-sorghum intercrop system appears to offer the best balance between productivity and water, OC, and nutrient reserves. Among the isolated systems, forage cactus stores the largest amounts of OC in the soil, while sorghum stands out for accumulating carbon in the plants. Studies on the sustainability of forage species should be encouraged to improve the development of agricultural systems.

Sex-specific effects of therapeutic hypothermia on short- and long-term microglial and astrocytic reactivity after severe neonatal hypoxia–ischemia - Ricardo Ribeiro Nunes; João Vitor Miotto Tauffer; Bianca Büchele Martins; Isadora D’Ávila Tassinari; Carlos Alexandre Netto; Ana Helena Paz; Luciano Stürmer de Fraga (Metabolic Brain Disease, 2026)

Retraction notice to “Spatial and temporal distribution of urban heat islands” [Sci. Total Environ. 605–606 (2017) 946–956] - Alexandre Rosa dos Santos; Felício Santos de Oliveira; Aderbal Gomes da Silva; José Marinaldo Gleriani; Wantuelfer Gonçalves; Giselle Lemos Moreira; Felipe Gimenes Silva; Elvis Ricardo Figueira Branco; Marks Melo Moura; Rosane Gomes da Silva; Ronie Silva Juvanhol; Kaíse Barbosa de Souza; et al. (Science of The Total Environment, 2026)

Therapeutic potential of Syzygium cumini L. extract in treating anxiety in adult zebrafish (Danio rerio): Behavioral, toxicological, and molecular evidence involving the GABAergic and serotonergic pathways - Cássia Taiane Viana Moraes; Gabriel Martins de Araújo Sousa; Ariel Falanga de Oliveira; Igor de Codes Soares; Paula Ticiani Alves de Souza; Lucca Moura de Freitas; Mário Guilherme de Paula Sales; Vitória Isabele Gomes Ferreira; Paula Alexandre de Freitas; Saulo Chaves Magalhães; Katarine Ferreira da Silva; Luís Sérgio Fonteles Duarte; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Diagnosis of acetaminophen and codeine poisoning in a dog using earwax analysis by headspace gas chromatography-mass spectrometry (HS/GC-MS) - Monica Chacon de Vicente; Alexandre Có Mangoni Barros; Gabriela Scarpin de Souza; Lais di Pauli Taborda Prado; João Marcos Gonçalves Barbosa; Rayanne Henrique Santana da Silva; Leidiane de Souza Gomes; Danieli Brolo Martins; Nelson Roberto Antoniosi Filho; Ana Flávia Machado Botelho (Veterinary Research Communications, 2026)
Poisoning of companion animals resulting from exposure to analgesics intended for human use is a frequent and clinically relevant problem in veterinary practice, usually associated with administration without professional supervision. This can induce severe systemic toxicity. Diagnostic confirmation can be particularly challenging in cases presenting with nonspecific clinical signs or when conventional biological samples are unavailable. This case report describes the innovative use of earwax as a non-invasive biological matrix for toxicological confirmation in veterinary medicine. A 9-year-old male mixed-breed dog was admitted following a traumatic accident and subsequent administration by its owner of a human medication containing acetaminophen and codeine. Clinical evaluation revealed lethargy, hypersalivation, hyporexia, dehydration, and neurological abnormalities. Laboratory findings demonstrated neutrophilic leukocytosis and marked increases in hepatic enzyme activities, consistent with acute hepatocellular injury. Toxicological investigation using headspace gas chromatography–mass spectrometry detected acetaminophen-related signatures in an earwax sample, supporting suspected exposure to the drug. Intensive treatment was promptly initiated and included fluid therapy, antidotal treatment with N-acetylcysteine, opioid antagonism, analgesia, and supportive care. The patient showed progressive clinical improvement, with complete resolution of clinical signs and full recovery. This case highlights the significant risks of administering human medications to companion animals and underscores the need to improve owner awareness of self-medication practices. Furthermore, it demonstrates the diagnostic potential of earwax as a non-invasive biological matrix for toxicological confirmation, expanding the range of complementary diagnostic tools available for veterinary toxicology and supporting improved clinical decision-making in cases of suspected pharmaceutical intoxication.

Correction: Supplementing the diet of Nile tilapia (Oreochromis niloticus) with microalgae Nannochloropsis oculata and Phaeodactylum tricornutum enhanced immune function, lipid profile, and resistance to Edwardsiella tarda infection - Domickson Silva Costa; Jucimauro de Araújo Pereira Júnior; Paola Capistrano dos Santos; Maria Clara Miguel Libanori; Gracienhe Gomes dos Santos; Ana Paula de Souza; Alexandre Vaz da Silva; Cláudia Andrea Lima Cardoso; Arlene Sobrinho Ventura; Aline Brum Figueredo Ruschel; Rafael Sales; Fábio de Farias Neves; et al. (Veterinary Research Communications, 2026)

Supplementing the diet of Nile tilapia (Oreochromis niloticus) with microalgae Nannochloropsis oculata and Phaeodactylum tricornutum enhanced immune function, lipid profile, and resistance to Edwardsiella tarda infection - Domickson Silva Costa; Jucimauro de Araújo Pereira Júnior; Paola Capistrano dos Santos; Maria Clara Miguel Libanori; Gracienhe Gomes dos Santos; Ana Paula de Souza; Alexandre Vaz da Silva; Cláudia Andrea Lima Cardoso; Arlene Sobrinho Ventura; Aline Brum Figueredo Ruschel; Rafael Sales; Fábio de Farias Neves; et al. (Veterinary Research Communications, 2026)
The aim of the present study was to evaluate the effects of dietary supplementation with the microalgae Nannochloropsis oculata and Phaeodactylum tricornutum , either separately or in combination, on growth performance, lipid profile, haematoimmunological parameters, and resistance to Edwardsiella tarda infection in Nile tilapia ( Oreochromis niloticus ). A total of 960 juvenile Nile tilapia (2.87 ± 0.68 g and 5.65 ± 0.16 cm) were allocated to 24 experimental units ( n = 40) and fed six experimental diets for 60 days: DC 0% (no microalgae inclusion), DN 0.5% (0.5% N. oculata ), DN 1% (1% N. oculata ), DP 0.5% (0.5% P. tricornutum ), DP 1% (1% P. tricornutum ), and DPN 1% (0.5% N. oculata + 0.5% P. tricornutum ). After the feeding period, fish were challenged with E. tarda (2 × 10⁸ CFU mL⁻¹). Microalgal inclusion increased significantly ( p < 0.05) dietary contents of phenolic compounds, flavonoids, tannins, and antioxidant potential of diets without affecting fish growth. The DP 1% and DPN 1% diets increased significantly ( p < 0.05) eicosapentaenoic and docosahexaenoic acid levels and reduced monounsaturated fatty acids and ∑saturated fatty acids in muscle, thereby improving the lipid profile and flesh quality. Following infection, reductions in erythrocytic parameters were observed, along with increases in lymphocyte, monocyte, basophil, neutrophil, and thrombocyte counts, as well as higher ( p < 0.05) agglutination and antimicrobial titres, total plasma protein, and immunoglobulin levels in the DP 1% and DPN 1% groups. Survival was higher in the microalgae-supplemented groups, particularly in DPN 1% (91.67 ± 1.8%) compared with the control (65.0 ± 2.0%). Supplementation with DP 1% and DPN 1% improved haematoimmunological responses, lipid composition, and resistance to E. tarda in Nile tilapia.

Phenotypic variability of hydraulic residual conductance and its temperature sensitivity in Abies alba Mill - Stéphane Herbette; Andanson Stéphane; Gonzalez Alexandre; J. Blackman Chris; Cartailler Julien; Martin Ludovic; Cochard Hervé (Trees, 2026)

Ultrastructural Features of Cryptococcus neoformans Histone Deacetylases Null Mutant Strains - Daniel Oliveira da Mata; Lucas da Costa Campos; Martha Viviana Roa-Cordero; Ariane Pandolfo Silveira; Ingrid Gracielle Martins da Silva; Victor Carlos Mello; Luís Alexandre Muehlmann; Bergmann Morais Ribeiro; Sônia Nair Báo; Marcio José Poças-Fonseca (Indian Journal of Microbiology, 2026)

CO2 removal by applying the adsorption process to biochar from waste materials - Maria Angelica Martins Costa; Geisa Albini; Lucas Freitas de Oliveira; Eliza Almeida de Oliveira; Alexandre Jorge Duarte de Souza; Mariana de Oliveira Bérgamo; Letícia Vicente Moreno; Kelly Johana Dussán (Environmental Science and Pollution Research, 2026)
This study evaluated lignocellulosic residues as low-cost adsorbents for CO 2 capture in a dynamic column system, focusing on spent coffee grounds biochar (SCGB) as an alternative to commercial activated carbon. Commercial activated carbon, SCGB, magnetized SCGB, KOH-activated SCGB, peanut shell pellet charcoal, sugarcane bagasse charcoal containing kaolin, and calcined SCGB samples were tested. SCGB was produced by pyrolysis and modified by chemical activation, magnetite incorporation, or post-pyrolysis calcination. CO 2 adsorption tests were performed in a column under different air and CO₂ inlet flow rates, and CO 2 concentrations were monitored at the inlet and outlet using infrared sensors. The adsorption capacity ranged from 0.43 to 7.17 mmol CO 2 /g, depending on the adsorbent and operating conditions. The best performance was obtained for non-activated SCGB, which reached 7.17 mmol CO 2 /g under intermediate air flow conditions. Although KOH activation improved the textural properties of SCGB, it did not lead to the highest adsorption capacity in the column. These results indicate that CO 2 capture under dynamic conditions is controlled not only by BET surface area and micropore volume, but also by pore accessibility, surface chemistry, bed behavior, and gas residence time. Spent coffee grounds biochar showed competitive CO 2 adsorption performance and may be considered a promising low-cost adsorbent for carbon capture applications. The results support the use of biomass-derived residues in column-based CO 2 mitigation processes, while highlighting the need for further studies on humidity tolerance, regeneration, and scale-up.

Climate sensitivity and glacial inception in the European Alps across marine isotope stage 11 and 10 - Alexandre Honiat; Jonathan L. Baker; Gina E. Moseley; Martin Trüssel; R. Lawrence Edwards; Christoph Spötl (Quaternary Science Reviews, 2026)

Range-wide monitoring reveals demographic vulnerability in Lahille's bottlenose dolphins - Fábio G. Daura-Jorge; Paula Laporta; Ignacio B. Moreno; Paulo H. Ott; Paulo A.C. Flores; Pedro Volkmer de Castilho; André S. Barreto; Rodrigo Cezar Genoves; Carolina Bezamat; Alexandre M.S. Machado; Eduardo R. Secchi; Silvina Botta; et al. (Biological Conservation, 2026)

Interplay Between River Formation and Historical Climatic Changes Drove Diversification of the Thamnomanes caesius and T. schistogynus (Passeriformes, Thamnophilidae) Species Complex Across Amazonian and Atlantic Forests - Henrique Batalha‐Filho; Tibério César Tortola Burlamaqui; Martin Irestedt; Per G. P. Ericson; Jon Fjeldså; Cristina Yumi Miyaki; Alexandre Aleixo (Zoologica Scripta, 2026)
The Amazon and Atlantic forests harbour immense biodiversity shaped by complex evolutionary history with diverse processes leading to species build‐up. We investigated the Cinereous Antshrike species complex ( Thamnomanes caesius and T. schistogynus ) to disentangle the relative contributions of riverine barriers and historical climatic fluctuations to diversification, using large specimen sampling across their entire distribution and a multilocus dataset. Our results revealed hidden genetic diversity, with 13 geographically structured phylogroups largely concordant with Amazonian interfluves and areas of endemism. Species delimitation analyses supported eight of these lineages as independently evolving units, unveiling cryptic diversity within T. caesius . Divergence time estimates indicate that diversification took place during the Pliocene to Late Pleistocene, with signatures of demographic expansion consistent with climate‐driven range dynamics. Our findings underscore a strong association between phylogroups and major river systems, revealing their role as primary drivers of lineage diversification, later modulated by demographic shifts associated with climatic oscillations. Our findings highlight an interplay between geomorphological and climatic factors in shaping avian diversity across the Amazon basin, while also pointing to underestimated taxonomic richness within the Thamnomanes caesius /schistogynus species complex.

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

Forest restoration enhances soil health in tropical agricultural landscapes assessed by soil management assessment framework (SMAF) across land uses and soil types - Vanêssa Lopes Faria; Helen Carla Santana Amorim; Maria Cecília Vieira Totti; Fernanda Almeida Bócoli; Junior Cesar Avanzi; Sérgio Henrique Godinho Silva; Alexandre Uezu; Amanda J. Ashworth; Gerson L. Drescher; Lara Mota Corinto; Samara Martins Barbosa; Vinícius Ferreira Fernandes; et al. (Geoderma Regional, 2026)

Fire, flooding, and herbivory: interactive drivers of taxonomic and functional diversity in a tropical wetland - Alexandre de Matos Martins Pereira; Francielli Bao; Evaldo Benedito de Souza; Maxwell da Rosa Oliveira; Anahi Cerzosimo de Souza Escobar; Rosa Helena da Silva; Suelen Sandim de Carvalho; Arnildo Pott; Valli Joana Pott; Staci Arielli Caires Correia; Geraldo Alves Damasceno-Júnior (Wetlands Ecology and Management, 2026)
Fire and flooding are key ecological filters that shape biodiversity and ecosystem functioning in tropical wetlands. This study investigates the combined effects of prescribed fire, flood regimes, and herbivory on the taxonomic and functional diversity of herbaceous communities in the Brazilian Pantanal, the world’s largest continuous floodplain. Using a long-term experimental design with 32 one-hectare plots distributed across two flood levels (according to the region’s altitude), we applied four fire treatments—Early, Modal, Late, and Control—and assessed species richness, vegetation cover, and functional traits over time. Herbivory was inferred from biomass measurements and incorporated into statistical models. Results revealed that species richness and diversity metrics were highest in low-flood areas subjected to low-intensity fires (Early and Late treatments), while high-intensity fires (Modal) reduced both taxonomic and functional diversity, particularly in highly inundated zones. Herbivory can exert a negative synergistic effect when combined with fire, leading to reduced species richness and functional divergence. Beta diversity analyses showed that species turnover was the dominant process across treatments, although nestedness contributed significantly in high-flood areas exposed to Modal fire. Functional diversity metrics indicated ecosystem resilience, with greater functional regularity and divergence observed in highly inundated areas. The findings underscore the importance of fire regime, flood intensity, and grazing pressure in structuring herbaceous communities. Prescribed fire, when applied with consideration of seasonal timing, flood level, and grazing dynamics, can serve as a strategic tool for maintaining pyrodiversity and ecosystem services in fire-dependent wetlands. However, inappropriate combinations of fire and herbivory may lead to biodiversity loss and functional homogenization, especially in flood-prone zones. These insights are critical for developing adaptive fire management strategies that balance ecological integrity with socio-economic needs in the Pantanal biome.

Intergroup Encounters Among Wild White-Faced Capuchins (Cebus imitator) at a Densely Populated Field Site: Insights into Frequency, Intensity, and Participation - Sarah A. Kovalaskas; Agostina Colosimo; Vasco Alexandre Martins; Juan Carlos Ordoñez; Elena Morera Saborío; Jacinta C. Beehner; Thore J. Bergman; Marcela E. Benítez (International Journal of Primatology, 2026)
Intergroup encounters (IGEs) are a major feature of social life for group-living primates, influencing access to resources, reproductive opportunities, and territory. We examined IGE frequency, intensity, and participation in a high-density population of wild white-faced capuchin monkeys ( Cebus imitator ) at the Capuchinos de Taboga research project in Guanacaste, Costa Rica, using 4 years of data on three capuchin groups (4,984 observation hours, 218 IGEs). The IGE rates at Taboga (0.044/hr) were two to four times higher than those at nearby lower-density sites and did not vary with rainfall or temperature. More than half of IGEs involved high-intensity aggression (chases or contact aggression). Ordinal logistic models showed that the number of focal group participants was a consistent predictor of escalation, with each additional participant increasing the odds of higher intensity by 1.4 times, while ecological variables had little explanatory value. Participation was more likely for older individuals, males, alphas, and when individuals were closer to the center of core use areas; males participated more than females at distances further from the center of core use areas. Females participated in 44% of IGEs, with lactating females less likely to participate than cycling or pregnant females. Our findings suggest that high population density and overlapping ranges drive frequent and aggressive IGEs at Taboga and that escalation is shaped primarily by social rather than ecological factors. These results highlight the importance of social processes in territorial defense and underscore their role in shaping intergroup conflict in areas of high population density.

Environmental gradients shape fish assemblages across estuarine-coastal ecosystems on the eastern Brazilian coast - Rafael L. Oliveira; Germano Henrique Costa Barrilli; Mauricio Hostim-Silva; Ronaldo R. Oliveira-Filho; Helen A. Pichler; André P. Cattani; Ryan Andrades; Ciro C. Vilar; Ana C. Martins; Valéria M. Lemos; Alexandre M. Garcia; Henry L. Spach; et al. (Marine Environmental Research, 2026)

Food use, behavioral and cultural significance of the wood-boring mollusc Turu (Teredo sp.) in the Brazilian Amazon - Danilo Vitor Vilhena Batista; Larissa Aparecida Moreira de Castro; Adriana Fernandes de Barros; Caio Francisco Santana Farias; Ana Paula de Souza; Alexandre Vaz da Silva; Carolina Cerqueira Lima Dittrich; Emilly Monteiro Lopes; Elenice Martins Brasil; Marco Shizuo Owatari; José Luiz Pedreira Mouriño; Maurício Laterça Martins (Food and Humanity, 2026)

Enhancing water management and natural resource use in tropical grassland systems under semi-arid conditions: Dual Kc approach - Cleber Pereira Alves; Danielle da Silva Eugenio; Luciana Sandra Bastos de Souza; Alexandre Maniçoba da Rosa Ferraz Jardim; Carlos André Alves de Souza; Gabriel Italo Novaes da Silva; João Pedro Alves de Souza Santos; Wilma Roberta dos Santos; Álefe Chagas de Lima Costa; Leonardo Francelino de Souza; Jandis Ferreira Nunes de Araujo; Ênio Farias de Franca e Silva; et al. (Biomass and Bioenergy, 2026)

Multidimensional analysis of social withdrawal in the sub-chronic phencyclidine rat model for schizophrenia - Stefani Kalli; Alina Davletova; Lenka Seillier; Martin Kuchař; Alexandre Seillier (Psychopharmacology, 2026)

Parental autonomy-supportive food practices and fruit and vegetable consumption in children: A systematic review and meta-analysis - Elisama Costa Lopes; Priscylla Rodrigues Vilella; Paula Ruffoni Moreira; Sarah Warkentin; Alexandre Siqueira Guedes Coelho; Géssica Mercia de Almeida; Matias Noll; Raquel Machado Schincaglia; Karine Anusca Martins (Appetite, 2026)

Thallium: An overview of its distribution in the environment and its cellular and molecular toxicity - Alexandre Varão Moura; Lucas Aleixo Leal Pedroza; José Domingos Santos da Silva; Airton Cunha Martins; Michael Aschner; Priscila Gubert (Toxicology Letters, 2026)

Tree planting in public squares in an Amazonian capital: are morphometric and ecological aspects considered for decision-making? - Hiago Felipe Cardoso Pacheco; Walmer Bruno da Rocha Martins; Julia Isabella de Matos Rodrigues; Joathan Cipriano Castro; Paula Daniele Martins Moraes; José Rozendo de Lima Silva; Marcos Alexandre Vieira Nascimento Filho; Lucas Lopes da Silva (Trees, 2026)
Key message This study highlights native species’ potential for urban landscaping in the Amazon region, prioritizing safety and ecosystem benefits. Abstract Public squares can be important elements for sustainable urban development and adaptation to climate change, for which an adequate tree composition is key. In the Amazon region, despite the high tree biodiversity, it is common to select unfitted species to compose public squares’ landscaping. Therefore, this research aimed to evaluate the suitability of species used for landscaping of public squares in an Amazonian state capital, based on 4 morphometric and 3 ecological features. 50 public squares were selected and inventoried, tree species were evaluated and classified according to morphometric features (crown projection, slenderness, overhang index, and coverage index), as well as ecological features (leaf habit, fruit weight, and species origin). Species were ranked from the most to the least suitable using weighted values based upon the 7 features employed. The results indicated that, within species currently in used in Belém public squares, Andira inermis (W.Wright) DC. (Cabbage bark) and Ceiba pentandra (L.) Gaertn. (Kapok tree), native to the Amazon region, were the most fitted for public squares landscaping among all the species encountered. Native species such as Bertholletia excelsa Bonpl. (Brazil nut) and Swietenia macrophylla King (Brazilian mahogany), although promising, showed limitations due to their high weighted fruits. This study highlights the need for further research on the use of native Amazonian flora in public squares, especially on its regulating and cultural ecosystem services provision in urban contexts. Additionally, it emphasizes that the implementation of some species should be discontinued due to risks to the safety of urban square visitors and possible damage to urban infrastructure.

Deciphering geochemical variations driven by metasomatism around a lithium pegmatite at the Gonçalo deposit, Portugal: implications for rare-metal exploration in granitic terranes of the European Variscan Belt - Jon Errandonea-Martin; Encarnación Roda-Robles; Idoia Garate-Olave; Sonia García de Madinabeitia; Fernando Sarrionandia; Nora Santos-Loyola; Alexandre Lima (Mineralium Deposita, 2026)
Geochemical halos surrounding Li-rich pegmatites represent a potentially effective vectoring tool for the exploration of concealed deposits. To determine the petrochemical processes triggered by fluids derived from evolved pegmatitic melts in granitic host rocks, this work investigates the geochemical anomalies around a lepidolite-rich pegmatite at Gonçalo (Portugal). The study combines EMPA and LA-ICP-MS analyses of rock-forming minerals from the pegmatite and host monzogranite, along with whole-rock geochemistry. Results indicate that fluid exsolution and infiltration into the monzogranite occurred prior to, or coeval with, the onset of pegmatite crystallization. Boron, W, Mo, and As (± Cs, ± Sn) show preferential incorporation into the fluid phase over remaining in the pegmatitic melt, while F, Be, Li, Ta, Rb, Tl, and Ge likely incorporated into metasomatizing fluids due to their strong enrichment in the melt, rather than a preferential incorporation. Greisenization, zinnwalditization and tourmalinization reactions led to the formation of metasomatic Li-rich micas, quartz, apatite, fluorite, rutile, ilmenite, schorl, and sulfides in the variably metasomatized monzogranite. The Li halo in whole-rock extends 4–5 m from the contact and, together with F, B, As, and Cs enrichments, serves as a reliable pathfinder for buried Li-rich pegmatites, detectable up to twice the dyke thickness. Mica chemistry may offer a more sensitive alternative, with Li, Cs, Sn, and Be representing key components of the geochemical fingerprint associated with Li-rich pegmatites. These results may be applicable to the exploration of rare-element pegmatite deposits in granitic terranes, particularly within the Li-metallogenic province of the European Variscides.

Annatto concentrate supplementation improves systemic redox balance and modulates placental FGF-2 expression in ewes - Leonardo Lima Salata; Calie Castilho; Isabella Guartieri da Silva; Leticia Jalloul Guimarães; Isabella Pereira Azoia; Ines Cristina Giometti; Dionísio Pedro Lopes Kuhn Pinheiro; Alexandre Martins Olivete; Marilice Zundt (Reproductive Biology, 2026)

Enigmatic granite–gneiss domes within the Balkan fold-and-thrust belt, Bulgaria: Tracers of Gondwana–Baltica proximity and large-scale terrane displacement during the waning stages of the Cadomian orogeny? - Jiří Žák; Martin Svojtka; Ianko Gerdjikov; Lukáš Ackerman; Václav Kachlík; Jiří Sláma; Dian A. Vangelov; Alexandre Kounov; R.Damian Nance; J.Brendan Murphy; Jitka Míková (Gondwana Research, 2026)

Cabergoline (Velactis®) administration at dry-off enhances milk yield in subsequent lactation of Holstein and Girolando (Gir × Holstein) cows - Alexandre Henryli de Souza; Philippe Gisbert; Carla Lopes de Azevedo; Alessio Valenza; Viviane Ribeiro Pinheiro Coelho; Emiliana Oliveira Santana Batista; João Paulo Nascimento Martins (Tropical Animal Health and Production, 2026)

Spatiotemporal dynamics of burned areas in the Caatinga Biome, Brazil: a GIS-based assessment - Suelem Farias Soares Martins; Alex Mota dos Santos; Carlos Fabricio Assunção da Silva; Fabrizia Gioppo Nunes; Alexandre Arnhold; Anderson Paulo Rudke; Gerson dos Santos Lisboa (Applied Geomatics, 2026)

Participatory monitoring with VA'A canoes identifies key environmental factors driving microplastic distribution - Alexandre David Dantas; Lucio Brabo; Tatiane Martins Garcia; Friedrich Wolfgang Keppeler; Ryan Andrades; Tamyris Pegado; Wilson Franklin-Jr; Filipa Bessa; L.A.E. Batista de Carvalho; Marcelo de Oliveira Soares; Tommaso Giarrizzo (Marine Pollution Bulletin, 2026)

Contribution of reed bed filter substrate’s microorganisms and vegetation to the biodegradation of road runoff organic micropollutants - Julia Roux; Martin Seidl; Narimane Chibane; Lila Boudahmane; Vanessa Alfonse; Mohamed Barakat; Wafa Achouak; Emilie Caupos; Alexandre Livet; Pascale Neveu; Noureddine Bousserrhine (Journal of Environmental Chemical Engineering, 2026)

Sizing principles and practice of an earth-air heat exchanger (EAHE) for thermal conditioning of buildings - Aloísio Leoni Schmid; George Stanescu; Marcelo Risso Errera; Alexandre Bessa Martins Alves; Alexandre Ruiz Da Rosa (Energy and Buildings, 2026)

Correction: Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)

Alkaloid fraction of Duguetia furfuracea demonstrated anti-inflammatory and antinociceptive effects through decrease of tumour necrosis factor alpha in mice models - João Paulo Costa Rodrigues; Fellipe Alexandre Alves Moraes; Flávio Martins de Oliveira; Débora de Oliveira Lopes; Flávia Carmo Horta Pinto; Aline Aparecida Saldanha; Arthur Ladeira Macedo; Carlos Alexandre Carollo; João Máximo de Siqueira; Adriana Cristina Soares (Inflammopharmacology, 2026)

Therapeutic Efficacy of Monoterpenes in Nile Tilapia Infected With Edwardsiella tarda : A Phytogenic Alternative to Oxytetracycline - Danilo Vitor Vilhena Batista; Adolfo Jatobá; Alexandre Vaz da Silva; Ana Paula de Souza; Caio Francisco Santana Farias; Emilly Monteiro Lopes; Marco Shizuo Owatari; Arlene Sobrinho Ventura; Claudia Andrea Lima Cardoso; Silvia Terra Fontes; Fernando Yugo Yamamoto; Maurício Laterça Martins; et al. (Journal of Fish Diseases, 2026)
The purpose of this research was to assess the effectiveness of a combination of monoterpenes (thymol and carvacrol) in treating juvenile Nile tilapia ( Oreochromis niloticus ) infected with Edwardsiella tarda as a potential substitute for the antibiotic oxytetracycline. The study utilised different concentrations of the monoterpenes blend (MTs): 0.4, 0.6 and 0.8 g kg −1 of feed. A negative control group received a diet without the additive, while a positive control group was given medicated feed containing oxytetracycline (OTC) (11.85 g kg −1 ) for a 10‐day treatment period. Cumulative mortality (%), haematological and immunological parameters were assessed after the feed administration. The negative control group experienced a mortality rate of 53%, while fish treated with medicated feed had a significantly lower mortality rate of 3%. The addition of MTs at concentrations of 0.4 g kg −1 (13% mortality), 0.6 g kg −1 (8% mortality) and 0.8 g kg −1 (0% mortality) also resulted in reduced mortality rates, with the highest concentration showing survival rates comparable to the oxytetracycline group. Following the 10‐day treatment period, no mortality was observed in the treated groups, indicating the efficacy of MTs‐supplemented feed in alleviating the clinical symptoms of Edwardsiellosis. The haematological parameters indicated that as the dosage of MTs increased, the mean corpuscular volume (MCV) decreased. The MCV was significantly lower in the 0.6 and 0.8 g kg −1 treatments compared to the control. Mean corpuscular haemoglobin initially increased with the 0.4 g kg −1 MTs treatment but then decreased with higher doses. The mean corpuscular haemoglobin concentration was higher in the treated groups compared to the control. Red blood cell levels were higher in the 0.8 g kg −1 MTs treatment and lower in the 0.4 g kg −1 treatment. Ht was higher in the control group and lower in the 0.4 g kg −1 MTs treatment. Haemoglobin levels followed a similar trend, with higher values in the control group. The 0.8 g kg −1 MTs treatment had the highest number of total leucocytes and lymphocytes. The control group had the highest number of neutrophils, while the 0.8 g kg −1 MTs group had higher numbers of monocytes, eosinophils, basophils and thrombocytes. The negative control exhibited the lowest antimicrobial titre compared to the OTC and the various concentrations of MTs. The concentrations of MTs (0.4, 0.6 and 0.8 g kg −1 ) demonstrated similar average values and were more effective than the control and OTC. There was no significant difference in agglutinating titre among MTs, control and OTC. Thymol and carvacrol notably decreased the mortality of tilapia infected with E. tarda , with a dosage as high as 0.8 g kg −1 showing equivalent effectiveness to oxytetracycline. Furthermore, they enhanced haematological and immunological parameters, indicating that MTs could be a promising alternative to antibiotic use.

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Satellite evidence for persistent degradation in Brazil's desertification nuclei - Alanderson Firmino de Lucas; Marcos Vinícius da Silva; Alexandre Maniçoba da Rosa Ferraz Jardim; Luciana Sandra Bastos de Souza; Gabriel Thales Barboza Marinho; Lady Daiane Costa de Sousa Martins; João Emanoel Ambrósio Gomes; Gledson Luiz Pontes de Almeida; Jhon Lennon Bezerra da Silva; Wilma Roberta dos Santos; Wagner Martins dos Santos; Elania Freire da Silva; et al. (Remote Sensing Applications: Society and Environment, 2026)

Seasonal patterns and atmospheric modulators of erythemal UV radiation in a sensitive region of the Brazilian Amazon: Implications for environmental health risk assessment - Pericles Vale Alves; Vandoir Bourscheidt; Damaris Kirsch Pinheiro; Rodrigo Martins Moreira; Marcos André Braz Vaz; Mônica Santos; Marcos Antônio Lima Moura; Carlos Alexandre Santos Querino; Paula Regina Humbelino de Melo; Maria Adriana Moreira (Remote Sensing Applications: Society and Environment, 2026)

Law 22017/2023: a dire threat to the Cerrado's survival and Brazil's environmental leadership - Luciane Martins de Araújo; Manuel Eduardo Ferreira; José Antônio Tietzmann e Silva; Giovanni Martins de A. Mascarenhas; Altair Sales Barbosa; Mariana Pires de Campos Telles; José Alexandre Felizola Diniz-Filho; Ludgero Cardoso Galli Vieira; Geraldo Wilson Fernandes; Stephannie Fernandes; José Aluízio Ferreira Lima; Flávia de Figueiredo Machado (Environmental Development, 2026)

Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)
Bees are essential for ecosystem functioning, pollinating many wild and crop plant species. Predicting which species are most vulnerable to global changes, and how their loss may impact ecosystems and human well-being, is critical. Comprehensive information on bee response and effect traits is fundamental to these assessments. However, the Raunkiærian shortfall—insufficient trait data—remains significant for bees, particularly in the Neotropics. Moreover, it remains uncertain whether conservation strategies based on functional diversity from temperate regions can be generalized to the Neotropics. To address this gap, we compiled a comprehensive and validated dataset on Brazilian bee traits, covering 24 traits related to sociality (100% of the species with some information), nesting (88%), body size (71%), and buzzing capacity (42%) on 2,066 Brazilian bee species. The trait data here presented is a crucial resource for evaluating bee species' pollination effectiveness and susceptibility to global change. Comparative analysis with regions with ample trait data—USA, Europe, and China—revealed notable differences. Brazilian bees exhibited a higher prevalence of aboveground nesting species, especially compared to Europe. The proportion of eusocial species was also greater than in Europe and the United States, and more similar to China. Differently from other regions, Brazilian eusocial bees were significantly smaller than their non-eusocial counterparts. These cross-regional comparisons highlight the importance of geographically tailored conservation strategies and underscore the need for extensive trait data to accurately predict regional vulnerabilities and ecological impacts in a rapidly changing world.

Analysis of the energy and nature of bandgap in layered double hydroxides Mg-Al-X and Zn-Al-X (X= Cl − , OH − , CO 3 2 − , or NO 3 − ) - Márcio F. Santos; Pedro Ivo R. Moraes; Sérgio R. Tavares; A.S. Martins; Rodrigo B. Capaz; Fernando Wypych; Alexandre A. Leitão (Applied Clay Science, 2026)

From Rainforests to Open‐Vegetation: The Biogeographic History of Chamaecrista (Leguminosae) in the Neotropics - Juliana Gastaldello Rando; Eduardo Koerich Nery; Anselmo Nogueira; Matheus Martins Teixeira Cota; Alexandre Zuntini; Suzana Alcantara; Gwilym Peter Lewis; Domingos Cardoso; Luciano Paganucci de Queiroz; José Rubens Pirani (Journal of Biogeography, 2026)
Aim We reconstructed the biogeographical history of a species‐rich legume genus by testing alternative hypotheses on the origin and expansion of neotropical open‐vegetation areas, with particular emphasis on the campos rupestres . Location Neotropics. Taxon Chamaecrista (Leguminosae), one of the most speciose genera of the neotropical region. Methods We reconstructed a fossil‐calibrated phylogeny of Chamaecrista species and built a comprehensive database of species occurrences. We fitted and compared nine biogeographic models that differed in area availability and dispersal rates across time frames. These time frames were defined based on major climatic processes that have influenced neotropical open‐vegetation areas. Results and Main Conclusions Under the best‐fitting biogeographical model, Chamaecrista originated in the Amazon during the Mid Eocene. A single ancestral Chamaecrista lineage colonised the campos rupestres before the Late Oligocene–Mid Miocene, when climatic shifts presumably expanded lowland open‐vegetation areas in the Neotropics. Most diversification of Chamaecrista species occurred in the campos rupestres from the Late Miocene to the Quaternary. Multiple ancestral Chamaecrista lineages dispersed from the campos rupestres to the Cerrado from the Mid Miocene onwards, while few lineages dispersed into the Caatinga during the same period. We propose that the campos rupestres might have functioned as a montane reservoir of plant diversity, harbouring lineages that later dispersed into adjacent lowland areas.

Monoterpenes: Functional Additives for Reducing Antibiotics in Aquaculture - Danilo Vitor Vilhena Batista; Barbara Silveira Souza; Caio Francisco Santana Farias; Ana Paula de Souza; Alexandre Vaz da Silva; Emilly Monteiro Lopes; Elenice Martins Brasil; Maurício Laterça Martins; José Luiz Pedreira Mouriño; Marco Shizuo Owatari (Reviews in Aquaculture, 2026)
Aquaculture is a rapidly growing industry that supplies fish for global consumption. However, the intensive production practices have resulted in disease outbreaks, largely driven by the misuse of antibiotics. Natural alternatives, such as monoterpenes, which are biocompounds derived from essential oils obtained from plants like thyme and oregano, are being investigated for their antimicrobial properties. Research has shown that monoterpenes can effectively reduce mortality rates in aquaculture, providing a sustainable solution for disease management without the negative environmental impacts associated with antibiotics. This approach has the potential to promote healthier and more environmentally friendly fish production. Monoterpenes have demonstrated promising results in enhancing fish resistance to pathogens, which could potentially reduce the reliance on antibiotics in aquaculture. However, the economic feasibility of incorporating these compounds into fish diets has not been thoroughly examined, which may hinder their widespread adoption. Clear economic data is essential to evaluate the costs and benefits of using monoterpenes in aquaculture, as uncertainties regarding financial returns could discourage producers and investors. Without this information, the market acceptance of aquafeeds containing monoterpenes may be limited, affecting the progress of cleaner and more sustainable fish farming practices. This review aims to address the gaps in knowledge regarding the widespread use of phytobiotics, specifically focusing on monoterpenes and their impact on the aquaculture industry. It will delve into their mechanisms of action, effectiveness in protecting aquatic animals, and recent developments in combating bacterial infections, while also discussing the risks posed by antimicrobial resistance.

Effects of melatonin or physical exercise application in rats with hepatopulmonary syndrome - Sandielly Rebeca Benitez Fonseca; Elizângela Gonçalves Schemitt; Marilda da Silva Brasil; Gabriela dos Santos Martins; Millena de Oliveira Engeroff; Giorgia Assoni; Alexandre Simões Dias; Jaqueline Nascimento Picada; Claudio Augusto Marroni; Norma Possa Marroni (Toxicology and Applied Pharmacology, 2025)

Production and marketing of wine from the palm tree Hyphaene petersiana Klotzsch ex mart. (Arecaceae) in Banhine National Park, Mozambique - Isabel Uamba; Valdemiro Muhala; Angelina Martins; Cornélio Ntumi; Romari Alejandra Martinez; Alexandre Schiavetti (South African Journal of Botany, 2025)

Preliminary pre-formulation studies of novel mexiletine analogs: Focus on solid-state characterization - Michelle A. Sarcinelli; Thalita M. Silva; Cinira Fandaruff; Viviane S. Vaiss; Larissa L. Lima; Emerson T. da Silva; Marcus V.N. de Souza; Alexandre A. Leitão; Fabio F. Ferreira; Jorge C.S. Costa; Marco A. Martins; Helvécio V.A. Rocha (Next Research, 2025)

Catastrophic wildfires in the Pantanal wetlands as catalysts for transformative change - Alexandre de Matos Martins Pereira; Geraldo Alves Damasceno-Junior; Renata Libonati; Liana O. Anderson; Allan Henrique de Almeida Souza; Bruno Henrique dos Santos Ferreira; Andre Valle Nunes; André Luiz Siqueira; Angelica Guerra; Angelo Cipriano Pacelli Rabelo; Arnaud L.J. Desbiez; Arthur Henrique Leite Falcette; et al. (Environmental Science & Policy, 2025)

Retrospective analysis of sperm metrics in fresh ejaculates of collared peccaries presenting contrasting semen freezability - Samara Sandy Jerônimo Moreira; Romário Parente dos Santos; Luana Grasiele Pereira Bezerra; Ana Glória Pereira; Náyra Rachel Nascimento Luz; Andreza Vieira Brasil; Thales Pinheiro Cavalcanti; Moacir Franco de Oliveira; Simone Maria Massami Kitamura Martins; André Furugen Cesar de Andrade; Alexandre Rodrigues Silva (Cryobiology, 2025)

Flood-Fire Interplays in Wetlands: The Rising of an Actionable Field of Study - Geraldo Alves Damasceno-Junior; Alexandre de Matos Martins Pereira; Bambang Hero Saharjo; Sally Archibald; Beibei Zhang; Bibiana Bilbao; Bruno Henrique dos Santos Ferreira; Carol Kagaba Kairumba; Danilo Bandini Ribeiro; David G. Campbell; Denis Mburu Njoroge; Dennis Twinomujuni; et al. (Wetlands, 2025)
Floods and fires are part of the ecological regime in many wetlands, yet their interconnectedness is poorly explored. Climate extremes, such as droughts and heatwaves, are increasing fire frequency and intensity, while changing rainfall patterns make floods more unpredictable. These events shape wetland physiognomy, species composition, and functioning. Different wetlands experience varying fire exposure; seasonally inundated grasslands burn almost annually, whereas tropical forests rarely catch fire. Some wetlands are more resilient to fire, drought, and floods than others. Communities dependent on wetlands possess ecological knowledge that supports adaptation, enhancing ecosystem resilience. Though often studied separately, floods and fires in wetlands are interrelated. In addition to environmental aspects, social, cultural and associated traditional knowledge dimensions must be included in conservation processes for these environments. A holistic understanding is crucial for conservation. Researchers from sixteen countries propose a new field of study on flood-fire interactions to improve wetland management and sustainability.

Safety and efficacy of an intramuscular bivalent vaccine against influenza and Streptococcus pneumoniae infections in mice - Kimberly Freitas Cardoso; Lara Regina Alves de Souza; Débora Silva Martins; Beatriz Senra Álvares da Silva Santos; Ketyllen Reis Andrade de Carvalho; Sarah Giarola da Silva Messias; Ana Paula de Faria Gonçalves; Rayanne Rosa Do Nascimento Macário; Deyse Julia Ferreira de Jesus; Ana Luiza Pessoa De Mendonça Ângelo; Leonardo de Paula Pereira; Sâmick Layene Moreira Nascimento; et al. (Medical Microbiology and Immunology, 2025)

Investigation of the canine distemper virus in dogs living at public kennels in Northern Brazil: validation of a detection assay - Vitória Sahena Martins Souza Barbosa; Danielle Rodrigues de Deus; Renato da Silva Bandeira; Dielle Monteiro Teixeira; Marcelino Antônio Costa Maués; Márcia Janete de Fátima Mesquita de Figueiredo; Alexandre do Rosário Casseb; Luciana Damascena da Silva; Luana Silva Soares; Yvone Benchimol Gabbay; Jones Anderson Monteiro Siqueira; Hugo Reis Resque (Brazilian Journal of Microbiology, 2025)

Sustainable agriculture with cyanobacterial biomass: Soil experiments on spinach and radish plants - Anabella Massa; Diogo Martins; Joana Azevedo; Ana I. Prieto; Ana M. Camean; Leticia Diez-Quijada; Angeles Jos; Mariana Reimão; Rui Azevedo; Edgar Pinto; Agostinho Almeida; Vitor Vasconcelos; et al. (Science of The Total Environment, 2025)

A comprehensive review on the prevalence and issues caused by Pseudomonas spp. in food - Marcela Aparecida da Silva Alexandre; Tiago Nogueira de Santana; Lorena Arlinda Pena; Analice Martins Duarte; Lucas Cotrim dos Santos; Sílvio Jackson Félix Alves; Renan Machado Dias; Arthur Vinicius de Abreu Oliveira; Solimar Gonçalves Machado; Monique Renon Eller (Food Control, 2025)

An Experimental Method for Measuring Permeability of Fragile, Irregularly Shaped Porous Media - J. Ryan O’Nan; Yejajul Hakim; Cameron Brewer; Alexandre Martin; Savio J. Poovathingal; Michael W. Renfro (Transport in Porous Media, 2025)

Changing isotope compositions of Mg, Ca and Sr in bulk crystalline rocks toward the weathering front: Disentangling inputs of geogenic base cations into ecosystems - Martin Novak; Yulia V. Erban Kochergina; Chris Holmden; Alexandre V. Andronikov; Vaclav Kachlik; Jana Kotkova; Irina E. Andronikova; James W. Kirchner; Jakub Hruška; Frantisek Veselovsky; Frantisek Laufek; Ondrej Pour; et al. (Applied Geochemistry, 2025)

Hyperactive Otolith-Ocular Reflex During Heat Tilt (Rabbit’s Eye Sign) In Anti-Ma2 Rhombencephalitis - João Lemos; Sara Matos; Ana Inês Martins; João Durães; Alexandre Dionísio; Egídio Machado; André Jorge (The Cerebellum, 2025)

Myiasis-causing flies in anurans: new interactions, geographic distribution, and an updated list of records in the Neotropics - Franciele Cristina de Souza; Victor Morais Ghirotto; Alexandre Polletini Neto; Camila Saraiva dos Anjos; André Luís F. da Silva; Rodrigo Lingnau; Emeline da S. Ceccon; Cátia Antunes de Melo-Patiu †; Mirco Solé; Silionamã P. Dantas; Claudio Borteiro; Domingos de J. Rodrigues; et al. (Biologia, 2025)

Prospecting the phytochemical and antioxidant effects in vivo and in vitro of the ethanolic and aqueous extracts of the seeds of Geoffroea decorticans burkart (Fabaceae) on the animal model Tenebrio molitor - Ariana Pereira da Silva; Maria Lúcia da Silva Cordeiro; Verônica Giuliani de Queiroz Aquino Martins; Georggia Fatima Silva Naliato; Raquel Cordeiro Theodoro; Carlos Henrique Salvino Gadelha Meneses; Hugo Alexandre Oliveira Rocha; Kátia Castanho Scortecci (Phytochemistry Letters, 2025)

Antioxidant potential and phytochemical analysis of an infusion obtained from the leaves of Talisia esculenta - Katia Castanho Scortecci; Maria Lúcia da Silva Cordeiro; Leticia Barbosa Santos; Verônica Giuliani de Queiroz Aquino Martins; Ariana Pereira da Silva; Weslley de Souza Paiva; Hasan Karimi; Ana Carolina Luchiari; Hugo Alexandre Oliveira Rocha; Fabio Boylan (Phytochemistry Letters, 2025)

Validation of a desertification monitoring model in a semiarid region with the support of machine learning techniques - José Francisco da Cruz Neto; Francisco Charles dos Santos Silva; Carlos André Alves de Souza; Alexandre Maniçoba da Rosa Ferraz Jardim; Wilma Roberta dos Santos; Lady Daiane Costa de Sousa Martins; Wagner Martins dos Santos; Alan Mario Zuffo; Thieres George Freire da Silva (Journal of South American Earth Sciences, 2025)

Reconstructing the trophic structure of Maastrichtian elasmobranch communities in Morocco using calcium isotopes - Alexandre Assemat; Sylvain Adnet; Jeremy E. Martin (Gondwana Research, 2025)

Protection and safety of aluminum hydroxide adjuvant and chimeric antigen containing predicted epitopes from bacteria murC gene in Aeromonas hydrophila fish infection - Jojo Silva Rodrigues; Maria Roméria da Silva; Camila Aparecida Martins; Laura Alves Zuanon; Karina Ventura Boechat Martins; Pedro Segantini Tótola; Jheneze Guimarães Pereira Rocha; Mariana Grôppo Parma; Isabel Samila Lima Castro; Tarciza Fernandes Nascimento; Allan Rodrigues Pires; Filipe Silveira Azevedo; et al. (Fish & Shellfish Immunology, 2025)

Litter removal has long-lasting harmful effects on nutrient dynamics in a tropical secondary forest - Julia Isabella de Matos Rodrigues; Walmer Bruno Rocha Martins; Victor Pereira de Oliveira; Luiz Fernandes Silva Dionísio; Hiago Felipe Cardoso Pacheco; Marcos Alexandre Vieira Nascimento Filho; Manoel Tavares de Paula; Francisco de Assis Oliveira; Gustavo Schwartz (Plant and Soil, 2025)

Plant-soil microbiome feedback under post-pasture tropical ecotone forest regeneration - Franciele Muchalak; Anderson Santos de Freitas; Luís Felipe Guandalin Zagatto; Gabriel Silvestre Rocha; Guilherme Lucio Martins; Solange dos Santos Silva-Zagatto; Thierry Alexandre Pellegrinetti; Siu Mui Tsai; Acacio Aparecido Navarrete (Applied Soil Ecology, 2025)

Plot level nitrogen stock is enhanced by a young agroforestry system in a mediterranean environment - Mubarak Mahmud; Isabelle Bertrand; Jerôme Ngao; Soline Martin-Blangy; Stéphane Bazot; Nicolas Delpierre; Paul Leadley; Gaëlle Vincent; Claire Marsden; Rémi Dugue; Alexandre Morfin; Marion Forest; et al. (Agroforestry Systems, 2025)
A 2-years assessment of nitrogen (N) stocks, tree N safety nets (from a 15 N labeling experiment), and biological N fixation was conducted in a Mediterranean agroforestry system in southern France. The study aimed to quantify N retention in agroforestry. The study area is characterized by a skeletic rhodic luvisol soil, a mean annual temperature of 15.5 °C, and an average annual precipitation of 556 mm. N and 15 N were quantified across all system components, which are N-fixing black locust trees, crops, weed plants, understory vegetation strips (UVS), rhizospheric soil, and soil microbial biomass. A split-plot experimental design was used, with agroforestry (AF) and monoculture (MC) plots. 15 N labeling was applied to track N fluxes and determine tree nutrient absorption over time. We hypothesized that tree root growth and nutrient leaching would enhance the safety-net effect, improving N retention. Results showed that crops in AF had lower N stocks (13–30% less than MC), but tree and UVS contributions compensated for the deficit, leading to a 62% increase in total plot-level N stock in 2022. The Relative Nitrogen Content was 0.97 in 2021 and 1.63 in 2022. While no 15 N was detected in trees in the first year (70 days after labeling), 2% of applied 15 N was recovered in trees 14 months post-labeling. % of N derived from atmospheric N 2 (%Ndfa) ranged from 52 to 68%, with trees fixing 14–18 kg N ha −1 . We confirmed that agroforestry enhances N retention, but further research is needed to quantify leaching and gaseous losses of nitrogen.

Improving presurgical language mapping by a method for optimally sorting independent components of resting-state fMRI - Beatriz Vale; Diogo Duarte; Ricardo Vigário; Christopher Benjamin; Pedro Vilela; Martin Lauterbach; Alexandre Andrade (Brain Imaging and Behavior, 2025)

Polymetallic interactions of Zn-Pb-Cu in blue/green-colored speleothems from Malaval Cave (France) - Martin Vlieghe; Gaëtan Rochez; Stéphane Pire-Stevenne; Alexandre Felten; Marie Dechamps; Sébastien R. Mouchet; Francesca Cecchet; Olivier Bruguier; Jean-Louis Galéra; Gipsi Lima-Mendez; Marc Llirós Dupré; Johan Yans (Geochemistry, 2025)

Is it safe to use bone tissue for transplants stored for more than five years in a human tissue bank? - Carlos Alexandre Curylofo Corsi; Katia Carmen Gabriel Scarpelini; Rodolfo Leandro Bento; Joel Bel Del Pádua; Luis Fernando Zitei-Baptista; Alan Vinicius Assunção-Luiz; Álefe Saloum Cintra; Denissani Aparecida Ferrari Santos dos Lima; Flávio Luís Garcia; Celso Herminio Ferraz Picado; Luís Gustavo Gazoni Martins (Cell and Tissue Banking, 2025)

Historical and spatial analysis of the water quality in a tropical eutrophic system: a case study of remediation strategies in Pampulha reservoir, Brazil - Tiago Antônio Figueiredo; Luciana Pena Mello Brandão; Gabriela Rabelo Andrade; Alexandre Flávio Assunção; Hugo Luiz Martins de Paula; Camila Costa Amorim (Environmental Monitoring and Assessment, 2025)

Single-cell proteins as alternative sources of proteins and nutrients - Sílvio Jackson Félix Alves; Elizabeth Bárbara Epalanga Pires; Marcela Aparecida da Silva Alexandre; Claudia Cristina Auler do Amaral Santos; José Guilherme Prado Martin; Pedro Henrique Campelo; Evandro Martins; Monique Renon Eller (Food Research International, 2025)

Miocene marine vertebrate trophic ecology reveals megatooth sharks as opportunistic supercarnivores - Jeremy McCormack; Iris Feichtinger; Benjamin T. Fuller; Klervia Jaouen; Michael L. Griffiths; Nicolas Bourgon; Harry Maisch; Martin A. Becker; Jürgen Pollerspöck; Oliver Hampe; Gertrud E. Rössner; Alexandre Assemat; et al. (Earth and Planetary Science Letters, 2025)

Dietary supplementation with açai (Euterpe oleracea) improved the haemato-immunological parameters and growth performance of koi carp (Cyprinus Carpio Linnaeus, 1758) - Alexandre Vaz da Silva; Emilly Monteiro Lopes; Domickson Silva Costa; Gracienhe Gomes dos Santos; Caio Francisco Santana Farias; Paola Capistrano dos Santos; Ana Paula de Souza; Gabriele Bueno dos Anjos; Manoela Clemente Fernandes; Arlene Sobrinho Ventura; Claudia Andrea Lima Cardoso; Marco Shizuo Owatari; et al. (Veterinary Research Communications, 2025)

Bacterial and nematode communities associated with soybean-cultivated soils from two native Brazilian biomes - Felipe Martins do Rêgo Barros; Roy Neilson; Madeline Giles; Sandra Caul; Alexandre Pedrinho; Claudio Marcelo Gonçalves de Oliveira; Luiz Antônio da Silva; Victor Lucas Vieira Prudêncio de Araújo; Lucas William Mendes; Fernando Dini Andreote (Applied Soil Ecology, 2025)

Assessing the impact of Samanea tubulosa trees on methane emissions and its potential as a feed supplement for ruminants in silvopastoral systems - Simón Pérez-Márquez; Vagner Ovani; Vanderson Eliel Meira; Alexandre de Azevedo Olival; Helder Louvandini; Jozivaldo Prudencio Gomes de Morais; Mariana Campana; Tiago Antônio Del Valle; Rogério Martins Mauricio; Adibe Luiz Abdalla (Agroforestry Systems, 2025)
Silvopastoral systems (SPS) have been recognized for their multiple benefits, including animal welfare, performance, greenhouse gas mitigation, forage quality, and overall ecosystem services. However, the availability of native tree components for SPS is limited, leading to the prevalent use of exotic species. This study aimed to investigate the potential of the native leguminous tree, Samanea tubulosa , in SPS for sustainable livestock production. Chemical-bromatological analysis of S. tubulosa fruits revealed a high crude protein content and non-structural carbohydrates (NSC). An in vivo assay with Dorper lambs showed that increasing levels of S. tubulosa in diets had a linear effect on both neutral detergent fiber (NDF) and NSC intake, with reduced NDF digestibility. However, no significant effects were observed on dry matter, organic matter, or crude protein digestibility. Moreover, methane (CH 4 ) emissions decreased with increasing S. tubulosa inclusion, with daily CH 4 emissions being up to 39% lower in animals fed with S. tubulosa compared to those without. Dendrometric characteristics of S. tubulosa trees indicated an average height of 8.79 m and a canopy area of 92.04 m 2 when in pasture, with an average fruit production of 56 kg per tree, allowing for the inclusion of 108 trees per hectare. The study highlights the potential of S. tubulosa as a natural feed supplement for ruminants in SPS during the dry season, offering environmental and economic benefits. The integration of this native species into grazing systems can promote sustainable livestock production practices while contributing to the conservation of Brazilian biomes.

Reconciling community-level responses of wild bees to highly anthropized landscapes - William Fiordaliso; Sara Reverte; Guillaume Ghisbain; Thomas Wood; Eulalie Ruelle; Alexandre Lefèbvre; Alexandre Reese; Martin Loockx; Denis Michez; Kévin Tougeron (Landscape and Urban Planning, 2025)

Evaluation of web post-buckling in high-strength cellular steel and high-strength concrete composite beams: A numerical study - Jonas Yoshihiro Namba; Igor Eduardo da Silva Ribeiro; Haron Cesar Almeida Tavares; Alexandre Rossi; Pablo Augusto Krahl; Carlos Alberto Benedetty Torres; Carlos Humberto Martins (Engineering Structures, 2025)

Range expansion and reconnection of historical populations in the Eurasian otter (Lutra lutra) in France: Insights from heterogeneous data and integrated species distribution modelling - Simon Lacombe; Sébastien Devillard; Cécile Kauffmann; Mélanie Aznar; Ondine Dupuis; Christine Fournier-Chambrillon; Estelle Isère-Laoué; Camille Fraissard; Nicolas Fuento; Tiphaine Heugas; Alexandre Martin; Magali Perrin; et al. (Biological Conservation, 2025)

The squat jump and sprint force–velocity profiles of elite female football players are not influenced by the menstrual cycle phases and oral contraceptive use - Jérémie Bouvier; Pierre-Hugues Igonin; Mélanie Boithias; Alexandre Fouré; Alain Belli; Nathalie Boisseau; Cyril Martin (European Journal of Applied Physiology, 2025)

Environmental Correlates of Juvenile Fish (Trachinotus marginatus) in a Marine Surf-Zone Revealed ENSO Influence and Interannual Declining Trend in Abundance - Ana Luíza Santos Araújo; Ana Carolina Martins; Alexandre Miranda Garcia (Estuaries and Coasts, 2025)

Model seasonal and proxy spatial biases revealed by assimilated mid-Holocene seasonal temperatures - Shuo Hao; Xu Zhang; Yanwu Duan; Evan J. Gowan; Jiang Zhu; Alexandre Cauquoin; Jie Chen; Martin Werner; Fahu Chen (Science Bulletin, 2025)

Field measurements of wave and flow dynamics along a high-energy meso-macrotidal coast adjacent to a large estuary mouth - Marine Vandenhove; Bruno Castelle; Alexandre Nicolae Lerma; Vincent Marieu; Kévin Martins; Vincent Mazeiraud (Estuarine, Coastal and Shelf Science, 2025)

Tissue distribution of Ocimum basilicum essential oil in Nile tilapia Oreochromis niloticus after anesthesia - Emilly Monteiro Lopes; Arlene Sobrinho Ventura; Claudia Andrea Lima Cardoso; Alexandre Vaz da Silva; Caio Francisco Santana Farias; Domickson Silva Costa; Ana Paula de Souza; Danilo Vitor Vilhena Batista; Silvia Terra Fontes; Gabriela Tomas Jerônimo; José Luiz Pedreira Mouriño; Maurício Laterça Martins (Veterinary Research Communications, 2025)

Low carbon footprint of Nile tilapia farming with recirculation aquaculture - Anderson M. de Melo Júnior; Sarian Kosten; Vitor Luis da C. Duque; Alexandre A.O. Santos; André M. Amado; Laís C. Soranço; Jochem Dreise; Arthur C. Martins; Jonas Nasário; Ana Paula Dalbem Barbosa; Ive S. Muzitano; Giovana M. Cardoso; et al. (Resources, Conservation and Recycling, 2025)

Elastic thickness and residual gravity anomaly applied to the northern Brazilian basins: Unravelling the volcanic-sedimentary history linked to the Central Atlantic Ocean opening - Gabriel Leal Rezende; Afonso Cesar Rodrigues Nogueira; Nelson de Lima Ribeiro-Filho; Alexandre Ribeiro Cardoso; Renato Sol Paiva de Medeiros; Cristiano Mendel Martins; Davis Carvalho de Oliveira (Gondwana Research, 2025)

Steel-UHPC composite castellated beams under hogging bending: Experimental and numerical investigation - Vinicius Moura de Oliveira; Vinicius Brother dos Santos; Alexandre Rossi; André Vitor Benedito; Pablo Augusto Krahl; Carlos Humberto Martins; Flávio de Andrade Silva; Daniel Carlos Taissum Cardoso (Engineering Structures, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Immature Stages of the Greater Cutworm, Feltia repleta (Walker, 1857) (Noctuidae: Noctuinae), with Notes on its Host Plants and Distribution - Fernando Maia Silva Dias; Alexandre Specht; German San Blas; Mirna Martins Casagrande (Neotropical Entomology, 2025)

Propionate consumption activates mitochondrial activity, methylcitrate cycle and promotes changes in the cell wall of the human pathogen Histoplasma capsulatum - Luiz Paulo Araújo Santos; Dayane Moraes; Leandro do Prado Assunção; Matthias Brock; Kassyo Lobato Potenciano da Silva; Andréa Rodrigues Chaves; Rafael Oliveira Martins; Mirelle Garcia Silva-Bailão; Célia Maria de Almeida Soares; Alexandre Melo Bailão (Fungal Biology, 2025)

Assessing genetics, biophysical, and management factors related to soybean seed protein variation in Brazil - María Sol Zelaya Arce; Eduardo Lago Lago Tagliapietra; José Eduardo Minussi Winck; Alexandre Ferigolo Alves; Felipe Schmidt Dalla Porta; Tiago Broilo Facco; Nereu Augusto Streck; Mauricio Fornalski Soares; Gregori Da Encarnação Ferrão; Daniel Debona; Claudio Hideo Martins da Costa; Rodrigo Merighi Bega; et al. (European Journal of Agronomy, 2025)

Designing Burn Windows for Integrated Fire Management in Wetlands: Why Should Flooding Not Be Overlooked? - Maxwell da Rosa Oliveira; Alexandre de Matos Martins Pereira; Francielli Bao; Bruno Henrique dos Santos Ferreira; Adriana Espinoza Fernando; Fabio de Oliveira Roque; Arnildo Pott; Geraldo Alves Damasceno-Junior; Danilo Rafael Mesquita Neves (Wetlands, 2025)

Pan-Canadian Predictive Modeling of Lithium–Cesium–Tantalum Pegmatites with Deep Learning and Natural Language Processing - Mohammad Parsa; Christopher J. M. Lawley; Tarryn Cawood; Tania Martins; Renato Cumani; Steven E. Zhang; Aaron Thompson; Ernst Schetselaar; Steve Beyer; David R. Lentz; Jeff Harris; Hossein Jodeiri Akbari Fam; et al. (Natural Resources Research, 2025)
The discovery of new lithium resources is essential because lithium plays a vital role in the manufacturing of green technology. Along with brines and volcano–sedimentary deposits, approximately a one-third share of global lithium resources is associated with lithium-cesium-tantalum (LCT) pegmatites, with Canada hosting numerous examples. This research applied generative adversarial networks, natural language processing, and convolutional neural networks to generate mineral prospectivity models and support exploration targeting for Canadian LCT pegmatites. Geoscientific text data included within public bedrock geology maps and natural language processing were used to convert conceptual targeting criteria into evidence layers that complement more traditional, geophysical and geochronological data used for mineral prospectivity modeling (MPM). A multilayer architecture of convolutional neural networks, including an attention mechanism, was designed for data modeling. This architecture was trained and validated using variable synthetically generated class labels, input image sizes, and hyperparameters, resulting in an ensemble of 1000 models. The uncertainty of the ensemble was analyzed using a risk–return analysis, yielding a bivariate choropleth risk–return plot that facilitates the interpretation of prospectivity models for downstream applications. This was further complemented by employing post hoc interpretability algorithms to translate the black-box nature of neural networks into comprehensible content. The low-risk and high return class of our prospectivity models reduces the search space for discovering LCT pegmatites by 88%, delineating 99% of known LCT pegmatites in Canada. The results of this study suggest that our workflow (i.e., combining synthetic data generation, natural language processing, convolutional neural networks, and uncertainty propagation for MPM) facilitates decision-making for regional-scale lithium exploration and could also be applied to other mineral systems.

(Bio)Hybrid System of Layered Double Hydroxides and Dapsone: One-Pot Synthesis, Structural Characterization and Cell Viability - Felipe de Albuquerque Marinho; Amanda Damasceno Leão; Antônia Carla de Jesus Oliveira; Luise Lopes Chaves; Jessica Cavalcante Martins; Izabel Maria de Melo Amaral; Mylena Karolina Oliveira Do Amaral; Lucas José de Alencar Danda; Raiza Raianne Luz Rodrigues; Rafael Alexandre Raimundo; Klinger Antonio da Franca Rodrigues; Mônica Felts de La Rocca Soares; et al. (Journal of Pharmaceutical Innovation, 2025)

Capture of gaseous and fine particulate pollutants emitted in the biomass post-combustion process - Maria Angélica Martins Costa; Alexandre Jorge Duarte de Souza; Bruna Sampaio Mello; Eliza Almeida de Oliveira; Lucas Freitas Oliveira; Geisa Albini; Arnaldo Sarti; Kelly Johana Dussán (Environmental Science and Pollution Research, 2025)

Concurrent validity and reliability of global positioning systems for measuring intense running and peak speed performance: a systematic review - Hadi Nobari; Alexandre Duarte Martins; João Paulo Brito; Elena Mainer-Pardos; Pablo Valdés-Badilla; Rafael Oliveira (German Journal of Exercise and Sport Research, 2025)

Differential stimulation of phosphorus-mobilizing bacteria by common bean genotypes in Amazonian Dark Earth and Agricultural Soils with varying fertility levels - Mariley Fonseca; Alexandre Pedrinho; Luis Fernando Merloti; João William Bossolani; Leandro Nascimento Lemos; Mayara Martins e Martins; Lucas William Mendes; Tsai Siu Mui (Rhizosphere, 2025)

Chemical characterization, antibacterial and antifungal activity of honey pots and pollen pots obtained from the stingless bee Tetragonisca angustula (Latreille, 1811) - Nair Silva Macêdo; Zildene de Sousa Silveira; Débora Menezes Dantas; Cristina Rodrigues dos Santos Barbosa; Antonia Thassya Lucas dos Santos; Thiago Araújo de Medeiros Brito; Josean Fechine Tavares; Débora Odília Duarte Leite; Priscilla Ramos Freitas Alexandre; José Galberto Martins da Costa; Cícera Datiane de Morais Oliveira-Tintino; Henrique Douglas Melo Coutinho; et al. (Food and Chemical Toxicology, 2025)

Molecular detection of respiratory viruses: an observational study on respiratory co-infections in children and adults - Tereza de Jesus Pinheiro Gomes Bandeira; Ana Leticia Sousa de Oliveira; Luis Fernando Pontes Martins; Rodrigo Moreira Matos; Sheryda Raynna Nobre Guedes dos Santos; Mateus Cedro Lopes; Raimundo Tadeu Pires Sobreira; Hermano Alexandre Lima Rocha (Brazilian Journal of Microbiology, 2025)

Unlocking the potential of Airborne LiDAR for direct assessment of fuel bulk density and load distributions for wildfire hazard mapping - Olivier Martin-Ducup; Jean-Luc Dupuy; Maxime Soma; Juan Guerra-Hernandez; Eva Marino; Paulo M. Fernandes; Ariadna Just; Jordi Corbera; Marion Toutchkov; Charlie Sorribas; Jerome Bock; Alexandre Piboule; et al. (Agricultural and Forest Meteorology, 2025)

Relief determines patterns of structure and composition of tree vegetation in seasonal forests in the Brazilian Cerrado - Maxwell R. Oliveira; Francielli Bao; Evaldo B. Souza; Arnildo Pott; Rosa H. Silva; Pedro Isaac; Joanice Lube Battilani; Vivian Ribeiro Baptista Maria; Edna Scremin-Dias; Vali Joana Pott; Alexandre de Matos Martins Pereira; Geraldo A. Damasceno Junior (Brazilian Journal of Botany, 2025)

Lippia origanoides essential oil increases longevity and ameliorates β-amyloid peptide-induced toxicity in Caenorhabditis elegans - Ana Maria Henrique Moniz; Francisco Humberto Xavier Junior; Giovanna Melo Martins Silva; Ana Cristina Gonçalves Reis de Melo; Maylla Maria Correia Leite Silva; Weslley Souza Paiva; Hugo Alexandre Oliveira Rocha; Luiz Antônio Mendonça Alves da Costa; Antônio Alves de Melo Filho; Riva de Paula Oliveira (Natural Product Research, 2025)

Taxonomy and Biological Aspects of Gonatopus Ljungh (Hymenoptera: Dryinidae): Description of a New Species, Sexual Association and Record of Host from Northeast Brazil - Gabriel Luiz Celante; Alexandre Cruz Domahovski; Benoit Jean Bernard Jahyny; André Luis Martins (Neotropical Entomology, 2025)

Evaluation of Scalibor® deltamethrin collar chronic exposure in dogs - Larissa T.P. Rodrigues; Andriele F. Qualhato; Carolle V.M. Sprícigo; Kelly C.A. Arantes; Rayanne H.S. da Silva; Alexandre C.M. Barros; Monica C. Vicente; Murilo R. Souza; Luiza G.F. de Paula; Danilo Roman-Campos; Artur S. Miranda; Danieli B. Martins; et al. (Research in Veterinary Science, 2025)

Boron isotopic characterization of ophiolitic serpentinites from Atlin terrane, Canadian Cordillera - Adina Bogatu; Loïc Labrousse; Céline Martin; Alexandre Zagorevski; Jean H. Bédard; Alain Tremblay (Lithos, 2025)

Spectrophotometric determination of bisphenol A in beverages using multi-dispersion calibration - Vivian Maringolo; Alexandre Z. Carvalho; Paula Homem-de-Mello; Mateus Zanotto; Fernanda C.O.L. Martins; Wanessa R. Melchert; Diogo L. Rocha (Food Control, 2025)

Is the amount of parenchyma in storage organs a good predictor of non-structural carbohydrate storage in herbs? - Alexandre Ferraro; F. Curtis Lubbe; Martin Bitomský; Alena Bartušková; Michael Bartoš; Štěpán Janeček; Jana Martínková; Jitka Klimešová (Plant and Soil, 2025)

Integrating plasmasphere, ionosphere and thermosphere observations and models into a standardised open access research environment: The PITHIA-NRF international project - Anna Belehaki; Ingemar Häggström; Tamas Kiss; Ivan Galkin; Anders Tjulin; Mária Miháliková; Carl-Fredrik Enell; Gabriel Pierantoni; Yin Chen; Gergely Sipos; Sean Bruinsma; Viviane Pierrard; et al. (Advances in Space Research, 2025)

Selenium agronomic biofortification and genotypic variability in physiological responses of cowpea plants under field conditions - Elcio Ferreira Santos; Eduardo Comparsi Filho; Luiz Eduardo Morais Fernandes Fontes; Mateus Andrey Pires Silva; Gutierres Nelson Silva; Alexandre Alonso Oliveira; Maurisrael de Moura Rocha; Vinícius Martins Silva; André Rodrigues Reis (Acta Physiologiae Plantarum, 2025)

Temperature-induced changes in the hematological and biochemical parameters of Nile tilapia anesthetized with Ocimum basilicum - Paola Capistrano dos Santos; Emilly Monteiro Lopes; Arlene Sobrinho Ventura; Claudia Andrea Lima Cardoso; Alexandre Vaz da Silva; Domickson Silva Costa; Marília Tedesco; Gabriela Tomas Jerônimo; Maurício Laterça Martins (Aquaculture International, 2025)

Plasma miRNAs Correlate with Structural Brain and Cardiac Damage in Friedreich’s Ataxia - Thiago M. Peluzzo; André S. Vieira; Alexandre H. B. Matos; Cynthia Silveira; Mariana Martin; Otávio R. C. Filho; Thiago J.R. Rezende; Alberto R. M. Martinez; Marcondes C. França (The Cerebellum, 2024)

Construction, monitoring, and efficiency of a biofilter treating a high flow, lean, landfill gas - Jessica Leindorf de Almeida; Joelle Dumouchel; Jeovana Jisla das Neves Santos; Yohan Dulac; Alexandre R. Cabral; Martin Héroux (Waste Management, 2024)

Comprehensive characterization of European house dust contaminants: Concentrations and profiles, geographical variability, and implications for chemical regulation and health risk - Peter Haglund; Nikiforos A. Alygizakis; Adrian Covaci; Lisa Melymuk; Pernilla Bohlin Nizzetto; Pawel Rostkowski; Alexandre Albinet; Sylvana Alirai; Dagny Aurich; Stefan Bieber; Ana Ballesteros-Gómez; Amanda A. Brennan; et al. (Science of The Total Environment, 2024)

A transcontinental threat: Plastic waste from Africa invades Brazil's coast - Lucio Brabo; Laercio L. Martins; Ryan Andrades; Carlos E.P. Teixeira; Adriana Pereira do Nascimento; Rufino Neto Andrade de Azevedo; Luís E.A. Bezerra; Rivelino M. Cavalcante; Kelly Ferreira Cottens; Romulo Alexandre Soares; Paulo Henrique Gomes de Oliveira Sousa; Tarin F. Mont'Alverne; et al. (Science of The Total Environment, 2024)

Toxic and non-toxic cyanobacterial biomass as a resource for sustainable agriculture: A lettuce cultivation experiment - Anabella Massa; Érica Santos; Diogo Martins; Joana Azevedo; Mariana Reimão; Agostinho Almeida; Rui Azevedo; Edgar Pinto; Vitor Vasconcelos; Alexandre Campos; Marisa Freitas (Environmental Research, 2024)

Geostatistical modeling of the rainfall patterns and monthly multiscale characterization of drought in the South Coast of the Northeast Brazilian via Standardized Precipitation Index - Marcos Vinícius da Silva; Jhon Lennon Bezerra da Silva; Maria Beatriz Ferreira; Lizandra de Barros de Sousa; Abelardo Antônio de Assunção Montenegro; Jorge Manuel Guieiro Pereira Isidoro; Héliton Pandorfi; José Francisco de Oliveira-Júnior; Helena Maria Neto Paixão Vazquez Fernandez; Fernando Miguel Granja-Martins; Alexandre Maniçoba da Rosa Ferraz Jardim; Thieres George Freire da Silva; et al. (Atmospheric Research, 2024)

Differential effects of fresh and composted organic wastes on soil bacterial community and maize growth - Guilherme Lucio Martins; Thierry Alexandre Pellegrinetti; Anderson Santos de Freitas; Gabriel Silvestre Rocha; Gabriel Gustavo Tavares Nunes Monteiro; Lucas William Mendes; Siu Mui Tsai; Fernando Carvalho Oliveira; Jussara Borges Regitano (Applied Soil Ecology, 2024)

Exploring biodegradable alternatives: microorganism-mediated plastic degradation and environmental policies for sustainable plastic management - Rita de Cássia Garcia Simão; Paula Maria Carneiro Rocha; Júlia Thays Kava Martins; Maurício Turkiewicz; Jacqueline Plewka; José Luis da-Conceição Silva; Alexandre Maller; Marina Kimiko Kadowaki; Álvaro Pereira Sampaio Costa-Júnior (Archives of Microbiology, 2024)

FreshLanDiv : A Global Database of Freshwater Biodiversity Across Different Land Uses - Minghua Shen; Roel van Klink; Alban Sagouis; Danielle K. Petsch; Deborah Atieno Abong'o; Janne Alahuhta; Salman Abdo Al‐Shami; Laura Cecilia Armendáriz; Mi‐Jung Bae; Tiago Octavio Begot; Jerome Belliard; Jonathan Peter Benstead; et al. (Global Ecology and Biogeography, 2024)
Motivation Freshwater ecosystems have been heavily impacted by land‐use changes, but data syntheses on these impacts are still limited. Here, we compiled a global database encompassing 241 studies with species abundance data (from multiple biological groups and geographic locations) across sites with different land‐use categories. This compilation will be useful for addressing questions regarding land‐use change and its impact on freshwater biodiversity. Main Types of Variables Contained The database includes metadata of each study, sites location, sample methods, sample time, land‐use category and abundance of each taxon. Spatial Location and Grain The database contains data from across the globe, with 85% of the sites having well‐defined geographical coordinates. Major Taxa and Level of Measurement The database covers all major freshwater biological groups including algae, macrophytes, zooplankton, macroinvertebrates, fish and amphibians.

Clinical and pathological findings of Africanized bee (Apis mellifera) envenomation in horses - Beatriz da Costa Kamura; Lukas Garrido Albertino; Ricardo Romera Cavallari; Larissa Queiroz de Souza; Lucas Troncarelli Rodrigues; Isabella Barros de Sousa Pereira; Noeme Sousa Rocha; Regina Kiomi Takahira; Wanderson Adriano Briscola Pereira; Alexandre Secorun Borges; José Paes de Oliveira-Filho; Rogério Martins Amorim (Toxicon, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Antimicrobial and anthelmintic effects of copper nanoparticles against Koi carp parasites and their toxicity - Gracienhe Gomes dos Santos; Liseth Vanessa Perengue Riofrio; Ana Paula Sousa; Paola Capistrano Santos; Alexandre Vaz Silva; Emilly Monteiro Lopes; Domickson Silva Costa; Jucimauro de Araújo Pereira Júnior; Giulia Beatrice Ferreira; Graziella Vivine Gonçalves de Matos Silva; Marilia Tedesco; Diego José Nogueira; et al. (Journal of Fish Diseases, 2024)
This study investigated the in vitro antimicrobial and anthelmintic effect of copper nanoparticles (CuNPs) against the bacterium Aeromonas hydrophila , the monogeneans Dactylogyrus minutus , Dactylogyrus extensus , Gyrodactylus cyprini , and the cestode Schyzocotyle acheilognathi , as well as their toxicity to Cyprinus carpio Koi. In the antimicrobial in vitro test, the inhibition zone method and minimum inhibitory concentration (MIC) were performed. In order to determine the time and efficacy of monogenean parasite mortality, the parasites were exposed to CuNP concentrations of 20, 50, 100, 150, 200, and 300 mg L −1 , and a control group with tank water and one with copper sulphate pentahydrate (CuSO 4 . 5 H 2 O) at a concentration of 0.3 mg L −1 , performed in triplicate. The parasites were observed every 10 min for 300 min, and mortality was recorded. For the cestodes, parasites were immersed in CuNP concentrations of 50, 100, 150, and 300 mg L −1 . At the end of the in vitro tests, the anthelmintic efficacy of each treatment was calculated. To assess the tolerance and toxicity in fish, they were exposed to CuNP concentrations of 0.6, 1.25, 2.5, 5, 10, 20, and 50 mg L −1 for 12 h. The MIC demonstrated that CuNPs effectively inhibited the growth of A . hydrophila up to a dilution of 12,500 mg L −1 and showed an inhibition zone of 14.0 ± 1.6 mm for CuNPs. The results of anthelmintic activity showed a dose‐dependent effect of concentration for both groups of parasites, with the most effective concentration being 300 mg L −1 in 120 min. In the toxicity test, the carps showed tolerance to lower concentrations. The study indicated that CuNPs were effective against the studied pathogens. However, it proved to be toxic to fish at high concentrations. The use of low concentrations is recommended still requires further investigation.

Exploring diet shifts and ecology in modern sharks using calcium isotopes and trace metal records of their teeth - Alexandre Assemat; Sylvain Adnet; Kani Bayez; Auguste Hassler; Florent Arnaud‐Godet; Frederik H. Mollen; Catherine Girard; Jeremy E. Martin (Journal of Fish Biology, 2024)
Sharks occupy all living environments of the marine realm as well as some freshwater systems. They display varied and flexible feeding behaviours, but understanding their diet remains challenging due to their elusive ecology and the invasiveness of stomach content analyses in regard of their threatened status. As a potential alternative, we discuss the variability in δ 44/42 Ca values recorded in the tooth enamel of size‐graded individuals belonging to three species of large sharks with distinct diets ( Isurus oxyrinchus , Hexanchus griseus and Carcharodon carcharias ). The preliminary results highlight shifts in diet linked to ontogeny ( I. oxyrinchus and H. griseus ) and spatial distribution ( C. carcharias ) characterizing feeding behaviour in these species at individual and population level. These outcomes agree with the results of traditional stomach analyses supporting that nontraditional stable isotopes thus represent new perspectives for the study of modern and extinct shark ecology. In addition, for the first time, the Sr/Ca elemental ratios measured in H. griseus reflect sexual differences that could be interpreted in terms of spatial segregation or physiological heterogeneities.

Disentangling the Influence of Phylogeny and Traits on Climatic Risk of European Butterflies - Andros T. Gianuca; Oliver Schweiger; Luis Mauricio Bini; Martin Wiemers; Victor Rocha di Cavalcanti; José Alexandre Diniz‐Filho; Michiel F. WallisDeVries; Niklaus E. Zimmermann; Josef Settele (Global Ecology and Biogeography, 2024)
Aim The relative importance of traits and phylogeny to predict species extinction risk is unclear and it depends on which traits are measured and their phylogenetic conservatism. Here, we evaluate the power of functional traits, ecological characteristics, such as range size and specialization, and phylogeny to predict climatic risks in European butterflies. Location Europe. Time Period Distribution data from 1981 to 2002 was used to project range shifts up to 2080. Major Taxa Studied In total, 268 European butterfly species ( Rhopalocera ). Methods We extracted information on climatic risk for each species from the literature. Two hypothetical conditions were assumed: full climate tracking and no climate tracking. We used variation partitioning to quantify and disentangle the effects of phylogeny, four traits (wingspan, voltinism, overwintering and egg volume) and two ecological characteristics (range size and specialization) on climatic risk. We used Random Forest as an imputation method to predict climatic risk values for additional European butterfly species that have not been previously modelled. Results Range size and degree of specialization strongly predicted climatic risk of European butterflies, but only for no climate tracking scenarios. Overall, more generalist species have larger ranges and are less vulnerable to climate change. Furthermore, we found that phylogenetic information adds strong power to explain climatic risk, especially, but not exclusively for scenarios that assume full climate tracking. Main Conclusions Considering current scenarios of habitat fragmentation in Europe, it is likely that species with smaller ranges and high degree of specialization will be unable to track their climates and thus be more at risk. However, our results imply that assisting dispersal and colonization might allow small ranged species to cope with climate change. Our analysis also indicate that phylogeny can be used as a proxy of unmeasured traits to predict climatic risk under certain circumstances.

Characterizing coastal aquifer heterogeneity from a single piezometer head chronicle - Martin Le Mesnil; Alexandre Gauvain; Frédéric Gresselin; Luc Aquilina; Jean-Raynald de Dreuzy (Journal of Hydrology, 2024)

Corrigendum to ‘A contribution to understanding ion-exchange mechanisms for lithium recovery from industrial effluents of lithium-ion battery recycling operations’ [J. Environ. Chem. Eng. 12 (2024) 112951] - Aliza Marie Salces; Norman Kelly; Gabriel Jon Streblow; Ekin Türkü Temel; Martin Rudolph; Alexandre Chagnes; Anna Vanderbruggen (Journal of Environmental Chemical Engineering, 2024)

Flooding and fire frequency promotes beta diversity in tree and non-tree species in tropical wetlands - Bruno Henrique dos Santos Ferreira; Maxwell da Rosa Oliveira; Bruno Arguelho Arrua; Vivian Ayumi Fujizawa Nacagava; Rafaela Aparecida Mariano Fernandes; Alexandre de Matos Martins Pereira; Andréia de Carvalho Santos; Ademilson Costa; Mesaque Rocha; Silvio Xavier; Rubens Aquino Ferraz; Arnildo Pott; et al. (Forest Ecology and Management, 2024)

Insights of potential trypanocidal effect of the synthetic derivative (2E)-1-(4-aminophenyl)-3-(2,4-dichlorophenyl)prop-2-en-1-one: in vitro assay, MEV analysis, quantum study, molecular docking, molecular dynamics, MPO analysis, and predictive ADMET - Márcia Machado Marinho; Matheus Nunes da Rocha; Emanuel Paula Magalhães; Lyanna Rodrigues Ribeiro; Caio Henrique Alexandre Roberto; Francisco Wagner de Queiroz Almeida-Neto; Marília Lopes Monteiro; João Victor Serra Nunes; Ramon Róseo Paula Pessoa Bezerra de Menezes; Emmanuel Silva Marinho; Pedro de Lima Neto; Alice Maria Costa Martins; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

In-situ observations of resident space objects with the CHEOPS space telescope - Nicolas Billot; Stephan Hellmich; Willy Benz; Andrea Fortier; David Ehrenreich; Christopher Broeg; Alexis Heitzmann; Anja Bekkelien; Alexis Brandeker; Yann Alibert; Roi Alonso; Tamas Bárczy; et al. (Journal of Space Safety Engineering, 2024)

Chemical constraints are the major limiting factor of root deepening in southern Brazil soils - Rodrigo Pivoto Mulazzani; Daniel Boeno; Bruna San Martin Rolim Ribeiro; Alexandre Ferigolo Alves; Alencar Junior Zanon; Paulo Ivonir Gubiani (Geoderma Regional, 2024)

Draw me an oxidoreductase reacting with quinones - Marianne Broc; Michael V. Cherrier; Alexandre Uzel; Rodrigo Arias-Cartin; Pascal Arnoux; Gaël Brasseur; Farida Seduk; Bruno Guigliarelli; Stéphane Grimaldi; Pierre Legrand; Fabien Pierrel; Guy Schoen; et al. (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Active intervals between sets and exercise of resistance exercises potentiate the magnitude of post-exercise hypotension in middle-aged hypertensive women - Filipe Santana Martins; Marcos Antônio Pereira dos Santos; Márcia Devânia Guedes Simões; Thamires Barbosa da Silva; Izabhelle Dantas Agra de Araújo; Alexandre Sérgio Silva (European Journal of Applied Physiology, 2024)

Drivers of seasonal rainfall variability over the Angolan and Namibian plateaus - Carlos A. Pereira; João P. Martins; Andreas H. Fink; Joaquim G. Pinto; Alexandre M. Ramos (International Journal of Climatology, 2024)
Southern Africa has been strongly affected by ongoing climate change in recent decades. Rainfall variability is modulated by regional patterns of moisture advection and convergence in the lower troposphere. Using reanalysis, ground and satellite‐based rainfall products and observations from 10 weather stations, we perform a synoptic and climatological analysis focussing on atmospheric circulation, moisture transport and their relationship with rainfall anomalies over the Angolan and Namibian Plateau region. Results clearly show that a stronger (weaker) Zambezi low level jet (LLJ) magnitudes are associated with above (below) normal rainfalls over the main Angolan and Namibian plateaus. With lower confidence, a stronger Limpopo LLJ may also lead to enhanced rainfall over Namibia and southeast Angola. The Zambezi LLJ moisture fluxes are moderately controlled by Mozambique Chanel Trough and Angola Low intensities, while the Limpopo LLJ intensities have very low influence from the Mozambique Chanel Trough and Angola Low, respectively. The Angola Low in its tropical phase is associated with deeper moisture convergence and stronger vertical velocities, leading to higher amounts of precipitable water within the air column, thus enhancing precipitation over the region. It is shown that the major moisture source of rainfall, which is advected to via the Zambezi LLJ, is the Indian Ocean. Meanwhile, the Atlantic Ocean plays a minor role. Given the current lack of observations and projected climate change, further research and investments are urgently needed in the region, for example, regarding the expansion of the surface data network.

Oil Spill Mitigation with a Team of Heterogeneous Autonomous Vehicles - André Dias; Ana Mucha; Tiago Santos; Alexandre Oliveira; Guilherme Amaral; Hugo Ferreira; Alfredo Martins; José Almeida; Eduardo Silva (Journal of Marine Science and Engineering, 2024)
This paper presents the implementation of an innovative solution based on heterogeneous autonomous vehicles to tackle maritime pollution (in particular, oil spills). This solution is based on native microbial consortia with bioremediation capacity, and the adaptation of air and surface autonomous vehicles for in situ release of autochthonous microorganisms (bioaugmentation) and nutrients (biostimulation). By doing so, these systems can be applied as the first line of the response to pollution incidents from several origins that may occur inside ports, around industrial and extraction facilities, or in the open sea during transport activities in a fast, efficient, and low-cost way. The paper describes the work done in the development of a team of autonomous vehicles able to carry as payload, native organisms to naturally degrade oil spills (avoiding the introduction of additional chemical or biological additives), and the development of a multi-robot framework for efficient oil spill mitigation. Field tests have been performed in Portugal and Spain’s harbors, with a simulated oil spill, and the coordinate oil spill task between the autonomous surface vehicle (ASV) ROAZ and the unmanned aerial vehicle (UAV) STORK has been validated.

Dynamics of dissolved inorganic carbon (DIC) and stable C isotope ratios (δ13CDIC) in a tropical watershed with diversified land use in São Paulo State, Brazil - Fabiano Tomazini da Conceição; Alexandre Martins Fernandes; Rodrigo Braga Moruzzi; Jefferson Mortatti (Science of The Total Environment, 2024)

Microscale hydrogen, carbon, and nitrogen isotopic diversity of organic matter in asteroid Ryugu - Larry R Nittler; Jens Barosch; Katherine Burgess; Rhonda M Stroud; Jianhua Wang; Hikaru Yabuta; Yuma Enokido; Megumi Matsumoto; Tomoki Nakamura; Yoko Kebukawa; Shohei Yamashita; Yoshio Takahashi; et al. (Earth and Planetary Science Letters, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Dereplication of polar extracts from Croton antisyphiliticus Mart. roots and its anti-inflammatory and antinociceptive potential - Jorge Luiz Souza Simão; Stephanie Vilela Prado; Alana Kelyene Pereira; Gerso Pereira Alexandre; Núbia Alves Mariano Teixeira Pires Gomide; Marcia Matos da Silva; Dionys de Souza Almeida; Aline Nazareth Martins; Daiany Priscilla Bueno da Silva; Elson Alves da Costa; Vanessa Gisele Pasqualotto Severino (Natural Product Research, 2024)

Speleothems in subglacial caves: An emerging archive of glacial climate history and mountain glacier dynamics - Christoph Spötl; Jonathan L. Baker; Vanessa Skiba; Alexandre Honiat; Jens Fohlmeister; Marc Luetscher; Martin Trüssel (Quaternary Science Reviews, 2024)

Advancing air quality monitoring: A low-cost sensor network in motion – Part I - Carolina Correia; Pedro Santana; Vânia Martins; Pedro Mariano; Alexandre Almeida; Susana Marta Almeida (Journal of Environmental Management, 2024)

A contribution to understanding ion-exchange mechanisms for lithium recovery from industrial effluents of lithium-ion battery recycling operations - Aliza Marie Salces; Norman Kelly; Gabriel Jon Streblow; Ekin Türkü Temel; Martin Rudolph; Alexandre Chagnes; Anna Vanderbruggen (Journal of Environmental Chemical Engineering, 2024)

Solar thermo-photocatalytic methanation using a bifunctional RuO2:TiO2/Z13X photocatalyst/adsorbent material for efficient CO2 capture and conversion - Larissa O. Paulista; Alexandre F.P. Ferreira; Alírio E. Rodrigues; Ramiro J.E. Martins; Rui A.R. Boaventura; Vítor J.P. Vilar; Tânia F.C.V. Silva (Journal of Environmental Chemical Engineering, 2024)

Texture prediction of natural soils in the Brazilian Amazon through proximal sensors - Quésia Sá Pavão; Paula Godinho Ribeiro; Gutierre Pereira Maciel; Sérgio Henrique Godinho Silva; Suzana Romeiro Araújo; Antonio Rodrigues Fernandes; José Alexandre Melo Demattê; Pedro Walfir Martins e Souza Filho; Silvio Junio Ramos (Geoderma Regional, 2024)

Cytogenotoxicity and inflammatory response in liver of rats exposed to different doses of cannabis nano emulsions - Thiago Guedes Pinto; Barbara dos Anjos Rosario; Andrea Cristina de Moraes Malinverni; Rosana Xavier; Yasmin Alaby Martins Ferreira; Luciana Pellegrini Pisani; Pedro Everson Alexandre de Aquino; Glauce Socorro de Barros Viana; Daniel Vitor de Souza; Milena de Barros Viana; Daniel Araki Ribeiro (Archives of Toxicology, 2024)

Trends in airborne grass pollen in Évora City (Portugal) - Elsa Rute Guerra Caeiro; Roberto Alexandre Pisa Camacho; Manuel Branco Ferreira; Pedro Carreiro-Martins; Irene Gomes Câmara Camacho (Aerobiologia, 2024)
Aerobiology could be used as complementary data or proxy for studying phenology, especially in species which usually are not long-distance transported, such as grasses. This 21-year aerobiological study took place in Évora (South Portugal), using a seven-day recording volumetric pollen trap with the aim of analysing the temporal trends of grass pollen seasons. To this end, data were statistically tested for correlation and regression to determine the features and temporal trends of pollen seasons. Main results show that Poaceae pollen has a high representation in pollen spectrum, 20% (min: 7%; max: 44%), with a long season starting in March and lasting till August/September or October. There was an overall, but not statistically significant trend, towards an increase in the annual pollen integral and peak values, and also an overall non-statistically significant trend towards an earlier start and later end of the pollen season. Main and high pollen seasons have been lasting longer, and the days with allergenic potential have been rising in line with the local temperature rising trend. It seems that grass pollen production is being aided by warmer temperatures and increased grassland areas in Alentejo region. This could promote the increase in annual pollen levels and in the number of high pollen days over the years. In clinical terms, it means that grass allergic patients are exposed to longer periods of airborne pollen and to higher counts over a longer time. The climate conditions projected for Alentejo region, including rising temperature, and the changes in local grassland areas may help to clarify the trends of grass pollen seasons in the next decades.

Changes, trends, and gaps in research dynamics after the megafires in the Pantanal - Alexandre de Matos Martins Pereira; Maxwell da Rosa Oliveira; Francielli Bao; Evaldo Benedito de Souza; Arnildo Pott; Anahi Cerzosimo de Souza Escobar; Suelen Sandin de Carvalho; Geraldo Alves Damasceno-Júnior (Environment, Development and Sustainability, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Acaricidal activity of synthetic spilanthol derivative against ticks of medical and veterinary importance - Luis Adriano Anholeto; Guilherme Andrade Brancaglion; Danilo Martins dos Santos; Rafaela Tami Ikeda Kapritchkoff; Karina Neoob de Carvalho Castro; Kirley Marques Canuto; Rodney Alexandre Ferreira Rodrigues; Daniel Souza Correa; Ana Carolina de Souza Chagas; Julio Cezar Pastre (Veterinary Parasitology, 2024)

Artificial neural network modeling of the stability behavior of stainless steel I-beams with sinusoidal web openings - Adriano Silva de Carvalho; Alexandre Rossi; Marcela Moreira da Rocha Almeida; Yasin Onuralp Özkılıç; Carlos Humberto Martins (Engineering Structures, 2024)

Combining X-ray micro-CT and microscopy-based images of two lianas species to derive structural, mechanical and functional relationships - Claudine Karlen; Pascal Turberg; Alexandre Buttler; Océane Martin; Fritz Schweingruber; Anastasios P. Vassilopoulos (Plant Systematics and Evolution, 2024)
This paper presents a biomechanical study of stems of two liana species, Clematis vitalba and Vitis vinifera , investigates the mechanical performance of these two liana species and attempts to enhance the understanding of structure–function relationships. The investigation involved mechanical testing of whole plant stems, supplemented by X-ray micro-CT (X-ray computed tomography at micron voxel size) imaging and 2D microscopic images of stained cross sections of the plant stems, to derive structure–function relationships with potential for application in bioinspired composite materials. The micro-CT images were compared to the microscopic images of stained cross sections, in order to show benefits and potential drawbacks of the X-ray micro-CT method with respect to traditional methods. The high-resolution 3D imaging capacity of micro-CT is exploited to explain the structural functionality derived from the mechanical testing. A simple finite element model is developed based on the plant topology derived by the micro-CT images and proved accurate enough to model the plant’s mechanical behaviour and assess the influence of their structural differences. The two plants exhibit different to each other physical and mechanical properties (density, strength and stiffness) due to their common growth form. Anatomical cross-sectional observation and X-ray micro-CT provide complementary information. The first method allows the identification of the lignified parts, supposedly more resistant mechanically, of these structures, while the second one provides a full 3D model of the structure, admittedly less detailed but providing the spatial distribution of density contrasts supposed to be important in the mechanical properties of the plant. The proposed methodological approach opens new perspectives to better understand the mechanical behaviour of the complex structure of plants and to draw inspiration from it in structural engineering.

Drought resistance of major tree species in the Czech Republic - Yumei Jiang; William Marchand; Miloš Rydval; Radim Matula; Pavel Janda; Krešimir Begović; Dominik Thom; Alexandre Fruleux; Arne Buechling; Jakob Pavlin; Juliana Nogueira; Martin Dušátko; et al. (Agricultural and Forest Meteorology, 2024)

Vitamin C combined with oregano essential oil, Origanum vulgare, reduced oxidative damage in Astyanax aff. bimaculatus exposed to air - Maria Tatiana Soares Martins; Suellen Silva Condessa; Alex Júnio da Silva Cardoso; Jerusa Maria de Oliveira; Jheneze Guimarães Pereira Rocha; Juliana Rodrigues Gomes; Pollyanna de Moraes França Ferreira; Wanderson Valente; Mariella Bontempo Freitas; Jener Alexandre Sampaio Zuanon (Aquaculture International, 2024)

Photo‐identification and satellite telemetry connect southern right whales from South Georgia Island (Islas Georgias del Sur) with multiple feeding and calving grounds in the southwest Atlantic - Amy S. Kennedy; Emma L. Carroll; Alexandre N. Zerbini; C. Scott Baker; Manuela Bassoi; Nazarena A. Beretta; Danielle L. Buss; Susannah Calderan; Ted Cheeseman; Martin A. Collins; Paula Costa‐Urrutia; Paul Ensor; et al. (Marine Mammal Science, 2024)
The sub‐Antarctic waters of South Georgia Island (Islas Georgias del Sur, SG/IG) are a regularly visited feeding ground for southern right whales ( Eubalaena australis , SRW) in the southwest Atlantic. Satellite telemetry and photo‐identification records were compared to better understand the role of SG/IG in the SRW migratory network. We present the first insights from SRW satellite‐tracked from the SG/IG feeding ground, habitat use patterns in the Scotia Arc, and movements to Antarctic habitats. Photo‐identification comparisons to calving and feeding areas across the South Atlantic and a review of sightings of cetaceans reported from Bird Island (west of SG/IG) since 1979 illuminate long‐term habitat use patterns in SG/IG. We present the first recorded migratory movement between SG/IG and multiple countries: Argentina, Uruguay, and Brazil. Photo‐identification (1) linked SG/IG to a female SRW with a long‐term sighting history in Brazil, and (2) provided the first match between SG/IG and the western Antarctic Peninsula, suggesting the latter could extend the feeding area for southwest Atlantic SRW. Satellite tracking and opportunistic sightings suggest that shelf and coastal waters west of SG/IG represent an important multi‐season SRW feeding habitat and add to our overall understanding of habitats and ranges occupied by recovering southwest Atlantic SRW.

Sizeable net export of base cations from a Carpathian flysch catchment indicates their geogenic origin while the 26Mg/24Mg, 44Ca/40Ca and 87Sr/86Sr isotope ratios in runoff are indistinguishable from atmospheric input - Martin Novak; Yulia V. Erban Kochergina; Alexandre V. Andronikov; Chris Holmden; Frantisek Veselovsky; Vaclav Kachlik; Jakub Hruška; Frantisek Laufek; Tomas Paces; Arnost Komarek; Ondrej Sebek; Marketa Stepanova; et al. (Environmental Science and Pollution Research, 2024)
Nutrient imbalances may negatively affect the health status of forests exposed to multiple stress factors, including drought and bark beetle calamities. We studied the origin of base cations in runoff from a small Carpathian catchment underlain by base-poor flysch turbidites using magnesium (Mg), calcium (Ca) and strontium (Sr) isotope composition of 10 ecosystem compartments. Our objective was to constrain conclusions drawn from long-term hydrochemical monitoring of inputs and outputs. Annual export of Mg, Ca and Sr exceeds 5-to-15 times their atmospheric input. Mass budgets per se thus indicate sizeable net leaching of Mg, Ca and Sr from bedrock sandstones and claystones. Surprisingly, δ 26 Mg, δ 44 Ca and 87 Sr/ 86 Sr isotope ratios of runoff were practically identical to those of atmospheric deposition and soil water but significantly different from bedrock isotope ratios. We did not find any carbonates in the studied area as a hypothetical, easily dissolvable source of base cations whose isotope composition might corroborate the predominance of geogenic base cations in the runoff. Marine carbonates typically have lower δ 26 Mg and 87 Sr/ 86 Sr ratios, and silicate sediments often have higher δ 26 Mg and 87 Sr/ 86 Sr ratios than runoff at the study site. Mixing of these two sources, if confirmed, could reconcile the flux and isotope data.

Effectiveness and safety of clove oil and common salt in the long-term transport of Cyprinus carpio - Karina Ventura Boechat Martins; Stella Bicalho Silva; Alex Júnio da Silva Cardoso; Ana Lúcia Salaro; Pollyanna de Moraes França Ferreira; Mariella Bontempo Freitas; Jener Alexandre Sampaio Zuanon (Aquaculture, 2024)

Microcystin influence on soil-plant microbiota: Unraveling microbiota modulations and assembly processes in the rhizosphere of Vicia faba - El Mahdi Redouane; Andrés Núñez; Wafa Achouak; Mohamed Barakat; Anoop Alex; José Carlos Martins; Zakaria Tazart; Richard Mugani; Soukaina El Amrani Zerrifi; Mohammed Haida; Ana M. García; Alexandre Campos; et al. (Science of The Total Environment, 2024)

Hy-TeC: a hybrid vision transformer model for high-resolution and large-scale mapping of canopy height - Ibrahim Fayad; Philippe Ciais; Martin Schwartz; Jean-Pierre Wigneron; Nicolas Baghdadi; Aurélien de Truchis; Alexandre d'Aspremont; Frederic Frappart; Sassan Saatchi; Ewan Sean; Agnes Pellissier-Tanon; Hassan Bazzi (Remote Sensing of Environment, 2024)

Demography of endangered juvenile green turtles in face of environmental changes: 10 years of capture-mark-recapture efforts in Martinique - Pierre Lelong; Aurélien Besnard; Marc Girondot; Caroline Habold; Fabienne Priam; Mathieu Giraudeau; Guillaume Le Loc'h; Aurélie Le Loc'h; Pascal Fournier; Christine Fournier-Chambrillon; Paco Bustamante; Sophie M. Dupont; et al. (Biological Conservation, 2024)

Isolation and primary culture of human abdominal aorta smooth muscle cells from brain-dead donors: an experimental model for vascular diseases - Carlos Alexandre Curylofo Corsi; Claudia Tarcila Gomes Sares; Fabiola Mestriner; Jéssyca Michelon-Barbosa; Vinicius Flora Dugaich; Timna Varela Martins; Alex Martins Násare; Roberta Ribeiro Costa Rosales; Maria Cecília Jordani; José Carlos Alves-Filho; Rodolfo Borges dos Reis; Mauricio Serra Ribeiro; et al. (Cell and Tissue Banking, 2024)

Concentrations, sources and risks of polycyclic aromatic hydrocarbons in sediments from the Parnaiba Delta basin, Northeast Brazil - Analine D.C. Andrade; Gabrielle M. Fernandes; Davi A. Martins; Rivelino M. Cavalcante; Michel R.B. Chaves; Alexandre A. de Souza; Jeremias P. da S. Filho; Ronaldo F. Nascimento; Sidney G. de Lima (Chemosphere, 2024)

The interplay between Azospirillum brasilense and the native bacterial communities in the soil and rhizosphere of maize (Zea mays L.) - Alexandre Pedrinho; Lucas William Mendes; Felipe Martins do Rêgo Barros; João William Bossolani; Tayná Negri Kühn; Maria Carolina Quecine; Fernando Dini Andreote (Soil Biology and Biochemistry, 2024)

Application of Vegetative Indices for Leaf Nitrogen Estimation in Sugarcane Using Hyperspectral Data - Juliano Araújo Martins; Peterson Ricardo Fiorio; Carlos Augusto Alves Cardoso Silva; José Alexandre Melo Demattê; Pedro Paulo da Silva Barros (Sugar Tech, 2024)

Global patterns and environmental drivers of forest functional composition - Elise Bouchard; Eric B. Searle; Pierre Drapeau; Jingjing Liang; Javier G. P. Gamarra; Meinrad Abegg; Giorgio Alberti; Angelica Almeyda Zambrano; Esteban Alvarez‐Davila; Luciana F. Alves; Valerio Avitabile; Gerardo Aymard; et al. (Global Ecology and Biogeography, 2024)
Aim To determine the relationships between the functional trait composition of forest communities and environmental gradients across scales and biomes and the role of species relative abundances in these relationships. Location Global. Time period Recent. Major taxa studied Trees. Methods We integrated species abundance records from worldwide forest inventories and associated functional traits (wood density, specific leaf area and seed mass) to obtain a data set of 99,953 to 149,285 plots (depending on the trait) spanning all forested continents. We computed community‐weighted and unweighted means of trait values for each plot and related them to three broad environmental gradients and their interactions (energy availability, precipitation and soil properties) at two scales (global and biomes). Results Our models explained up to 60% of the variance in trait distribution. At global scale, the energy gradient had the strongest influence on traits. However, within‐biome models revealed different relationships among biomes. Notably, the functional composition of tropical forests was more influenced by precipitation and soil properties than energy availability, whereas temperate forests showed the opposite pattern. Depending on the trait studied, response to gradients was more variable and proportionally weaker in boreal forests. Community unweighted means were better predicted than weighted means for almost all models. Main conclusions Worldwide, trees require a large amount of energy (following latitude) to produce dense wood and seeds, while leaves with large surface to weight ratios are concentrated in temperate forests. However, patterns of functional composition within‐biome differ from global patterns due to biome specificities such as the presence of conifers or unique combinations of climatic and soil properties. We recommend assessing the sensitivity of tree functional traits to environmental changes in their geographic context. Furthermore, at a given site, the distribution of tree functional traits appears to be driven more by species presence than species abundance.

The exometabolome of microbial communities inhabiting bare ice surfaces on the southern Greenland Ice Sheet - Eva L. Doting; Marie B. Jensen; Elisa K. Peter; Lea Ellegaard‐Jensen; Martyn Tranter; Liane G. Benning; Martin Hansen; Alexandre M. Anesio (Environmental Microbiology, 2024)
Microbial blooms colonize the Greenland Ice Sheet bare ice surface during the ablation season and significantly reduce its albedo. On the ice surface, microbes are exposed to high levels of irradiance, freeze–thaw cycles, and low nutrient concentrations. It is well known that microorganisms secrete metabolites to maintain homeostasis, communicate with other microorganisms, and defend themselves. Yet, the exometabolome of supraglacial microbial blooms, dominated by the pigmented glacier ice algae Ancylonema alaskanum and Ancylonema nordenskiöldii , remains thus far unstudied. Here, we use a high‐resolution mass spectrometry‐based untargeted metabolomics workflow to identify metabolites in the exometabolome of microbial blooms on the surface of the southern tip of the Greenland Ice Sheet. Samples were collected every 6 h across two diurnal cycles at 5 replicate sampling sites with high similarity in community composition, in terms of orders and phyla present. Time of sampling explained 46% (permutational multivariate analysis of variance [PERMANOVA], pseudo‐ F = 3.7771, p = 0.001) and 27% (PERMANOVA, pseudo‐ F = 1.8705, p = 0.001) of variance in the exometabolome across the two diurnal cycles. Annotated metabolites included riboflavin, lumichrome, tryptophan, and azelaic acid, all of which have demonstrated roles in microbe–microbe interactions in other ecosystems and should be tested for potential roles in the development of microbial blooms on bare ice surfaces.

Metabolomic profiling and correlations of supercritical extracts of guarana - Leila Larisa Medeiros Marques; Fabianne Martins Ribeiro; Celso Vataru Nakamura; Ane Stefano Simionato; Galdino Andrade; Acácio Antonio Ferreira Zielinski; Carlos Alexandre Carollo; Denise Brentan da Silva; Admilton Gonçalves de Oliveira; João Carlos Palazzo de Mello (Natural Product Research, 2024)

Trace metal biomonitoring in the farming of tambaqui (Colossoma macropomum), an Amazonian neotropical fish - Edson Luniere Porto; Matheus Gomes da Cruz; Marcos Alexandre Bolson; Ézio Sargetini Junior; Maurício Laterça Martins; Gabriela Tomas Jerônimo (Environmental Science and Pollution Research, 2024)

Exploring the neuroprotective potential of antimicrobial peptides from Dinoponera quadriceps venom against pentylenetetrazole-induced seizures in vivo - Livia Correia Fernandes Paes; Dânya Bandeira Lima; Daniel Moreira Alves da Silva; José Tiago Valentin; Pedro Everson Alexandre de Aquino; Alicia Belén García-Jareño; Mar Orzaéz; Marta Maria de França Fonteles; Alice Maria Costa Martins (Toxicon, 2024)

Effects of cold stress on physiologic metabolism in the initial phase and performance of broiler rearing - Ludmyla Martins Moreira; Lorena Salim Sousa; César Andrés Guato Guamán; Mariana Cristina Vieira; Matheus Barros Santini; Alexandre Rodrigues Cardoso; Fabíola de Oliveira Paes Leme; Leonardo José Camargos Lara; Itallo Conrado Sousa Araújo (Journal of Thermal Biology, 2024)

The thermal history of Ryugu based on Raman characterization of Hayabusa2 samples - Lydie Bonal; Eric Quirico; Gilles Montagnac; Mutsumi Komatsu; Yoko Kebukawa; Hikaru Yabuta; Kana Amano; Jens Barosch; Laure Bejach; George D. Cody; Emmanuel Dartois; Alexandre Dazzi; et al. (Icarus, 2024)

Attention-deficit/hyperactivity disorder and inflammation: natural product-derived treatments—a review of the last ten years - Alexandre Martins; Magali Conte; Márcia Inês Goettert; Verônica Contini (Inflammopharmacology, 2023)

Energetic responses of head-out water immersion at different temperatures during post-exercise recovery and its consequence on anaerobic mechanical power - Marcelo Coertjens; Patricia Chaves Coertjens; Marcus Peikriszwili Tartaruga; Tatiane Gorski; Adriano Eduardo Lima-Silva; Lorival José Carminatti; Paulo Otto Beyer; Ana Paula Viola de Almeida; Jeam Marcel Geremia; Leonardo Alexandre Peyré-Tartaruga; Luiz Fernando Martins Kruel (European Journal of Applied Physiology, 2023)

Temperate Primary Forest Biomass Accumulates over Centuries-Long Time Frames - Dheeraj Ralhan; Heather Keith; Jakob Pavlin; Annemiek Irene Stegehuis; William Marchand; Alexandre Fruleux; Miroslav Poláček; Marek Svitok; Thomas A. Nagel; Martin Mikoláš; Daniel Kozák; Arne Buechling; et al. (Ecosystems, 2023)

Pleural Empyema in Six Horses: A Retrospective Case Series - Lorena Battistin; Fabrício Moreira Cerri; Marcos Jun Watanabe; Regina Kiomi Takahira; Márcio Garcia Ribeiro; Noeme Sousa Rocha; José Paes de Oliveira-Filho; Alexandre Secorun Borges; Rogério Martins Amorim (Journal of Equine Veterinary Science, 2023)

Methodological insights from unmanned system technologies in a rock quarry environment and geomining heritage site: coupling LiDAR-based mapping and GIS geovisualisation techniques - Ana Pires; André Dias; Pedro Silva; António Ferreira; Paulo Rodrigues; Tiago Santos; Alexandre Oliveira; Liliana Freitas; Alfredo Martins; José Almeida; Eduardo Silva; Helder I. Chaminé (Arabian Journal of Geosciences, 2023)

Effects of Acid and Organosolv Pretreatments on the Analytical Fast Pyrolysis Products of Green Coconut Fiber - Carlos Eduardo de Araújo Padilha; Luiz Eduardo Pereira Santiago; Alexandre de Araújo Guilherme; José Demétrio Nery Cavalcante; Habila Yusuf Thomas; Everaldo Silvino dos Santos; Dulce Maria de Araújo Melo; Renata Martins Braga; Domingos Fabiano de Santana Souza (BioEnergy Research, 2023)

Bioaccumulation and speciation of arsenic in plankton from tropical soda lakes along a salinity gradient - José Lucas Martins Viana; Débora Aparecida Steffler; Amauris Hechavarría Hernández; Juliana dos Santos Costa; Thierry Alexandre Pellegrinetti; Erick Christian Rodrigues de Jesus; Marianna Cancian; Marli Fátima Fiore; Ary T. Rezende-Filho; Alessandra Sussulini; Laurent Barbiero; Amauri Antonio Menegario; et al. (Science of The Total Environment, 2023)

Behavioural compensation of extruded urea level and the effects of supplementation presencefor finished lambs in tropical grass pastures - Francisca Fernanda da Silva Roberto; Gelson dos Santos Difante; Roberto Germano Costa; Luís Carlos Vinhas Ítavo; Camila Celeste Brandão Ferreira Ítavo; Marina de Nadai Bonin Gomes; Alexandre Menezes Dias; Jéssica Gomes Rodrigues; Marislayne de Gusmão Pereira; Neila Lidiany Ribeiro; Antonio Leandro Chaves Gurgel; Gabriela Oliveira de Aquino Monteiro; et al. (Small Ruminant Research, 2023)

Campomanesia guazumifolia infusion decreases human platelet aggregation by reducing cyclooxygenase 1 activity and its underlying mechanisms - Caroline Honaiser Lescano; Fernando Freitas de Lima; Taline Baganha Stefanello Catelan; Victor Hugo Dantas Guimarães; Ulisses Alves Pereira; Charles Martins Aguilar; Cláudia Andrea Lima Cardoso; Sérgio Henrique Sousa Santos; Alexandre Borges; Ivan Pires de Oliveira (Food Bioscience, 2023)

Flexural and shear behavior of steel-UHPC composite beams: a review - Carlos Alberto Benedetty; Vinicius Brother dos Santos; Pablo Augusto Krahl; Alexandre Rossi; Flávio de Andrade Silva; Daniel Carlos Taissum Cardoso; Carlos Humberto Martins (Engineering Structures, 2023)

Core–shell clustering approach for detection and analysis of coastal upwelling - Susana Nascimento; Alexandre Martins; Paulo Relvas; Joaquim F. Luís; Boris Mirkin (Computers & Geosciences, 2023)

Cryptococcal meningitis and cerebral vasculitis in a patient with primary intestinal lymphangiectasia: a case report - Martin Mathurin; Sandra Devatine; Aude Kopp-Derouet; Antoine Guillonnet; Alexandre Alanio; Nelson Lourenco; Victoria Manda; Véronique Delcey; Jean-Michel Molina; Pierre Sellier (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Plant-parasitic nematode community and enzyme activities in soils under no-till soybean crops in Brazil - Felipe Martins do Rêgo Barros; Alexandre Pedrinho; Gustavo da Cunha Sant’Ana; Caio César Gomes Freitas; Juliana Magrinelli Osório Rosa; Claudio Marcelo Gonçalves de Oliveira; Caique Rozada; Felipe Nogueira de Sá Marto; João Augusto Lopes Pascoalino; Luiz Antônio da Silva; Fernando Dini Andreote (Rhizosphere, 2023)

Li-rich pegmatites and related peraluminous granites of the Fregeneda-Almendra field (Spain-Portugal): A case study of magmatic signature for Li enrichment - Encarnación Roda-Robles; Romeu Vieira; Alexandre Lima; Jon Errandonea-Martin; Alfonso Pesquera; Joana Cardoso-Fernandes; Idoia Garate-Olave (Lithos, 2023)

In search of the Rheic suture: detrital zircon geochronology of Neoproterozoic to Lower Paleozoic metasedimentary units in the Balkan fold-and-thrust belt in Bulgaria - Jiří Žák; Martin Svojtka; Ianko Gerdjikov; Dian A. Vangelov; Alexandre Kounov; Jiří Sláma; Václav Kachlík (Gondwana Research, 2023)

COVID-19 and candiduria: an investigation of the risk factors and immunological aspects - Junya L. Singulani; Danielle L. Silva; Caroline M. Lima; Vanessa C. R. Magalhães; Ludmila M. Baltazar; Alexandre S. Moura; Ana Raquel O. Santos; Tatiani Fereguetti; Juliana C. Martins; Lívia F. Rabelo; Ana C. Lyon; Olindo A. Martins-Filho; et al. (Brazilian Journal of Microbiology, 2023)

How does the subtropical landscape configuration influence the ecomorphological traits and community composition of ground-dwelling beetles in southern Brazil? - Pâmela Niederauer Pompeo; Luís Carlos Iuñes Oliveira Filho; Douglas Alexandre; Ana Carolina Lovatel; Pedro Martins da Silva; José Paulo Sousa; Osmar Klauberg-Filho; Dilmar Baretta (Applied Soil Ecology, 2023)

Redox status of juvenile Nile tilapia, Oreochromis niloticus (Linnaeus, 1758), fed diets supplemented with poultry liver protein hydrolysate as feed aditive - Juliana Rodrigues Gomes; Alex Júnio da Silva Cardoso; Hamilton Hisano; Renata Maria Pereira de Freitas; Karina Ventura Boechat Martins; Filipe Silveira Azevedo; Mariella Bontempo Freitas; Pollyanna de Moraes França Ferreira; Ana Lúcia Salaro; Jener Alexandre Sampaio Zuanon (Animal Feed Science and Technology, 2023)

Larvicidal potential of extracts and isolated compounds from Piper cubeba fruits against Aedes aegypti (Diptera: Culicidae) larvae - Ana Carolina Gomes; Alexandre Borges; Daniela Garcia Zoca; Marcio Luís Andrade e Silva; Aline Rafaela da Silva Rodrigues Machado; Alex Martins Machado; Mario F. C. Santos; Rosangela da Silva de Laurentiz (Natural Product Research, 2023)

Protein profiles identified by LC-MS/MS demonstrate change in beta oxidation, ketogenesis, and propionate metabolism in rumen epithelium with different additives - Leone Campos Rocha; Andrey Sávio de Almeida Assunção; Renata Aparecida Martins; Victor Valério de Carvalho; Alexandre Perdigão; Marília Afonso Rabelo Buzalaf; Jiri Adamec; Camila Pereira Braga; Danilo Domingues Millen; José Cavalcante Souza Vieira; Pedro de Magalhães Padilha (Livestock Science, 2023)

Interannual modulation of the East and South Asian summer precipitation δ18O by the Indian and western North Pacific summer monsoon strength - Yuanyuan Li; Xiaodong Liu; Xiaoxun Xie; Alexandre Cauquoin; Martin Werner (Global and Planetary Change, 2023)

Restoration of riparian ecosystems posterior to tin mining in the Central Amazon: Restoration indicators and selection of suitable species for planting - Rodrigo de Souza Barbosa; Julia Isabella de Matos Rodrigues; Victor Pereira de Oliveira; Walmer Bruno Rocha Martins; Carlos Alexandre Costa Coelho; Wyler Frank Siqueira do Carmo; Nonato Junior Ribeiro dos Santos; Wagner Varanda de Sousa; Eliezer Augusto Litaiff de São Paulo Aguiar (Ecological Engineering, 2023)

[8] and [10]-Gingerol reduces urothelial damage in ifosfamide-induced hemorrhagic cystitis via JAK/STAT/FOXO signaling pathway via IL-10 - Francisco C. S. Ferreira; Marco Clementino; Francisco A. P. Rodrigues; Herlice N. Veras; Dainesy S. Martins; Marcus L. Queiroga; Mikael A. Lima; Dayara O. Silva; Thiago M. de Freitas; Samilly A. Ribeiro; Mario R. L. Mota; James A. da Silva; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Deontic signs increase control monitoring: evidence from a modified traffic flanker task - Teresa Garcia-Marques; Pedro Figueira; Alexandre Fernandes; João Martins (Cognitive Processing, 2023)
Deontic norms are expected to impose individuals’ control over their behavior. In this paper, we address such norms presented in traffic signs and test their influence over executive control functions. For Experiment 1, we develop a traffic flanker task in which the typical neutral arrows are replaced with traffic prohibition/obligation signs. Experiment 2 isolated the deontic aspect of the signs using simple arrows on red, blue, and green backgrounds and either primed them to be interpreted as traffic signs or as elements of a gaming console controller. Results in both studies show evidence of controlling context interferences more efficiently when dealing with deontic (traffic) signs than with simple arrows (Experiment 1) or with similar perceptive targets when primed with a deontic context than with a gaming context (Experiment 2). In both studies, obligation/blue signs mitigate flanker effects less than prohibition/red signs. Stimuli color affects the alertness of the cognitive system, with the color red being, by itself, a cue for increased control. Based on temporal analysis, we further discuss these results as evidence of an increase in proactive control that aims to prevent the occurrence of undesirable influence.

Biological and pharmacological aspects of tannins and potential biotechnological applications - Luciana Fentanes Moura de Melo; Verônica Giuliani de Queiroz Aquino-Martins; Ariana Pereira da Silva; Hugo Alexandre Oliveira Rocha; Katia Castanho Scortecci (Food Chemistry, 2023)

Spatial and temporal trends in δ66Zn and 206Pb/207Pb isotope ratios along a rural transect downwind from the Upper Silesian industrial area: Role of legacy vs. present-day pollution - Eva Prechova; Ondrej Sebek; Martin Novak; Alexandre V. Andronikov; Ladislav Strnad; Vladislav Chrastny; Jerzy Cabala; Marketa Stepanova; Jan Pasava; Eva Martinkova; Petra Pacherova; Vladimir Blaha; et al. (Environmental Pollution, 2023)

Temporo-basal sulcal connections: a manual annotation protocol and an investigation of sexual dimorphism and heritability - Kevin de Matos; Claire Cury; Lydia Chougar; Lachlan T. Strike; Thibault Rolland; Maximilien Riche; Lisa Hemforth; Alexandre Martin; Tobias Banaschewski; Arun L. W. Bokde; Sylvane Desrivières; Herta Flor; et al. (Brain Structure and Function, 2023)

Natural history and morphology of immature stages of Tolype medialis (Jones, 1912) (Lepidoptera: Lasiocampidae: Macromphaliinae) - Mônica Piovesan; Fábio Luis dos Santos; Elton Orlandin; Alexandre Specht; Olaf Hermann Hendrik Mielke; Mirna Martins Casagrande (Neotropical Entomology, 2023)

Health risk assessment of lake water contaminated with microcystins for fruit crop irrigation and farm animal drinking - El Mahdi Redouane; Zakaria Tazart; Majida Lahrouni; Richard Mugani; Sara Elgadi; Hamza Zine; Soukaina El Amrani Zerrifi; Mohammed Haida; José Carlos Martins; Alexandre Campos; Khalid Oufdou; Vitor Vasconcelos; et al. (Environmental Science and Pollution Research, 2023)
The health risks linked to the consumption of microcystin-accumulating crops have been increasing worldwide in toxic cyanobloom-occurring regions. The bioaccumulation of microcystins (MCs) in agricultural produce at environmentally realistic concentrations is poorly investigated. In this field study, we assessed the health risks of MCs in raw water used for irrigating fruit crops (bioaccumulation) and watering farm animals in the Lalla Takerkoust agricultural region (Marrakesh, Morocco). Thus, MCs were extracted from water and fruit samples and quantified by enzyme-linked immunosorbent assay in order to calculate the health risk indicators. MCs posed a high health-risk level to poultry and horses, with estimated daily intakes (EDI) being 14- and 19-fold higher than the recommended limits (3.1 and 2.3 μg MC-LR L −1 ), respectively. Furthermore, pomegranate posed the same level of risk, with EDI being 22- and 53-fold higher than the limit dose (0.04 μg MC-LR kg −1 ) for adults and children, respectively. There was an urgent need for guidelines regarding water use and management in MC-polluted areas, besides the setup of nature-based tools for toxin removal from raw water used in farming practices. Moreover, MCs could contaminate the human food chain, which implies further investigations of their potential accumulation in livestock- and poultry-based food.

Phylogenomics reconciles molecular data with the rich fossil record on the origin of living turtles - Alexandre Pedro Selvatti; Filipe Romero Rebello Moreira; Daniel Cardoso Carvalho; Francisco Prosdocimi; Claudia Augusta de Moraes Russo; Ana Carolina Martins Junqueira (Molecular Phylogenetics and Evolution, 2023)

Effect of sires’ expected progeny difference for scrotal circumference and juvenile ADG on the puberty of crossbred beef heifers - José Paulo Roman Barroso; Marcos Vinicius de Castro Ferraz Junior; Gabriela Bagio Oliveira; Alexandre Arantes Miszura; Analisa Vasques Bertoloni; André Storti Martins; Marcelo Baggio; Daniel Montanher Polizel; Janaina Socolovski Biava; Evandro Maia Ferreira; Alexandre Vaz Pires (Tropical Animal Health and Production, 2023)

Addressing chemical pollution in biodiversity research - Gabriel Sigmund; Marlene Ågerstrand; Alexandre Antonelli; Thomas Backhaus; Tomas Brodin; Miriam L. Diamond; Walter R. Erdelen; David C. Evers; Thilo Hofmann; Thorsten Hueffer; Adelene Lai; Joao P. M. Torres; et al. (Global Change Biology, 2023)
Climate change, biodiversity loss, and chemical pollution are planetary‐scale emergencies requiring urgent mitigation actions. As these “triple crises” are deeply interlinked, they need to be tackled in an integrative manner. However, while climate change and biodiversity are often studied together, chemical pollution as a global change factor contributing to worldwide biodiversity loss has received much less attention in biodiversity research so far. Here, we review evidence showing that the multifaceted effects of anthropogenic chemicals in the environment are posing a growing threat to biodiversity and ecosystems. Therefore, failure to account for pollution effects may significantly undermine the success of biodiversity protection efforts. We argue that progress in understanding and counteracting the negative impact of chemical pollution on biodiversity requires collective efforts of scientists from different disciplines, including but not limited to ecology, ecotoxicology, and environmental chemistry. Importantly, recent developments in these fields have now enabled comprehensive studies that could efficiently address the manifold interactions between chemicals and ecosystems. Based on their experience with intricate studies of biodiversity, ecologists are well equipped to embrace the additional challenge of chemical complexity through interdisciplinary collaborations. This offers a unique opportunity to jointly advance a seminal frontier in pollution ecology and facilitate the development of innovative solutions for environmental protection.

A systematic review of the effects of cold exposure on pathological cardiac remodeling in mice - Alexandre Martins Oliveira Portes; Ana Beatriz Rezende Paula; Denise Coutinho de Miranda; Letícia Teresinha Resende; Bianca Iara Campos Coelho; Maria Cecília Teles; Isabela Alcântara Barretto Araújo Jardim; Antônio José Natali; Ana Maria de Lauro Castrucci; Mauro César Isoldi (Journal of Thermal Biology, 2023)

Whole bone subcutaneous transplantation as a strategy to study precisely the bone marrow niche - Caroline C. Picoli; Patrícia Rocha Martins; Xiao Lin Casey Wong; Thamires Righi; Pedro P. G. Guimarães; Mauro C. X. Pinto; Jaime H. Amorim; Vasco A. C. Azevedo; Silma Regina Pereira; Alexandre Kanashiro; Fabio Cardoso Cruz; Rodrigo R. Resende; et al. (Stem Cell Reviews and Reports, 2023)

Assessment of aquifer recharge and groundwater availability in a semiarid region of Brazil in the context of an interbasin water transfer scheme - Alexandre C. Costa; Fanny Dupont; George Bier; Pieter van Oel; David W. Walker; Eduardo S. P. R. Martins (Hydrogeology Journal, 2023)
Particularly in arid and semiarid areas, more and more populations rely almost entirely on imported water. However, the extent to which intentional discharge into transiting river systems and unintentional leakage may be augmenting water resources for communities along and down gradient of the water transfer scheme has not previously been subject to research. The objective of this study was to assess both the potential of a large-scale water transfer (WT) scheme to increase groundwater availability by channel transmission losses in a large dryland aquifer system (2,166 km²) in Brazil, and the capability of the receiving streams to transport water downstream under a prolonged drought. An integrated surface-water/groundwater model was developed to improve the estimation of the groundwater resources, considering the spatio-temporal variability of infiltrated rainfall for aquifer recharge. Aquifer recharge from the WT scheme was simulated under prolonged drought conditions, applying an uncertainty analysis of the most influential fluxes and parameters. The annual recharge (66 mm/year) was approximately twice the amount of water abstracted (1990–2016); however, the annual recharge dropped to 13.9 mm/year from 2012 to 2016, a drought period. Under similar drought conditions, the additional recharge (6.89 × 106 m³/year) from the WT scheme did not compensate for the decrease in groundwater head in areas that do not surround the receiving streams. Actually, the additional recharge is counteracted by a decrease of 25% of natural groundwater recharge or an increase of 50% in pumping rate; therefore, WT transmission losses alone would not solve the issue of the unsustainable management of groundwater resources.

Xenarthra richness and activity pattern in the Brazilian Amazon - Maíra Prestes Margarido; Elildo A. R. Carvalho; Whaldener Endo; Alexandre Martins Costa Lopes; Flávia Regina Miranda (Mammalian Biology, 2023)

Go for Lipids! Food Preferences and Nutrient Composition in Zoo-Housed White-Faced Sakis, Pithecia pithecia - Vasco Alexandre Martins; Natalie Magnusson; Matthias Laska (International Journal of Primatology, 2023)
The role that single nutrients may play for food choices in nonhuman primates is not fully understood. White-faced sakis ( Pithecia pithecia ) are unusual among frugivorous primates as they do not serve as seed dispersers but rather exploit the seeds they consume, presumably for their high contents of lipids and proteins. Therefore, we assessed the occurrence of spontaneous food preferences in zoo-housed white-faced sakis and analyzed whether these preferences correlate with nutrient composition. Using a two-alternative choice test, we repeatedly presented three female and two male sakis with all possible binary combinations of 15 types of food that are part of their diet under human care, and found them to display the following rank order of preference: peanut > hazelnut > avocado > melon > egg > apple > mealworms > beetroot > carrot > cucumber > cabbage > tomato > sweet potato > broccoli > eggplant. This preference ranking significantly and positively correlated with the total energy content of the food items. However, we found the strongest positive correlation among the three macronutrients providing metabolic energy between the sakis’ food preferences and lipid content. This is remarkable as all other primate species tested so far using this method displayed the strongest correlation with carbohydrates instead. Together with our finding that the sakis significantly preferred foods high in mono-unsaturated fatty acids, the building blocks of lipids, these results support the notion that white-faced sakis exploit the lipids contained in seeds to meet their requirements of metabolic energy.

Antimicrobial and Antibiofilm Activity of Copper-Based Metallic Compounds Against Bacteria Related with Healthcare-Associated Infections - Anna L. Pereira; Mayron A. Vasconcelos; Alexandre L. Andrade; Israel M. Martins; Alda K. M. Holanda; Ana C. S. Gondim; Dayana P. S. Penha; Katherine L. Bruno; Francisco O. N. Silva; Edson H. Teixeira (Current Microbiology, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Bacterial identification in cerebrospinal fluid of domestic species with neurologic signs: a retrospective case-series study in 136 animals (2005–2021) - Márcio Garcia Ribeiro; Thiago Tourinho Pereira; Patrik Júnior de Lima Paz; Beatriz Oliveira de Almeida; Carmen S. Araújo Cerviño; Carolina Aparecida Rodrigues; Gabrielly Terra Sartori Santos; Larissa Maria de Souza Freire; Fábio Vinicius Ramos Portilho; Marcelo Fagali Árabe Filho; Natália Rodrigues Paschoal; Thaís Spessotto Bello; et al. (Brazilian Journal of Microbiology, 2023)

δ26Mg, δ44Ca and 87Sr/86Sr isotope differences among bedrock minerals constrain runoff generation in headwater catchments: An acidified granitic site in Central Europe as an example - Martin Novák; Alexandre V. Andronikov; Chris Holmden; Yulia V. Erban Kochergina; František Veselovský; Tomáš Pačes; Martina Vítková; Václav Kachlík; Ondřej Šebek; Jakub Hruška; Markéta Štěpánová; Jan Čuřík; et al. (CATENA, 2023)

Precipitation extremes over the tropical Americas under RCP4 .5 and RCP8 .5 climate change scenarios: Results from dynamical downscaling simulations - Alexandre Araújo Costa; Sullyandro Oliveira Guimarães; Domingo Cassain Sales; Francisco das Chagas Vasconcelos Junior; Marcos Wender Santiago Marinho; José Marcelo Rodrigues Pereira; Eduardo Sávio Passos Rodrigues Martins; Emerson Mariano da Silva (International Journal of Climatology, 2023)
The Regional Atmospheric Modelling System (RAMS) driven by data from the CMIP5 Earth System Model HadGEM2‐ES was used to simulate daily precipitation over the tropical Americas for both current and future climate, including distinct scenarios (representative concentration pathways 4.5 and 8.5) and different time horizons (short‐term, mid‐term and long‐term changes). The major objective was to evaluate possible future changes in extreme events, with emphasis on the intensity of precipitation events and the duration of wet and dry spells. According to RAMS, longer dry spells are expected over most regions of the tropical Americas in the future, with indications for Northeast Brazil, Caribbean, Northern Amazon, and shorter wet spells over Central America and Amazon. With the exception of the Caribbean, there is a general tendency towards the increased frequency of intense precipitation in the tropical Americas.

Static Balance in Hereditary Spastic Paraplegias: a Cross-sectional Study - Diana Maria Cubillos-Arcila; Valéria Feijó Martins; Ana Paula Janner Zanardi; Gustavo Dariva Machado; Daniela Burguêz; Natalia Andrea Gomeñuka; Leonardo Alexandre Peyré-Tartaruga; Jonas Alex Morales Saute (The Cerebellum, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Biological pilot treatment reduces physicochemical and microbiological parameters of dairy cattle wastewater - Marcos Filgueiras Jorge; Leonardo Duarte Batista da Silva; Jonathas Batista Gonçalves Silva; Dinara Grasiela Alves; Cristina Moll Huther; Daiane Cecchin; José Guilherme Marinho Guerra; Luise Maria Martins dos Santos; João Paulo Francisco; Antonio Carlos Farias de Melo; Alexandre Lioi Nascentes; Rozileni Piont Kovsky Caletti (Environmental Science and Pollution Research, 2022)

The impact of COVID-19 on antimicrobial prescription and drug resistance in fungi and bacteria - Junya L. Singulani; Danielle L. Silva; Caroline M. Lima; Vanessa C. R. Magalhães; Ludmila M. Baltazar; Nalu T. A. Peres; Rachel B. Caligiorne; Alexandre S. Moura; Ana Raquel O. Santos; Tatiani Fereguetti; Juliana C. Martins; Lívia F. Rabelo; et al. (Brazilian Journal of Microbiology, 2022)

A novel in vitro propagation system for West Indian elm [Guazuma ulmifolia Lam. (Malvaceae)]: a valuable medicinal woody species - Mayla de Jesus Santana; Sebastião Martins Barbosa-Júnior; Lana Laene Lima Dias; Lázara Aline Simões Silva; Givanildo Zildo da Silva; Evandro Alexandre Fortini; Diego Silva Batista; Wagner Campos Otoni; Antônio Paulino da Costa Netto; Diego Ismael Rocha (In Vitro Cellular & Developmental Biology - Plant, 2022)

Bioaccumulation of trace metals in Neoechinorhynchus buttnerae and in its fish host tambaqui (Colossoma macropomum) from fish farms - Gabriela Tomas Jerônimo; Edson Luniere Porto; Marcos Alexandre Bolson; Ézio Sargentini-Júnior; Maurício Laterça Martins; Matheus Gomes da Cruz (Environmental Science and Pollution Research, 2022)

Assessing bias in aerial surveys for cetaceans: Results from experiments conducted with the franciscana dolphin - Federico Sucunza; Daniel Danilewicz; Artur Andriolo; Franciele R. de Castro; Marta Cremer; Pablo Denuncio; Emanuel Ferreira; Paulo A. C. Flores; Paulo H. Ott; Martin S. Perez; Dan Pretto; Camila M. Sartori; et al. (Frontiers in Marine Science, 2022)
Line transect aerial surveys are widely used for estimating abundance of biological populations, including threatened species. However, estimates obtained with data collected from aircraft are often underestimated because of visibility bias and bias in estimating group sizes from a fast-moving platform. An assessment of multiple sources of bias in aerial surveys were carried out in Brazilian coastal waters by experiments on multiple survey platforms (i.e., boat, airplane and helicopter). These studies focused on evaluating visibility bias (perception and availability bias) and potential differences in the estimation of group sizes from different types of platforms used in franciscana ( Pontoporia blainvillei ) abundance surveys. The ultimate goal was to develop correction factors to improve accuracy of estimates of density and population size for this threatened dolphin. Estimates of density and group sizes computed from boats were assumed to be unbiased and were compared to estimates of these quantities obtained from an airplane in the same area and period. In addition, helicopter surveys were conducted in two areas where water turbidity differed (clear vs. murky waters) to determine surfacing-diving intervals of franciscana groups and to estimate availability for aerial platforms. Abundance computed from the aerial survey data underestimated the true abundance by about 4-5 times, with ~70% of the total bias resulting from visibility bias (~80% from availability bias and ~20% from perception bias) and ~30% from bias in estimates of group size. The use of multiple survey platforms in contrasting habitats provided the opportunity to compute correction factors that can be used to refine range wide abundance estimates of the threatened franciscana given certain assumptions are met. Visibility bias and group size bias were substantial and clearly indicate the importance for accounting for such correction factors to produce unequivocal population assessment based on aerial survey data.

Effect of hip and knee joint angles on resting hamstring muscles rigidity in men and women - Jérémie Bouvier; Cyril Martin; Alexandre Fouré (European Journal of Applied Physiology, 2022)

Synthesis of a biobased resin and its screening as an alternative adsorbent for organic and inorganic micropollutant removal - Wardleison Martins Moreira; Paula Valéria Viotti; Alexandre Amado de Moura; Marcelino Luiz Gimenes; Melissa Gurgel Adeodato Vieira (Environmental Science and Pollution Research, 2022)

Global patterns in endemicity and vulnerability of soil fungi - Leho Tedersoo; Vladimir Mikryukov; Alexander Zizka; Mohammad Bahram; Niloufar Hagh‐Doust; Sten Anslan; Oleh Prylutskyi; Manuel Delgado‐Baquerizo; Fernando T. Maestre; Jaan Pärn; Maarja Öpik; Mari Moora; et al. (Global Change Biology, 2022)
Fungi are highly diverse organisms, which provide multiple ecosystem services. However, compared with charismatic animals and plants, the distribution patterns and conservation needs of fungi have been little explored. Here, we examined endemicity patterns, global change vulnerability and conservation priority areas for functional groups of soil fungi based on six global surveys using a high‐resolution, long‐read metabarcoding approach. We found that the endemicity of all fungi and most functional groups peaks in tropical habitats, including Amazonia, Yucatan, West‐Central Africa, Sri Lanka, and New Caledonia, with a negligible island effect compared with plants and animals. We also found that fungi are predominantly vulnerable to drought, heat and land‐cover change, particularly in dry tropical regions with high human population density. Fungal conservation areas of highest priority include herbaceous wetlands, tropical forests, and woodlands. We stress that more attention should be focused on the conservation of fungi, especially root symbiotic arbuscular mycorrhizal and ectomycorrhizal fungi in tropical regions as well as unicellular early‐diverging groups and macrofungi in general. Given the low overlap between the endemicity of fungi and macroorganisms, but high conservation needs in both groups, detailed analyses on distribution and conservation requirements are warranted for other microorganisms and soil organisms.

A 247‐year tree‐ring reconstruction of spring temperature and relation to spring flooding in eastern boreal Canada - Alexandre Florent Nolin; Martin Philippe Girardin; Jacques Clément Tardif; Xiao Jing Guo; France Conciatori; Yves Bergeron (International Journal of Climatology, 2022)
Few records of spring paleoclimate are available for boreal Canada, as biological proxies recording the beginning of the warm season are uncommon. Given the spring warming observed during the last decades, and its impact on snowmelt and hydrological processes, searching for spring climate proxies is receiving increasing attention. Tree‐ring anatomical features and intra‐annual widths were used to reconstruct the regional March to May mean air temperature from 1770 to 2016 in eastern boreal Canada. Nested principal component regressions calibrated on 116 years of gridded temperature data were developed from one Fraxinus nigra and 10 Pinus banksiana sites. The reconstruction indicated three distinct phases in spring temperature variability since 1770. Ample phases of multi‐decadal warm and cold springs persisted until the end of the Little Ice Age (1850–1870 CE) and were gradually replaced since the 1940s by decadal to interannual variability associated with an increase in the frequency and magnitude of warm springs. Significant correlations with other paleotemperature records, gridded snow cover extent and runoff support that historical high flooding were associated with late, cold springs with heavy snow cover. Most of the high magnitude spring floods reconstructed for the nearby Harricana River also coincided with the lowest reconstructed spring temperature per decade. However, the last 40 years of observed and reconstructed mean spring temperature showed a reduction in the number of extreme cold springs contrasting with the last few decades of extreme flooding in the eastern Canadian boreal region. This result indicates that warmer late spring mean temperatures on average may contribute, among other factors, to advance the spring break‐up and to likely shift the contribution of snow to rain in spring flooding processes.

The Balkan terranes: a missing link between the eastern and western segments of the Avalonian–Cadomian orogenic belt? - Jiří Žák; Martin Svojtka; Ianko Gerdjikov; Alexandre Kounov; Dian A. Vangelov (International Geology Review, 2022)

Techniques for monitoring dairy calves against the tick fever agents: a comparative analysis - Luciana Maffini Heller; Dina María Beltrán Zapa; Luiz Fellipe Monteiro Couto; Lídia Mendes de Aquino Gontijo; João Eduardo Nicaretta; Igor Maciel Lopes de Morais; Vanessa Ferreira Salvador; Luccas Lourenzzo Lima Lins Leal; Lorena Lopes Ferreira; Hariye Victória Iuasse; Alexandre Braga Scarpa; João Ricardo de Souza Martins; et al. (Veterinary Research Communications, 2022)

Zika Virus Strains and Dengue Virus Induce Distinct Proteomic Changes in Neural Stem Cells and Neurospheres - Juliana Minardi Nascimento; Danielle Gouvêa-Junqueira; Giuliana S. Zuccoli; Carolina da Silva Gouveia Pedrosa; Caroline Brandão-Teles; Fernanda Crunfli; André S. L. M. Antunes; Juliana S. Cassoli; Karina Karmirian; José Alexandre Salerno; Gabriela Fabiano de Souza; Stéfanie Primon Muraro; et al. (Molecular Neurobiology, 2022)

Assessment of water, sanitation, and hygiene services in district health care facilities in rural area of Mekong Delta, Vietnam - Thi-Khanh-Dieu Hoang; Quach-An Binh; Xuan-Thanh Bui; Thi-Hieu Le; Bao-Trong Dang; Hong-Hai Nguyen; Thi-Tra-My Ngo; Petra Kohler; Solomzi Makohliso; Peter Maryna; Martin Raab; Alexandre Vanobberghen; et al. (Environmental Monitoring and Assessment, 2022)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Ruminal kinetics and nutritive value of Zuri grass silage harvested at different ages and added with powder molasses - Omar Ali; Luciana Junges; Eva Nara Oliveira Gomes; Juliana Oliveira Batistoti; Anderson Ramires Candido; Fernanda de Kássia Gomes; Rafael de Oliveira Lima; Amarildo Pedro da Silva; Jeniffer da Cruz Siqueira; Luís Carlos Vinhas Ítavo; Elson Martins Coelho; Gelson dos Santos Difante; et al. (Tropical Animal Health and Production, 2022)

Progression of Functional Gait in Hereditary Spastic Paraplegias - Diana Maria Cubillos-Arcila; Gustavo Dariva Machado; Lauren Sehnem; Daniela Burguêz; Ana Paula Janner Zanardi; Valéria Feijó Martins; Leonardo Alexandre Peyré-Tartaruga; Jonas Alex Morales Saute (The Cerebellum, 2022)

Evaluation of the antifungal activity of α, β, and δ-damascone and inclusion complexes in β-cyclodextrin against Candida spp - Maria Rayane Correia de Oliveira; Maria Gabriely de Lima Silva; Antonia Thassya Lucas dos Santos; Francisco Lucas Alves Batista; Roger Henrique Sousa da Costa; Anita Oliveira Brito Pereira Bezerr Martins; Beatriz Gonçalves da Cruz; Maria Flaviana Bezerra Morais-Braga; Henrique Douglas Melo Coutinho; Francisco Ernani Alves Magalhães; Diniz Maciel de Sena Junior; Alexandre Magno Rodrigues Teixeira; et al. (Folia Microbiologica, 2022)

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Global Potential Distribution of the South American Cutworm Pest Agrotis robusta (Lepidoptera: Noctuidae) - Germán San Blas; Gisella Obholz; Fernando Maia Silva Dias; Alexandre Specht; Mirna Martins Casagrande; Olaf Hermann Hendrik Mielke (Neotropical Entomology, 2022)

SIA‐BRA: A database of animal stable carbon and nitrogen isotope ratios of Brazil - Thaís Rovere Diniz‐Reis; Fernanda Gaudio Augusto; Adibe Luiz Abdalla Filho; Maria Gabriella da Silva Araújo; Siglea Sanna Freitas Chaves; Rodrigo Figueiredo Almeida; Elen Blanco Perez; Carla da Penha Simon; Janaína Leite de Souza; Cristiane Formigosa Gadelha da Costa; Taciana Figueiredo Gomes; Melissa Gaste Martinez; et al. (Global Ecology and Biogeography, 2022)
Motivation SIA‐BRA is a data set that compiles stable carbon (C) and nitrogen (N) isotope ratios of terrestrial and aquatic animals sampled in Brazilian biomes and coastal marine areas. Stable isotope ratios are helpful in animal ecology for several reasons; for instance, they can be used to investigate trophic niches, energy sources (diet tracing) and to track migration patterns. The Neotropics are considered one of the most undersampled regions of the world. Given that Brazil is a continental country where most of the dietary ecology of animal species is under‐assessed, we believe that the SIA‐BRA can provide important complementary information to address this gap in the literature. Additionally, the SIA‐BRA data set allows future investigations to address many questions concerning diet tracing, habitat use, food webs, foraging ecology, physiological aspects and effects of phylogeny on dietary ecology. Main type of variable investigated Carbon and nitrogen stable isotope ratios for terrestrial and aquatic animals. Spatial location and grain The SIA‐BRA included animal tissues sampled in 964 sites in the main Brazilian biomes and coastal marine areas. Time period The data represent information published and/or sampled from 1984 to 2021. Major taxa studied and measurement level The SIA‐BRA contains isotopic data of c . 21,804 non‐captive wildlife specimens, excluding livestock production or laboratory experiments. They were 13,881 vertebrates and 7,923 invertebrates. They were divided into the following habitats: terrestrial (30% of the total), freshwater (27%), oceanic (40%) and estuarine (4%). There were 11 phyla, with a clear dominance of Chordata (64%) and Arthropoda (29%), 36 classes, 154 orders, 473 families, 894 genera and 1,157 species. Software format Data are supplied as a comma‐delimited text file (.csv).

Advances in Brazil Nut Tree Ecophysiology: Linking Abiotic Factors to Tree Growth and Fruit Production - Karen Cristina Pires da Costa; José Francisco de Carvalho Gonçalves; Alexandre Leão Gonçalves; Adamir da Rocha Nina Junior; Roberto Kirmayr Jaquetti; Vinícius Fernandes de Souza; Josiane Celerino de Carvalho; Andreia Varmes Fernandes; Joelma Keith Rodrigues; Gleisson de Oliveira Nascimento; Lúcia Helena de O. Wadt; Karen A. Kainer; et al. (Current Forestry Reports, 2022)

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Crambe meal and crude glycerin from biodiesel production in diets for finishing of crossbred cattle in feedlot - Eduardo Souza Leal; Luís Carlos Vinhas Ítavo; Camila Celeste Brandão Ferreira Ítavo; Marina de Nadai Bonin Gomes; Alexandre Menezes Dias; Aline Gomes da Silva; Gumercindo Loreano Franco; Marília Williani Filgueira Pereira; Camila da Silva Pereira; Alysson Martins Wanderley; Juliana Antonia Tonetto de Mello; Antonio Leandro Chaves Gurgel; et al. (Tropical Animal Health and Production, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Rainfall governs picocyanobacterial ecology in a tropical estuary (Guanabara Bay, Brazil) - Alexandre Buzzani; Rodolfo Paranhos; Marianne P. Mello; Fernanda Abreu; Anderson Aquino dos Santos; Rafael Martins; Kayo Bianco; Maysa Mandetta Clementino; Fernando H. Pulgati; Anderson de Souza Cabral (Hydrobiologia, 2022)

Ruminal degradation kinetics of diets with different lipid sources and its influence on intake and milk yield of early lactation crossbred Holstein × Gir cows - Alysson Martins Wanderley; Luís Carlos Vinhas Ítavo; Geraldo Tadeu dos Santos; Camila Celeste Brandão Ferreira Ítavo; Camila Soares Cunha; Gelson dos Santos Difante; Alexandre Menezes Dias; Rodrigo Gonçalves Mateus; Marcus Vinícius Moraes de Oliveira (Tropical Animal Health and Production, 2021)

Reproductive and Stress Response Hormones of the Critically Endangered Southern Muriqui (Brachyteles arachnoides: Atelidae) Under Captive Conditions - Alexandre Bastos Fernandes Lima; Gisela Sobral; Gabriela Siqueira Martins; Alcides Pissinatti; Priscila Viau; Claudio Alvarenga de Oliveira (International Journal of Primatology, 2021)

Therapeutic prevention of COVID-19 in elderly: a case–control study - Frederic Blanc; Cedric Waechter; Thomas Vogel; Benoit Schorr; Catherine Demuynck; Catherine Martin Hunyadi; Maxence Meyer; Denata Mutelica; Nadjiba Bougaa; Samira Fafi-Kremer; Lidia Calabrese; Elise Schmitt; et al. (GeroScience, 2021)

Prognosis of rash and chilblain-like lesions among outpatients with COVID-19: a large cohort study - Hélène Mascitti; Patrick Jourdain; Alexandre Bleibtreu; Luc Jaulmes; Agnès Dechartres; Xavier Lescure; Youri Yordanov; Aurélien Dinh; Caroline Apra; Arthur Mensch; Amélie Aime-Eusebi; Erwan Debuc; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Large-scale Degradation of the Tocantins-Araguaia River Basin - Fernando Mayer Pelicice; Angelo Antonio Agostinho; Alberto Akama; José Dilermando Andrade Filho; Valter M. Azevedo-Santos; Marcus Vinicius Moreira Barbosa; Luis Mauricio Bini; Marcelo Fulgêncio Guedes Brito; Carlos Roberto dos Anjos Candeiro; Érica Pellegrini Caramaschi; Priscilla Carvalho; Rodrigo Assis de Carvalho; et al. (Environmental Management, 2021)

Albatrosses respond adaptively to climate variability by changing variance in a foraging trait - Samantha C. Patrick; Julien G. A. Martin; Caroline C. Ummenhofer; Alexandre Corbeau; Henri Weimerskirch (Global Change Biology, 2021)
The ability of individuals and populations to adapt to a changing climate is a key determinant of population dynamics. While changes in mean behaviour are well studied, changes in trait variance have been largely ignored, despite being assumed to be crucial for adapting to a changing environment. As the ability to acquire resources is essential to both reproduction and survival, changes in behaviours that maximize resource acquisition should be under selection. Here, using foraging trip duration data collected over 7 years on black‐browed albatrosses ( Thalassarche melanophris ) on the Kerguelen Islands in the southern Indian Ocean, we examined the importance of changes in the mean and variance in foraging behaviour, and the associated effects on fitness, in response to the El Niño Southern Oscillation (ENSO). Using double hierarchical models, we found no evidence that individuals change their mean foraging trip duration in response to a changing environment, but found strong evidence of changes in variance. Younger birds showed greater variability in foraging trip duration in poor conditions as did birds with higher fitness. However, during brooding, birds showed greater variability in foraging behaviour under good conditions, suggesting that optimal conditions allow the alteration between chick provisioning and self‐maintenance trips. We found weak correlations between sea surface temperature and the ENSO, but stronger links with sea‐level pressure. We suggest that variability in behavioural traits affecting resource acquisition is under selection and offers a mechanism by which individuals can adapt to a changing climate. Studies which look only at effects on mean behaviour may underestimate the effects of climate change and fail to consider variance in traits as a key evolutionary force.

A “Dirty” Footprint: Macroinvertebrate diversity in Amazonian Anthropic Soils - Wilian C. Demetrio; Ana C. Conrado; Agno N. S. Acioli; Alexandre C. Ferreira; Marie L. C. Bartz; Samuel W. James; Elodie da Silva; Lilianne S. Maia; Gilvan C. Martins; Rodrigo S. Macedo; David W. G. Stanton; Patrick Lavelle; et al. (Global Change Biology, 2021)
Amazonian rainforests, once thought to be pristine wilderness, are increasingly known to have been widely inhabited, modified, and managed prior to European arrival, by human populations with diverse cultural backgrounds. Amazonian Dark Earths (ADEs) are fertile soils found throughout the Amazon Basin, created by pre‐Columbian societies with sedentary habits. Much is known about the chemistry of these soils, yet their zoology has been neglected. Hence, we characterized soil fertility, macroinvertebrate communities, and their activity at nine archeological sites in three Amazonian regions in ADEs and adjacent reference soils under native forest (young and old) and agricultural systems. We found 673 morphospecies and, despite similar richness in ADEs (385 spp.) and reference soils (399 spp.), we identified a tenacious pre‐Columbian footprint, with 49% of morphospecies found exclusively in ADEs. Termite and total macroinvertebrate abundance were higher in reference soils, while soil fertility and macroinvertebrate activity were higher in the ADEs, and associated with larger earthworm quantities and biomass. We show that ADE habitats have a unique pool of species, but that modern land use of ADEs decreases their populations, diversity, and contributions to soil functioning. These findings support the idea that humans created and sustained high‐fertility ecosystems that persist today, altering biodiversity patterns in Amazonia.

Complete genome sequence and analysis of a Saccharomyces cerevisiae strain used for sugarcane spirit production - Ane Catarine Tosi Costa; Jacob Hornick; Tathiana Ferreira Sá Antunes; Alexandre Martins Costa Santos; A Alberto R. Fernandes; James R. Broach; Patricia M. B. Fernandes (Brazilian Journal of Microbiology, 2021)

Regulatory approaches for genome edited agricultural plants in select countries and jurisdictions around the world - Jon Entine; Maria Sueli S. Felipe; Jan-Hendrik Groenewald; Drew L. Kershen; Martin Lema; Alan McHughen; Alexandre Lima Nepomuceno; Ryo Ohsawa; Reynante L. Ordonio; Wayne A. Parrott; Hector Quemada; Carl Ramage; et al. (Transgenic Research, 2021)
Genome editing in agriculture and food is leading to new, improved crops and other products. Depending on the regulatory approach taken in each country or region, commercialization of these crops and products may or may not require approval from the respective regulatory authorities. This paper describes the regulatory landscape governing genome edited agriculture and food products in a selection of countries and regions.

Effect of Spatial Variation on Defensive Substances of Constrictotermes Cyphergaster Soldiers (Blattaria, Isoptera) - Antonio Paulino De Mello; Marcilio Martins De Moraes; Cláudio Augusto Gosmes Da Câmara; Alexandre Vasconcellos (Journal of Chemical Ecology, 2021)

Molecular characterization and sequence analysis of four Brazilian rice stripe necrosis virus isolates - Daniela Domingos de Souza; Ananias Pinto de Queiroz; Fernando Sartori Pereira; Érico de Campos Dianese; Thor Vinícius Martins Fajardo; Antonio Nhani Júnior; Douglas Lau; Leonardo Assis da Silva; Bergmann Morais Ribeiro; Alexandre Siqueira Guedes Coelho; Raimundo Wagner de Souza Aguiar; Raquel Neves de Mello; et al. (Archives of Virology, 2021)

Systematics and biogeography of the Boana albopunctata species group (Anura, Hylidae), with the description of two new species from Amazonia - Antoine Fouquet; Pedro Marinho; Alexandre Réjaud; Thiago R. Carvalho; Marcel A. Caminer; Martin Jansen; Raíssa N. Rainha; Miguel T. Rodrigues; Fernanda P. Werneck; Albertina P. Lima; Tomas Hrbek; Ariovaldo A. Giaretta; et al. (Systematics and Biodiversity, 2021)

Musical Chairs on Temperate Reefs: Species Turnover and Replacement Within Functional Groups Explain Regional Diversity Variation in Assemblages Associated With Honeycomb Worms - Alexandre Muller; Camille Poitrimol; Flávia L. D. Nunes; Aurélien Boyé; Amelia Curd; Nicolas Desroy; Louise B. Firth; Laura Bush; Andrew J. Davies; Fernando P. Lima; Martin P. Marzloff; Claudia Meneghesso; et al. (Frontiers in Marine Science, 2021)
Reef-building species are recognized as having an important ecological role and as generally enhancing the diversity of benthic organisms in marine habitats. However, although these ecosystem engineers have a facilitating role for some species, they may exclude or compete with others. The honeycomb worm Sabellaria alveolata ( Linnaeus, 1767 ) is an important foundation species, commonly found from northwest Ireland to northern Mauritania, whose reef structures increase the physical complexity of the marine benthos, supporting high levels of biodiversity. Local patterns and regional differences in taxonomic and functional diversity were examined in honeycomb worm reefs from 10 sites along the northeastern Atlantic to explore variation in diversity across biogeographic regions and the potential effects of environmental drivers. While taxonomic composition varied across the study sites, levels of diversity remained relatively constant along the European coast. Assemblages showed high levels of species turnover compared to differences in richness, which varied primarily in response to sea surface temperatures and sediment content, the latter suggesting that local characteristics of the reef had a greater effect on community composition than the density of the engineering species. In contrast, the functional composition of assemblages was similar regardless of taxonomic composition or biogeography, with five functional groups being observed in all sites and only small differences in abundance in these groups being detected. Functional groups represented primarily filter-feeders and deposit-feeders, with the notable absence of herbivores, indicating that the reefs may act as biological filters for some species from the local pool of organisms. Redundancy was observed within functional groups that may indicate that honeycomb worm reefs can offer similar niche properties to its associated assemblages across varying environmental conditions. These results highlight the advantages of comparing taxonomic and functional metrics, which allow identification of a number of ecological processes that structure marine communities.

A controlled-release fertilizer improved soil fertility but not olive tree performance - Ermelinda Silva; Margarida Arrobas; Alexandre Gonçalves; Sandra Martins; Soraia Raimundo; Luis Pinto; Cátia Brito; José Moutinho-Pereira; Carlos M. Correia; M. Ângelo Rodrigues (Nutrient Cycling in Agroecosystems, 2021)

Anti-inflammatory and antinociceptive activities of a phenylpropanoid-enriched fraction of Duguetia furfuracea - Aline Aparecida Saldanha; Letícia Vieira; Débora Soares da Silva Maia; Flávio Martins de Oliveira; Rosy Iara Maciel de Azambuja Ribeiro; Ralph Gruppi Thomé; Hélio Batista dos Santos; Débora de Oliveira Lopes; Carlos Alexandre Carollo; Denise Brentan Silva; Adriana Cristina Soares; João Máximo de Siqueira (Inflammopharmacology, 2021)

Seasonal differences in seminal plasma proteins from two bovine breeds adapted to a subtropical climate - Paula Lorena Souto; Lilian Silveira Travassos Carmouy; Cristiane Santos; Edison Martins; Vera Martins; Luciana Keiko Hatamoto-Zervoudakis; André Melro Murad; Angela Mehta; Concepta McManus; Alexandre Floriano Ramos (Tropical Animal Health and Production, 2021)

Increased frequency of blaNDM in a tertiary care hospital in southern Brazil - Priscila Lamb Wink; Amanda Silva Martins; Fabiana Volpato; Alexandre P. Zavascki; Afonso L. Barth (Brazilian Journal of Microbiology, 2021)

Fuel Consumption Between Two Soil Tillage Systems for Planting Sugarcane - Murilo Battistuzzi Martins; Fernanda Pacheco de Almeida Prado Bortolheiro; João Vitor Paulo Testa; Maria Márcia Pereira Sartori; Carlos Alexandre Costa Crusciol; Kléber Pereira Lanças (Sugar Tech, 2021)

Traditional Knowledge Aids Description When Resolving the Taxonomic Status of Unsettled Species Using Classical and Molecular Taxonomy: The Case of the Shallow-Water Octopus Callistoctopus furvus (Gould, 1852) From the Western Atlantic Ocean - Manuella Dultra Jesus; João Bráullio de Luna Sales; Rodrigo Silvestre Martins; Jonathan Stuart Ready; Tarcisio Augusto S. Costa; Jonathan D. Ablett; Alexandre Schiavetti (Frontiers in Marine Science, 2021)
Shallow-water marine invertebrate fauna is diverse in tropical latitudes but generally poorly known. This is in part due the remoteness of many of these regions, and a lack of locally trained taxonomists. In such cases, the ethnoknowledge (i.e., information acquired from the sociocultural references of a given social group) of traditional human populations may be a valuable tool to elucidate gaps in the occurrence of some taxa. In this study, we used a combined approach of ethnoknowledge, classic taxonomy and molecular techniques to describe and diagnose an unsettled species of shallow-water octopus of the genus Callistoctopus . A neotype for the Brazilian eastern octopus Callistoctopus furvus ( Gould, 1852 ) is described along with some ecological notes. Octopuses were collected between April and May 2018 during field trips guided by artisanal octopus fishers of Bahia State (Brazil). A linear discriminant analysis showed that the morphology of C. furvus overlapped poorly with Callistoctopus sp. from the Caribbean and Macaronesia (Madeira Archipelago) as well as with Callistoctopus macropus stricto sensu from Mediterranean Sea. Analysis of mitochondrial large ribosomal subunit (rrnL, also known as 16S) gene and cytochrome C oxidase I (COI) showed that C. furvus differs genetically from European C. macropus and the other species in the genus. In general, C. furvus differs from other Atlantic/Mediterranean Callistoctopus species in having a slender body shape and longer mantle lengths. As in other species of the genus, C. furvus is nocturnal and inhabits sandy bottoms, seagrass beds and/or low-profile reefs. Interestingly, C. furvus burrows itself into the sand as a defense mechanism. In conclusion, we showed the support of ethnoknowledge for integrative biodiversity assessments in poorly surveyed remote areas in the western tropical Atlantic.

Haloperidol Interactions with the dop-3 Receptor in Caenorhabditis elegans - Bárbara Nunes Krum; Airton C. Martins; Libânia Queirós; Beatriz Ferrer; Ginger L. Milne; Félix Alexandre Antunes Soares; Roselei Fachinetto; Michael Aschner (Molecular Neurobiology, 2021)

Molecular Responses of Mussel Mytilus galloprovincialis Associated to Accumulation and Depuration of Marine Biotoxins Okadaic Acid and Dinophysistoxin-1 Revealed by Shotgun Proteomics - José Carlos Martins; Dany Domínguez-Pérez; Catarina Azevedo; Ana Catarina Braga; Pedro Reis Costa; Hugo Osório; Vitor Vasconcelos; Alexandre Campos (Frontiers in Marine Science, 2020)
The molecular pathways behind the toxicity of diarrheic shellfish toxins (DSTs) in bivalves have been scarcely studied. Thus, a shotgun proteomics approach was applied in this work to understand bivalves’ molecular responses to the dinoflagellate Prorocentrum lima (1.0 × 10 6 cells/L). Protein expression along with toxins levels were analyzed in the gills and digestive gland of the mussel Mytilus galloprovincialis during and after exposure to this toxic strain. Results revealed an accumulation of OA and DTX1 only in the digestive gland with maximum amounts attained at the end of uptake phase (day 5; 2819.2 ± 522.2 μg OA/kg and 1107.1 ± 267.9 μg DTX1/kg). At the end of the depuration phase (day 20), 16% and 47% of total OA and DTX1 concentrations remained in the digestive gland tissues, respectively. The shotgun proteomic analyses yielded 3051 proteins in both organs. A total of 56 and 54 differentially expressed proteins (DEPs) were revealed in the digestive gland and gills, respectively. Both organs presented the same response dynamics along the experiment, although with tissue-specific features. The early response (3 days uptake) was characterized by a high number of DEPs, being more marked in gills, in relation to the latter time points (5 days uptake and depuration). Functional enrichment analysis revealed the up-regulation of carboxylic (GO:0046943) and organic acid transmembrane transporter activity (GO:0005342) pathways after 3 days uptake for digestive gland. Matching to these pathways are a group of proteins related to transmembrane transport and response to toxic substances and xenobiotics, namely P-glycoprotein (ABCB11), Sodium-dependent proline transporter (SLC6A7), and Sideroflexin-1 (SFXN1). According to Clusters of Orthologous Groups (GOs) categories, most of the DEPs found for digestive gland in all time-points were related with “cellular processes and signaling” and involving signal transduction mechanisms, cytoskeleton and post-translational modification, protein turnover, chaperone functions. In gills, the early uptake phase was marked by a balance between DEPs related with “cellular processes and signaling” and “metabolism.” Depuration is clearly marked by processes related with “metabolism,” mainly involving secondary metabolites biosynthesis, transport, and catabolism. Proteomic data are available via ProteomeXchange with identifier PXD022293.

Implications of climate change mitigation strategies on international bioenergy trade - Vassilis Daioglou; Matteo Muratori; Patrick Lamers; Shinichiro Fujimori; Alban Kitous; Alexandre C. Köberle; Nico Bauer; Martin Junginger; Etsushi Kato; Florian Leblanc; Silvana Mima; Marshal Wise; et al. (Climatic Change, 2020)
Most climate change mitigation scenarios rely on increased use of bioenergy to decarbonize the energy system. Here we use results from the 33rd Energy Modeling Forum study (EMF-33) to investigate projected international bioenergy trade for different integrated assessment models across several climate change mitigation scenarios. Results show that in scenarios with no climate policy, international bioenergy trade is likely to increase over time, and becomes even more important when climate targets are set. More stringent climate targets, however, do not necessarily imply greater bioenergy trade compared to weaker targets, as final energy demand may be reduced. However, the scaling up of bioenergy trade happens sooner and at a faster rate with increasing climate target stringency. Across models, for a scenario likely to achieve a 2 °C target, 10–45 EJ/year out of a total global bioenergy consumption of 72–214 EJ/year are expected to be traded across nine world regions by 2050. While this projection is greater than the present trade volumes of coal or natural gas, it remains below the present trade of crude oil. This growth in bioenergy trade largely replaces the trade in fossil fuels (especially oil) which is projected to decrease significantly over the twenty-first century. As climate change mitigation scenarios often show diversified energy systems, in which numerous world regions can act as bioenergy suppliers, the projections do not necessarily lead to energy security concerns. Nonetheless, rapid growth in the trade of bioenergy is projected in strict climate mitigation scenarios, raising questions about infrastructure, logistics, financing options, and global standards for bioenergy production and trade.

Implementation and certification of ISO 9001:2015 seal in human tissue bank HCFMRP-USP - Carlos Alexandre Curylofo Corsi; Mitsuhisa Shoji; Katia Carmen Gabriel Scarpelini; Rodolfo Leandro Bento; Christiane Becari; Alan Vinicius Assunção-Luiz; Álefe Saloum Cintra; Luís Gustavo Gazoni Martins (Cell and Tissue Banking, 2020)

Guanosine Neuroprotection of Presynaptic Mitochondrial Calcium Homeostasis in a Mouse Study with Amyloid-β Oligomers - Jussemara Souza da Silva; Yasmine Nonose; Francieli Rohden; Pâmela C. Lukasewicz Ferreira; Fernanda Urruth Fontella; Andréia Rocha; Andressa Wigner Brochier; Rodrigo Vieira Apel; Thais Martins de Lima; Bianca Seminotti; Alexandre Umpierrez Amaral; Antonio Galina; et al. (Molecular Neurobiology, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Anti-inflammatory and central and peripheral anti-nociceptive activities of α-asarone through the inhibition of TNF-α production, leukocyte recruitment and iNOS expression, and participation of the adenosinergic and opioidergic systems - Aline Aparecida Saldanha; Letícia Vieira; Flávio Martins de Oliveira; Débora de Oliveira Lopes; Rosy Iara Maciel de Azambuja Ribeiro; Ralph Gruppi Thomé; Hélio Batista dos Santos; Denise Brentan Silva; Carlos Alexandre Carollo; João Máximo de Siqueira; Adriana Cristina Soares (Inflammopharmacology, 2020)

Seroepidemiological study of Caseous lymphadenitis in sheep from the Northeast region of Brazil using an indirect ELISA - José Romero Alexandre Alves; Areano Ethério Moreira de Farias; Denize Monteiro dos Anjos; Ana Milena Cézar Lima; Patrícia Yoshida Faccioli-Martins; Carlos José Hoff de Souza; Raymundo Rizaldo Pinheiro; Francisco Selmo Fernandes Alves; Sérgio Santos de Azevedo; Clebert José Alves (Tropical Animal Health and Production, 2020)

Influence of land use on the performance of the WRF model in a humid tropical climate - Youssimar Georgynio Rosales Aylas; Wesley de Souza Campos Correa; Alexandre Magalhães Santiago; Neyval Costa Reis Junior; Taciana Toledo de Almeida Albuquerque; Jane Meri Santos; Davidson Martins Moreira (Theoretical and Applied Climatology, 2020)

Modelling the water level of the alluvial aquifer of an ephemeral river in south-western Zimbabwe - Sibonakaliso C. Mpala; Alexandre S. Gagnon; Martin G. Mansell; Stephen W. Hussey (Hydrological Sciences Journal, 2020)

Conservation assessment of cassava wild relatives in central Brazil - Marcelo F. Simon; Talita S. Reis; J. Moises Mendoza F.; Thalyssa K. M. Arquelão; João B. A. Bringel; Sérgio E. Noronha; Márcio L. L. Martins; Carlos A. S. Ledo; Marcos J. Silva; Alexandre B. Sampaio; Eraldo T. Matricardi; Aldicir Scariot (Biodiversity and Conservation, 2020)

Phenology, Seed Germination, and Genetics Explains the Reproductive Strategies of Diospyros lasiocalyx (Mart.) B. Wall - Bruna Ibanes Aguiar; Alexandre Magno Sebbenn; Roberto Tarazi; Nara Oliveira Vogado; Leonor Patricia C. Morellato; Evandro Vagner Tambarussi; Maria Andréia Moreno; Lya C. S. M. Pereira; Cinthia Montibeller; Elza Martins Ferraz; Flávio Bertin Gandara; Paulo Yoshio Kageyama (Tropical Plant Biology, 2020)

A novel GIS-based tool to reveal spatial trends in reaction norm: upland rice case study - Germano Martins F. Costa-Neto; Odilon P. Morais Júnior; Alexandre Bryan Heinemann; Adriano Pereira de Castro; João Batista Duarte (Euphytica, 2020)

Characterization of a mine legacy site: an approach for environmental management and metals recovery - Maria de Lurdes Dinis; António Fiúza; Aurora Futuro; Alexandre Leite; Diogo Martins; Janine Figueiredo; Joaquim Góis; Maria Cristina Vila (Environmental Science and Pollution Research, 2020)
The characterization of historical mine tailings provides important information for land-management decisions, in particular when considering potential reprocessing activities or the development of an environmental protection program. In addition, outcomes from such characterization may define the scope for a more detailed investigation. The present work describes the characterization of the waste material from the Cabeço do Pião tailings impoundment performed within the project ReMinE: Improve Resource Efficiency and Minimize Environmental Footprint. The purpose of the work was to investigate alternative mine waste management options such as the extraction of valuable resources from an environmental liability. The study involved the collection of 41 samples at different locations at two different depths, physical and chemical characterization of the wastes, natural leaching tests, and potential for acid generation. The results showed that, apart from the potential instability of the dyke (with an average slope of 35°), the drained solutions flowing by percolation contain very small particles with high arsenic contents that are being incorporated into the river sediments. In addition, these very fine-grained materials are available for the transport by the wind creating secondary sources of environmental contamination. This data is fundamental for economic and environmental assessment of the two main alternatives, reprocessing or removal.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

First report of cis-1,4-polyisoprene degradation by Gordonia paraffinivorans - Stefania Pegorin Braga; Alexandre Paes dos Santos; Thais Paganini; Deibs Barbosa; George Willian Condomitti Epamino; Carlos Morais; Layla Farage Martins; Aline Maria Silva; João Carlos Setubal; Marcelo Afonso Vallim; Renata Castiglioni Pascon (Brazilian Journal of Microbiology, 2019)

Human activity is altering the world’s zoogeographical regions - Rubén Bernardo‐Madrid; Joaquín Calatayud; Manuela González‐Suárez; Martin Rosvall; Pablo M. Lucas; Marta Rueda; Alexandre Antonelli; Eloy Revilla (Ecology Letters, 2019)
Zoogeographical regions, or zooregions, are areas of the Earth defined by species pools that reflect ecological, historical and evolutionary processes acting over millions of years. Consequently, researchers have assumed that zooregions are robust and unlikely to change on a human timescale. However, the increasing number of human‐mediated introductions and extinctions can challenge this assumption. By delineating zooregions with a network‐based algorithm, here we show that introductions and extinctions are altering the zooregions we know today. Introductions are homogenising the Eurasian and African mammal zooregions and also triggering less intuitive effects in birds and amphibians, such as dividing and redefining zooregions representing the Old and New World. Furthermore, these Old and New World amphibian zooregions are no longer detected when considering introductions plus extinctions of the most threatened species. Our findings highlight the profound and far‐reaching impact of human activity and call for identifying and protecting the uniqueness of biotic assemblages.

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Spatial modeling applied to environmental monitoring: identifying sources of potentially toxic metals in aquatic system - Elisabete Leide Marzola; Luana Maria Tavares Rosa; Rogério Hartung Toppa; Marcos Roberto Martines; Leonardo Machado Pitombo; Alexandre Donizeti Martins Cavagis; Janaina Braga do Carmo; Wander Gustavo Botero; Luciana Camargo de Oliveira (Environmental Geochemistry and Health, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Seroepidemiological characterization and risk factors associated with seroconversion to Corynebacterium pseudotuberculosis in goats from Northeastern Brazil - Areano Ethério Moreira de Farias; José Romero Alexandre Alves; Francisco Selmo Fernandes Alves; Raymundo Rizaldo Pinheiro; Patrícia Yoshida Faccioli-Martins; Ana Milena César Lima; Sérgio Santos de Azevedo; Clebert José Alves (Tropical Animal Health and Production, 2019)

Energetic characterization and evaluation of briquettes produced from naturally colored cotton waste - Janduir Egito da Silva; Dulce Maria de Araújo Melo; Marcus Antônio de Freitas Melo; Emerson Moreira de Aguiar; Alexandre Santos Pimenta; Everaldo Paulo de Medeiros; Guilherme Quintela Calixto; Renata Martins Braga (Environmental Science and Pollution Research, 2019)

Enterococcus faecium as potential probiotic for ornamental neotropical cichlid fish, Pterophyllum scalare (Schultze, 1823) - Joel Artur Rodrigues Dias; Higo Andrade Abe; Natalino Costa Sousa; Raimundo Darley Figueredo Silva; Carlos Alberto Martins Cordeiro; Grazielle Fernanda Evangelista Gomes; Jonathan Stuart Ready; José Luiz Pedreira Mouriño; Maurício Laterça Martins; Paulo César Falanghe Carneiro; Alexandre Nízio Maria; Rodrigo Yudi Fujimoto (Aquaculture International, 2019)

Chronic Metabolic Derangement-Induced Cognitive Deficits and Neurotoxicity Are Associated with REST Inactivation - Aline Pertile Remor; Rodrigo Augusto da Silva; Filipe José de Matos; Viviane Glaser; Roberta de Paula Martins; Karina Ghisoni; Débora da Luz Scheffer; Denise Carleto Andia; Daniele Portinho; Ana Paula de Souza; Paulo Alexandre de Oliveira; Rui Daniel Prediger; et al. (Molecular Neurobiology, 2019)

Comparison of sterol and fatty acid profiles of chytrids and their hosts reveals trophic upgrading of nutritionally inadequate phytoplankton by fungal parasites - Mélanie Gerphagnon; Ramsy Agha; Dominik Martin‐Creuzburg; Alexandre Bec; Fanny Perriere; Cecilia Rad‐Menéndez; Claire M.M. Gachon; Justyna Wolinska (Environmental Microbiology, 2019)
Summary Chytrids are ubiquitous fungal parasites in aquatic ecosystems, infecting representatives of all major phytoplankton groups. They repack carbon from inedible phytoplankton hosts into easily ingested chytrid propagules (zoospores), rendering this carbon accessible to zooplankton. Grazing on zoospores may circumvent bottlenecks in carbon transfer imposed by the dominance of inedible or poorly nutritious phytoplankton (mycoloop). We explored qualitative aspects of the mycoloop by analysing lipid profiles (fatty acids, sterols) of two chytrids infecting two major bloom‐forming phytoplankton taxa of contrasting nutritional value: the diatom Asterionella formosa and the filamentous cyanobacterium Planktothrix agardhii . The polyunsaturated fatty acid composition of chytrids largely reflected that of their hosts, highlighting their role as conveyors of otherwise inaccessible essential lipids to higher trophic levels. We also showed that chytrids are capable of synthesizing sterols, thus providing a source of these essential nutrients for grazers even when sterols are absent in their phytoplankton hosts. Our findings reveal novel qualitative facets of the mycoloop, showing that parasitic chytrids, in addition to making carbon and essential lipids available from inedible sources, also upgrade their host's biochemical composition by producing sterols de novo , thereby enhancing carbon and energy fluxes in aquatic food webs.

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

GST transcriptional changes induced by a toxic Microcystis aeruginosa strain in two bivalve species during exposure and recovery phases - Paulo Antas; Mariana Carneiro; Bruno Reis; Raquel Castelo-Branco; Joana Azevedo; Ralph Urbatzka; Alexandre Campos; Vítor Vasconcelos; José Carlos Martins (Ecotoxicology, 2018)

Genetic interaction between two insulin-dependent diabetes susceptibility loci, Idd2 and Idd13, in determining immunoregulatory DN T cell proportion - Roxanne Collin; Kathy Doyon; Victor Mullins-Dansereau; Martin Karam; Geneviève Chabot-Roy; Erin E. Hillhouse; Alexandre Orthwein; Sylvie Lesage (Immunogenetics, 2018)

The Inventory of Geological Heritage of the State of São Paulo, Brazil: Methodological Basis, Results and Perspectives - Maria da Glória Motta Garcia; José Brilha; Flávia Fernanda de Lima; Jean Carlos Vargas; Annabel Pérez-Aguilar; Adriana Alves; Ginaldo Ademar da Cruz Campanha; Wânia Duleba; Frederico Meira Faleiros; Luiz Alberto Fernandes; Marisa de Souto Matos Fierz; Maria Judite Garcia; et al. (Geoheritage, 2018)

Diagnosing drought using the downstreamness concept: the effect of reservoir networks on drought evolution - Pieter R. van Oel; Eduardo S. P. R. Martins; Alexandre C. Costa; Niko Wanders; Henny A. J. van Lanen (Hydrological Sciences Journal, 2018)

BacHBerry: BACterial Hosts for production of Bioactive phenolics from bERRY fruits - Alexey Dudnik; A. Filipa Almeida; Ricardo Andrade; Barbara Avila; Pilar Bañados; Diane Barbay; Jean-Etienne Bassard; Mounir Benkoulouche; Michael Bott; Adelaide Braga; Dario Breitel; Rex Brennan; et al. (Phytochemistry Reviews, 2018)

Phenological patterns of Spodoptera Guenée, 1852 (Lepidoptera: Noctuidae) is more affected by ENSO than seasonal factors and host plant availability in a Brazilian Savanna - Mônica Piovesan; Alexandre Specht; Eduardo Carneiro; Silvana Vieira Paula-Moraes; Mirna Martins Casagrande (International Journal of Biometeorology, 2018)

ATLANTIC MAMMAL TRAITS : a data set of morphological traits of mammals in the Atlantic Forest of South America - Fernando Gonçalves; Ricardo S. Bovendorp; Gabrielle Beca; Carolina Bello; Raul Costa‐Pereira; Renata L. Muylaert; Raisa R. Rodarte; Nacho Villar; Rafael Souza; Maurício E. Graipel; Jorge J. Cherem; Deborah Faria; et al. (Ecology, 2018)
Measures of traits are the basis of functional biological diversity. Numerous works consider mean species‐level measures of traits while ignoring individual variance within species. However, there is a large amount of variation within species and it is increasingly apparent that it is important to consider trait variation not only between species, but also within species. Mammals are an interesting group for investigating trait‐based approaches because they play diverse and important ecological functions (e.g., pollination, seed dispersal, predation, grazing) that are correlated with functional traits. Here we compile a data set comprising morphological and life history information of 279 mammal species from 39,850 individuals of 388 populations ranging from −5.83 to −29.75 decimal degrees of latitude and −34.82 to −56.73 decimal degrees of longitude in the Atlantic forest of South America. We present trait information from 16,840 individuals of 181 species of non‐volant mammals (Rodentia, Didelphimorphia, Carnivora, Primates, Cingulata, Artiodactyla, Pilosa, Lagomorpha, Perissodactyla) and from 23,010 individuals of 98 species of volant mammals (Chiroptera). The traits reported include body mass, age, sex, reproductive stage, as well as the geographic coordinates of sampling for all taxa. Moreover, we gathered information on forearm length for bats and body length and tail length for rodents and marsupials. No copyright restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Antiproliferative Activity and VEGF Expression Reduction in MCF7 and PC-3 Cancer Cells by Paclitaxel and Imatinib Co-encapsulation in Folate-Targeted Liposomes - Marco Júnio Peres-Filho; Alexandre Pereira dos Santos; Thais Leite Nascimento; Renato Ivan de Ávila; Fabrícia Saba Ferreira; Marize Campos Valadares; Eliana Martins Lima (AAPS PharmSciTech, 2018)

Patterns, biases and prospects in the distribution and diversity of Neotropical snakes - Thaís B. Guedes; Ricardo J. Sawaya; Alexander Zizka; Shawn Laffan; Søren Faurby; R. Alexander Pyron; Renato S. Bérnils; Martin Jansen; Paulo Passos; Ana L. C. Prudente; Diego F. Cisneros‐Heredia; Henrique B. Braz; et al. (Global Ecology and Biogeography, 2018)
Motivation We generated a novel database of Neotropical snakes (one of the world's richest herpetofauna) combining the most comprehensive, manually compiled distribution dataset with publicly available data. We assess, for the first time, the diversity patterns for all Neotropical snakes as well as sampling density and sampling biases. Main types of variables contained We compiled three databases of species occurrences: a dataset downloaded from the Global Biodiversity Information Facility (GBIF), a verified dataset built through taxonomic work and specialized literature, and a combined dataset comprising a cleaned version of the GBIF dataset merged with the verified dataset. Spatial location and grain Neotropics, Behrmann projection equivalent to 1° × 1°. Time period Specimens housed in museums during the last 150 years. Major taxa studied Squamata: Serpentes. Software format Geographical information system (GIS). Results The combined dataset provides the most comprehensive distribution database for Neotropical snakes to date. It contains 147,515 records for 886 species across 12 families, representing 74% of all species of snakes, spanning 27 countries in the Americas. Species richness and phylogenetic diversity show overall similar patterns. Amazonia is the least sampled Neotropical region, whereas most well‐sampled sites are located near large universities and scientific collections. We provide a list and updated maps of geographical distribution of all snake species surveyed. Main conclusions The biodiversity metrics of Neotropical snakes reflect patterns previously documented for other vertebrates, suggesting that similar factors may determine the diversity of both ectothermic and endothermic animals. We suggest conservation strategies for high‐diversity areas and sampling efforts be directed towards Amazonia and poorly known species.

Determining the Roles of Inositol Trisphosphate Receptors in Neurodegeneration: Interdisciplinary Perspectives on a Complex Topic - Silvia Honda Takada; Juliane Midori Ikebara; Erica de Sousa; Débora Sterzeck Cardoso; Rodrigo Ribeiro Resende; Henning Ulrich; Martin Rückl; Sten Rüdiger; Alexandre Hiroaki Kihara (Molecular Neurobiology, 2017)

Ants visiting extrafloral nectaries and pyrrolizidine alkaloids may shape how a specialist herbivore feeds on its host plants - Alexandre Eduardo Magalhães; Carlos Henrique Zanini Martins; Diomar Verçosa; Kamila Ferreira Massuda; José Roberto Trigo (Arthropod-Plant Interactions, 2017)

Production of Electrospun Fast-Dissolving Drug Delivery Systems with Therapeutic Eutectic Systems Encapsulated in Gelatin - Francisca Mano; Marta Martins; Isabel Sá-Nogueira; Susana Barreiros; João Paulo Borges; Rui L. Reis; Ana Rita C. Duarte; Alexandre Paiva (AAPS PharmSciTech, 2017)

Alternatives to regular urea for abating N losses in lettuce production under sub-tropical climate - Rafael R. Cantú; Celso Aita; Alexandre Doneda; Diego A. Giacomini; Alexandre Dessbesell; Marlon Arenhardt; Géssica G. De Bastiani; Stefen B. Pujol; Philippe Rochette; Martin H. Chantigny; Sandro J. Giacomini (Biology and Fertility of Soils, 2017)

Inheritance of resistance to Meloidogyne enterolobii and individual selection in segregating populations of Psidium spp - Vicente Martins Gomes; Rodrigo Moreira Ribeiro; Alexandre Pio Viana; Ricardo Moreira de Souza; Eileen Azevedo Santos; Daniele Lima Rodrigues; Odimar Ferreira de Almeida (European Journal of Plant Pathology, 2017)

Curcuma longa as additive in the diet for Astyanax aff. bimaculatus - Pollyanna de Moraes França Ferreira; Maria Tatiana Soares Martins; Débora Werneck Caldas; Juliana Rodrigues Gomes; Jerusa Maria de Oliveira; Ana Lucia Salaro; Juliana Silva Rocha; Jener Alexandre Sampaio Zuanon (Fish Physiology and Biochemistry, 2017)

Determination of the Lead, Cadmium, and Chromium Concentration in Mineral Feeds and Supplements for Cattle Produced in the Mato Grosso State, Brazil - Keyla dos Santos Sigarini; Adriana Paiva de Oliveira; Daiane Lima Martins; Alexandre Silva Brasil; Kamila Cristina de Oliveira; Ricardo Dalla Villa (Biological Trace Element Research, 2017)

Capuchin monkey biogeography: understanding Sapajus Pleistocene range expansion and the current sympatry between Cebus and Sapajus - Marcela G. M. Lima; Janet C. Buckner; José de Sousa e Silva‐Júnior; Alexandre Aleixo; Amely B. Martins; Jean P. Boubli; Andrés Link; Izeni P. Farias; Maria Nazareth da Silva; Fabio Röhe; Helder Queiroz; Kenneth L. Chiou; et al. (Journal of Biogeography, 2017)
Aim Our aim was to examine gracile capuchin ( Cebus ) and robust capuchin monkey ( Sapajus ) diversification, with a focus on recent Sapajus expansion within Amazonia. We wanted to reconstruct the biogeographical history of the clade using statistical methods that model lineages’ occupation of different regions over time in order to evaluate recently proposed ‘Out of Amazonia’ and ‘Reinvasion of Amazonia’ hypotheses as alternative explanations for the extensive geographical overlap between reciprocally monophyletic gracile ( Cebus ) and robust ( Sapajus ) capuchin monkeys. Location Central and South America. Methods We reconstructed a time‐calibrated molecular phylogeny for capuchins under Bayesian inference from three mitochondrial genes. We then categorized 12 capuchin clades across four Neotropical centres of endemism and reconstructed the biogeographical history of the capuchin radiation using six models implemented in ‘BioGeo BEARS ’. We performed a phylogeographical analysis for a robust capuchin clade that spans the Atlantic Forest, Cerrado, Caatinga and Amazonia. Results We find support for a late Miocene vicariant Cebus‐Sapajus divergence and a Pleistocene Sapajus invasion of Amazonia from the Atlantic Forest. Our new analyses confirm Sapajus diversified first in the Atlantic Forest, with subsequent range expansion into widespread sympatry with Cebus in Amazonia, as well as multiple expansions into drier savanna‐like habitats. We do not find mitochondrial molecular congruence with morphological species distinctions for Sapajus flavius , S. cay , S. macrocephalus , S. libidinosus and S. apella ; instead, these five morphological types together form a single widespread clade (Bayesian posterior probability = 1) with geographical substructure and shared ancestry during the Pleistocene. Main conclusions Our results support vicariance dividing ancestral capuchin populations in Amazonia versus the Atlantic Forest, and a Pleistocene ‘Amazonian invasion’ by Sapajus to explain the present‐day sympatry of Cebus and Sapajus .

Characterization of isolates of equine infectious anemia virus in Brazil - Dellane Martins Tigre; Camila Fonseca Lopes Brandão; Fabiana Lopes de Paula; Fabio Alexandre Chinalia; Gubio Soares Campos; Silvia Ines Sardi (Archives of Virology, 2017)

The potential effects of antioxidant feed additives in mitigating the adverse effects of corn naturally contaminated with Fusarium mycotoxins on antioxidant systems in the intestinal mucosa, plasma, and liver in weaned pigs - Bich Van Le Thanh; Michel Lemay; Alexandre Bastien; Jérôme Lapointe; Martin Lessard; Younès Chorfi; Frédéric Guay (Mycotoxin Research, 2016)

Integrating ecological and genetic structure to define management units for caribou in Eastern Canada - Glenn Yannic; Martin-Hugues St-Laurent; Joaquin Ortego; Joëlle Taillon; Alexandre Beauchemin; Louis Bernatchez; Christian Dussault; Steeve D. Côté (Conservation Genetics, 2016)

Associating a negatively charged GdDOTA-derivative to the Pittsburgh compound B for targeting Aβ amyloid aggregates - André F. Martins; Alexandre C. Oliveira; Jean-François Morfin; Douglas V. Laurents; Éva Tóth; Carlos F. G. C. Geraldes (JBIC Journal of Biological Inorganic Chemistry, 2016)

Response of intertidal benthic microalgal biofilms to a coupled light–temperature stress: evidence for latitudinal adaptation along the A tlantic coast of S outhern E urope - Martin Laviale; Alexandre Barnett; João Ezequiel; Bernard Lepetit; Silja Frankenbach; Vona Méléder; João Serôdio; Johann Lavaud (Environmental Microbiology, 2015)
Summary Although estuarine microphytobenthos ( MPB ) is frequently exposed to excessive light and temperature conditions, little is known on their interactive effects on MPB primary productivity. Laboratory and in situ experiments were combined to investigate the short‐term joint effects of high light ( HL ) and high temperature (37° C versus 27° C ) on the operating efficiency of photoprotective processes [vertical migration versus non‐photochemical quenching ( NPQ )] exhibited by natural benthic diatom communities from two intertidal flats in F rance ( FR ) and P ortugal ( PT ). A clear latitudinal pattern was observed, with PT biofilms being more resistant to HL stress, regardless the effect of temperature, and displaying a lower relative contribution of vertical migration to photoprotection and a stronger NPQ in situ . However, higher temperature leads to comparable effects, with photoinhibition increasing to about three times (i.e. from 3% to 10% and from 8% to 22% in PT and FR sites respectively). By using a number of methodological novelties in MPB research (lipid peroxidation quantification, L hcx proteins immunodetection), this study brings a physiological basis to the previously reported depression of MPB photosynthetic productivity in summer. They emphasize the joint role of temperature and light in limiting, at least transiently (i.e. during emersion), MPB photosynthetic activity in situ .

Is the meiofauna a good indicator for climate change and anthropogenic impacts? - Daniela Zeppilli; Jozée Sarrazin; Daniel Leduc; Pedro Martinez Arbizu; Diego Fontaneto; Christophe Fontanier; Andrew J. Gooday; Reinhardt Møbjerg Kristensen; Viatcheslav N. Ivanenko; Martin V. Sørensen; Ann Vanreusel; Julien Thébault; et al. (Marine Biodiversity, 2015)

Chlorophyll a fluorescence and growth of Neoregelia concentrica (Bromeliaceae) during acclimatization in response to light levels - João Paulo Rodrigues Martins; Edilson Romais Schimildt; Rodrigo Sobreira Alexandre; Antelmo Ralph Falqueto; Wagner Campos Otoni (In Vitro Cellular & Developmental Biology - Plant, 2015)

The anuran calling repertoire in the light of social context - Luís F. Toledo; Itamar A. Martins; Daniel P. Bruschi; Michel A. Passos; César Alexandre; Célio F. B. Haddad (acta ethologica, 2015)

Ticks (Acari: Ixodidae) identified from prey–predator interactions via faecal analysis of Brazilian wild carnivores - Thiago F. Martins; Thaís R. Diniz-Reis; Gustavo S. Libardi; Alexandre R. Percequillo; Luciano M. Verdade; Eliana R. Matushima; Marcelo B. Labruna (Experimental and Applied Acarology, 2015)

Changes in the variability and periodicity of precipitation in Scotland - Muhammad Afzal; Alexandre S. Gagnon; Martin G. Mansell (Theoretical and Applied Climatology, 2015)

Evaluating potential man-induced changes in fish communities at estuarine and surf-zone areas: a long-term case study in Southern Brasil - Vieira Joao; Lameiro Fábio; Garcia Alexandre; Martins Ana (Frontiers in Marine Science, 2015)

Erratum to: Strontium ranelate changes the composition and crystal structure of the biological bone-like apatite produced in osteoblast cell cultures - William Querido; Andrea P. C. Campos; Erlon H. Martins Ferreira; Rosane A. S. San Gil; Alexandre M. Rossi; Marcos Farina (Cell and Tissue Research, 2014)

Strontium ranelate changes the composition and crystal structure of the biological bone-like apatite produced in osteoblast cell cultures - William Querido; Andrea P. C. Campos; Erlon H. Martins Ferreira; Rosane A. S. San Gil; Alexandre M. Rossi; Marcos Farina (Cell and Tissue Research, 2014)

Genetic diversity of hepatitis C virus quasispecies in chronic renal failure patients in Midwest Brazil - Regina Maria Santos de Amorim; Alexandre Coelho; Elisabeth Lampe; Tainá Raiol; Regina Maria Bringel Martins (Archives of Virology, 2014)

The effect of sex and genotype on growth performance, feed efficiency, and carcass traits of local sheep group Pantaneiro and Texel or Santa Inês crossbred finished on feedlot - Fernando Miranda de Vargas Junior; Charles Ferreira Martins; Guilherme dos Santos Pinto; Marcos Barbosa Ferreira; Hélio de Almeida Ricardo; André Gustavo Leão; Alexandre Rodrigo Mendes Fernandes; Alfredo Teixeira (Tropical Animal Health and Production, 2014)

Brazilian genetic database of chromosome X - Joyce Aparecida Martins; Bárbara Kawamura; Alexandre Eduardo Cardoso; Regina Maria Barretto Cicarelli (Molecular Biology Reports, 2014)

Dissociations between cognitive and motor effects of psychostimulants and atomoxetine in hyperactive DAT-KO mice - Thomas Del’Guidice; Morgane Lemasson; Adeline Etiévant; Stella Manta; Luiz Alexandre V. Magno; Guy Escoffier; François S. Roman; Jean-Martin Beaulieu (Psychopharmacology, 2014)

Resource partitioning among cladocerans in a littoral macrophyte zone: implications for the transfer of essential compounds - Hélène Masclaux; Gilles Bourdier; Pascal Riera; Martin J. Kainz; Lionel Jouve; Emilie Duffaud; Alexandre Bec (Aquatic Sciences, 2014)

Guava decline: effect of root exudates from Meloidogyne enterolobii-parasitized plants on Fusarium solani in vitro and on growth and development of guava seedlings under controlled conditions - Vicente Martins Gomes; Ricardo Moreira Souza; Silvaldo Felipe da Silveira; Alexandre Macedo Almeida (European Journal of Plant Pathology, 2013)

The CB1 cannabinoid receptor mediates glucocorticoid-induced effects on behavioural and neuronal responses during lactation - Fabiana Cardoso Vilela; Silvia Graciela Ruginsk; Carla Martins de Melo; Alexandre Giusti-Paiva (Pflügers Archiv - European Journal of Physiology, 2013)

Male mating competitiveness and age-dependent relationship between testosterone and social rank in bighorn sheep - Alexandre M. Martin; Hélène Presseault-Gauvin; Marco Festa-Bianchet; Fanie Pelletier (Behavioral Ecology and Sociobiology, 2013)

Experimental exposure of juvenile savannah monitors (Varanus exanthematicus) to an environmentally relevant mixture of three contaminants: effects and accumulation in tissues - Alexandre Ciliberti; Samuel Martin; Eric Ferrandez; Sara Belluco; Benoit Rannou; Céline Dussart; Philippe Berny; Vivian de Buffrenil (Environmental Science and Pollution Research, 2013)

CYP2C9 and VKORC1 polymorphisms influence warfarin dose variability in patients on long-term anticoagulation - Paulo Caleb Junior Lima Santos; Carla Luana Dinardo; Isolmar Tadeu Schettert; Renata Alonso Gadi Soares; Liz Kawabata-Yoshihara; Isabela Martins Bensenor; José Eduardo Krieger; Paulo Andrade Lotufo; Alexandre Costa Pereira (European Journal of Clinical Pharmacology, 2013)

Population genetics of the A merican eel ( A nguilla rostrata ): F ST = 0 and N orth A tlantic O scillation effects on demographic fluctuations of a panmictic species - Caroline L. Côté; Pierre‐Alexandre Gagnaire; Vincent Bourret; Guy Verreault; Martin Castonguay; Louis Bernatchez (Molecular Ecology, 2013)
We performed population genetic analyses on the A merican eel ( A nguilla rostrata ) with three main objectives. First, we conducted the most comprehensive analysis of neutral genetic population structure to date to revisit the null hypothesis of panmixia in this species. Second, we used this data to provide the first estimates of contemporary effective population size ( N e ) and to document temporal variation in effective number of breeders ( N b ) in American eel. Third, we tested for statistical associations between temporal variation in the N orth A tlantic O scillation ( NAO ), the effective number of breeders and two indices of recruit abundance. A total of 2142 eels from 32 sampling locations were genotyped with 18 microsatellite loci. All measures of differentiation were essentially zero, and no evidence for significant spatial or temporal genetic differentiation was found. The panmixia hypothesis should thus be accepted for this species. N b estimates varied by a factor of 23 among 12 cohorts, from 473 to 10 999. The effective population size N e was estimated at 10 532 (95% CI , 9312–11 752). This study also showed that genetically based demographic indices, namely N b and allelic richness ( Ar ), can be used as surrogates for the abundance of breeders and recruits, which were both shown to be positively influenced by variation during high (positive) NAO phases. Thus, long‐term genetic monitoring of American glass eels at several sites along the North American Atlantic coast would represent a powerful and efficient complement to census monitoring to track demographic fluctuations and better understand their causes.

Methanogenic potential of Arctic and Antarctic subglacial environments with contrasting organic carbon sources - Marek Stibal; Jemma L. Wadham; Grzegorz P. Lis; Jon Telling; Richard D. Pancost; Ashley Dubnick; Martin J. Sharp; Emily C. Lawson; Catriona E. H. Butler; Fariha Hasan; Martyn Tranter; Alexandre M. Anesio (Global Change Biology, 2012)
Subglacial environments are largely anoxic, contain organic carbon ( OC ) overridden by glacier ice during periods of advance, and harbour active microbial communities. This creates favourable conditions for OC degradation via methanogenesis. It has been hypothesized that OC beneath ice sheets is converted to methane ( CH 4 ) and may be released to the atmosphere during retreat. However, there are limited data available to support this contention. Here, we present new data on the abundance, diversity and activity of methanogenic archaea and the amount and character of OC in subglacial sediments from Arctic and Antarctic glacial systems based on different substrate types. We employed long‐term laboratory incubations to quantify the CH 4 production potential in different subglacial settings. Significant numbers of methanogens (up to 7 × 10 4 cells g −1 ) were detected in the samples and clones of Methanomicrobiales and Methanosarcinales were identified in clone libraries. Long lag periods (up to >200 days) were observed before significant CH 4 concentrations were measured. We report order of magnitude differences in rates of CH 4 production (10 1 –10 5 fmol g −1 d −1 ) in different subglacial sediments, reflecting contrasts in the origin of the sediment and the OC character. Hence, we predict that contrasting rates of CH 4 production are likely to occur beneath glaciers and ice sheets that overran different types of substrate. We subsequently estimated the potential for CH 4 production beneath the Laurentide/Inuitian/Cordilleran and Fennoscandian Ice Sheets during a typical 85 ka Quaternary glacial/interglacial cycle. CH 4 production from lacustrine‐derived OC is likely to be an order of magnitude higher (~6.3–27 Pg C) than that from overridden soils (~0.55–0.68 Pg C), possibly due to a difference in lability between lacustrine and soil OC . While representing a fraction of the entire OC pool (~418–610 Pg C), this finding highlights the importance of considering the character of different OC pools when calculating subglacial CH 4 production.

Host cell processes to accomplish mechanical and non-circulative virus transmission - Aurélie Bak; Sarah L. Irons; Alexandre Martinière; Stéphane Blanc; Martin Drucker (Protoplasma, 2012)

Keratinases and sulfide from Bacillus subtilis SLC to recycle feather waste - Sabrina Martins Lage Cedrola; Ana Cristina Nogueira de Melo; Ana Maria Mazotto; Ulysses Lins; Russolina Benedeta Zingali; Alexandre Soares Rosado; Raquel S. Peixoto; Alane Beatriz Vermelho (World Journal of Microbiology and Biotechnology, 2012)

Prokaryotic diversity in sediments beneath two polar glaciers with contrasting organic carbon substrates - Marek Stibal; Fariha Hasan; Jemma L. Wadham; Martin J. Sharp; Alexandre M. Anesio (Extremophiles, 2012)

High-fat diet based on dried bovine brain: an effective animal model of dyslipidemia and insulin resistance - Tiago Gomes Araújo; Ana Catarina Rezende Leite; Caíque Silveira Martins da Fonseca; Bruno Melo Carvalho; Alexandre Ricardo Pereira Schuler; Vera Lúcia de Menezes Lima (Journal of Physiology and Biochemistry, 2011)

Identification of defence-related genes expressed in coffee and citrus during infection by Xylella fastidiosa - Marcelo F. Carazzolle; Fernanda R. Rabello; Natália F. Martins; Alessandra A. de Souza; Alexandre M. do Amaral; Juliana Freitas-Astua; Gonçalo A. G. Pereira; Marcos A. Machado; Angela Mehta (European Journal of Plant Pathology, 2011)

Erratum to: Local and remote tissue injury upon intestinal ischemia and reperfusion depends on the TLR/MyD88 signaling pathway - Tatiana Victoni; Fernando Rodrigues Coelho; Alexandre Learth Soares; Andressa de Freitas; Thomas Secher; Rodrigo Guabiraba; François Erard; Ricardo Martins de Oliveira-Filho; B. Boris Vargaftig; Gregoire Lauvaux; Mamdouh A. Kamal; Bernhard Ryffel; et al. (Medical Microbiology and Immunology, 2010)

Local and remote tissue injury upon intestinal ischemia and reperfusion depends on the TLR/MyD88 signaling pathway - Tatiana Victoni; Fernando Rodrigues Coelho; Alexandre Learth Soares; Andressa de Freitas; Thomas Secher; Rodrigo Guabiraba; François Erard; Ricardo Martins de Oliveira-Filho; B. Boris Vargaftig; Gregoire Lauvaux; Mamdouh A. Kamal; Bernhard Ryffel; et al. (Medical Microbiology and Immunology, 2010)

Apoptosis in porcine macrophages infected in vitro with African swine fever virus (ASFV) strains with different virulence - Raquel Portugal; Alexandre Leitão; Carlos Martins (Archives of Virology, 2009)

Combined effects of food quality and temperature on somatic growth and reproduction of two freshwater cladocerans - HÉlène Masclaux; Alexandre Bec; Martin J. Kainz; Christian Desvilettes; Lionel Jouve; Gilles Bourdier (Limnology and Oceanography, 2009)
We investigated the effect of food quality on somatic growth and reproduction of zooplankton at different temperatures (12°C, 15°C, 20°C, and 25°C). Standardized growth experiments of two cladocerans, Daphnia magna and Simocephalus vetulus , were performed on (1) high‐quality food ( Cryptomonas sp.), (2) relatively low‐quality food ( Scenedesmus obliquus ), and (3) intermediate‐quality food ( Cryptomonas : Scenedesmus mixture). Food quality constraints on somatic growth and reproduction of the two cladocerans decreased with increasing temperature. For D. magna and for S. vetulus , differences between clutch size and growth rate of individuals fed on the three food sources were highly pronounced when they were reared at 12°C and 15°C; however, such differences decreased at 20°C and were negligible at 25°C. Variations in food quality constraints with temperature can be explained by the variability of dietary polyunsaturated fatty acids, such as eicosapentaenoic acid and stearidonic acid requirements of these cladocerans. We conclude that dietary constraints exerted by food quality for zooplankton development vary as a function of different temperature conditions.

Cloud condensation nuclei from biomass burning during the Amazonian dry-to-wet transition season - Jorge Alberto Martins; Fábio Luiz T. Gonçalves; Carlos A. Morales; Gilberto F. Fisch; Francisco Geraldo M. Pinheiro; João Bosco V. Leal Júnior; Carlos J. Oliveira; Emerson M. Silva; José Carlos P. Oliveira; Alexandre A. Costa; Maria Assunção F. Silva Dias (Meteorology and Atmospheric Physics, 2009)

Identification of susceptibility genes for complex diseases using pooling-based genome-wide association scans - Yohan Bossé; François Bacot; Alexandre Montpetit; Johan Rung; Hui-Qi Qu; James C. Engert; Constantin Polychronakos; Thomas J. Hudson; Philippe Froguel; Robert Sladek; Martin Desrosiers (Human Genetics, 2009)

Generation and characterization of recombinant feline β-galactosidase for preclinical enzyme replacement therapy studies in GM1 gangliosidosis - Tatiana I. Samoylova; Douglas R. Martin; Nancy E. Morrison; Misako Hwang; Anna M. Cochran; Alexandre M. Samoylov; Henry J. Baker; Nancy R. Cox (Metabolic Brain Disease, 2008)

The cost‐effectiveness of biodiversity surveys in tropical forests - Toby A. Gardner; Jos Barlow; Ivanei S. Araujo; Teresa Cristina Ávila‐Pires; Alexandre B. Bonaldo; Joana E. Costa; Maria Cristina Esposito; Leandro V. Ferreira; Joseph Hawes; Malva I. M. Hernandez; Marinus S. Hoogmoed; Rafael N. Leite; et al. (Ecology Letters, 2008)
The identification of high‐performance indicator taxa that combine practical feasibility and ecological value requires an understanding of the costs and benefits of surveying different taxa. We present a generic and novel framework for identifying such taxa, and illustrate our approach using a large‐scale assessment of 14 different higher taxa across three forest types in the Brazilian Amazon, estimating both the standardized survey cost and the ecological and biodiversity indicator value for each taxon. Survey costs varied by three orders of magnitude, and dung beetles and birds were identified as especially suitable for evaluating and monitoring the ecological consequences of habitat change in our study region. However, an exclusive focus on such taxa occurs at the expense of understanding patterns of diversity in other groups. To improve the cost‐effectiveness of biodiversity research we encourage a combination of clearer research goals and the use of an objective evidence‐based approach to selecting study taxa.

Polymorphisms in 33 inflammatory genes and risk of myocardial infarction—a system genetics approach - Sandrine Barbaux; David-Alexandre Tregouet; Viviane Nicaud; Odette Poirier; Claire Perret; Tiphaine Godefroy; Carole Francomme; Christophe Combadiere; Dominique Arveiler; Gerald Luc; Jean-Bernard Ruidavets; Alun E. Evans; et al. (Journal of Molecular Medicine, 2007)

A promising action of riboflavin as a mediator of leukaemia cell death - Ana Carolina Santos de Souza; Liudmila Kodach; Fernanda R. Gadelha; Carina L. Bos; Alexandre D. Martins Cavagis; Hiroshi Aoyama; Maikel P. Peppelenbosch; Carmen Veríssima Ferreira (Apoptosis, 2006)

Trophic upgrading of autotrophic picoplankton by the heterotrophic nanoflagellate Paraphysomonas sp. - Alexandre Bec; Dominik Martin-Creuzburg; Eric von Elert (Limnology and Oceanography, 2006)
We investigated whether trophic repackaging of autotrophic picoplankton by phagotrophic protists is associated with an improvement in food quality for the metazooplankton Daphnia magna (i.e., whether trophic upgrading occurs in this system). The nutritional value of the autotrophic species Microcystis aeruginosa PCC7806, Synechococcus sp. strain BO8809, Synechococcus elongatus SAG 89.79, and Choricystis minor KR1988/ 8, and of the heterotrophic nanoflagellate Paraphysomonas sp. grown on these different picoplanktonic species was evaluated in standardized growth experiments with D. magna . In order to investigate the functional role of the flagellate in the simplified autotrophic picoplankton‐ Daphnia food chain, Paraphysomonas sp. was grown on the different picoplanktonic organisms and subsequently separated from the food items before being fed to D. magna. The presence of Paraphysomonas sp. as an intermediary trophic step enhanced somatic growth and reproduction of D. magna. Supplementation of Synechococcus sp. with lipids from Paraphysomonas sp. (grown on Synechococcus sp.) revealed that trophic upgrading of autotrophic picoplankton is due to the additional lipids present in the flagellate. Paraphysomonas sp. synthesized polyunsaturated fatty acids and sterols de novo, which most likely explains the trophic upgrading. Paraphysomonas sp. also improved the food quality of M. aeruginosa PCC7806, which is toxic for D. magna . The heterotrophic flagellate Paraphysomonas sp. is capable of trophically upgrading a poor quality food source not only by producing essential lipids, but also by detoxifying the cyanobacterial food organism.

Spatial Variation and Dynamics of Flooding, Canopy Openness, and Structure in a Neotropical Swamp Forest - Alexandre F. Souza; Fernando R. Martins (Plant Ecology, 2005)

Sympatric occurrence of three cytotypes and four morphological types of B chromosomes of Astyanax scabripinnis (Pisces, Characiformes) in the River Ivaí Basin, state of Paraná, Brazil - Carlos Alexandre Fernandes; Isabel Cristina Martins-Santos (Genetica, 2005)

The thermal stability of a castor bean seed acid phosphatase - Paulo Afonso Granjeiro; Alexandre Donizeti Martins Cavagis; Luciana de Campos Leite; Carmen Veríssima Ferreira; José Mauro Granjeiro; Hiroshi Aoyama (Molecular and Cellular Biochemistry, 2004)

Population structure and dynamics of a neotropical palm in fire-impacted fragments of the Brazilian Atlantic Forest - Alexandre F. Souza; Fernando R. Martins (Biodiversity and Conservation, 2004)

Spatial distribution of an undergrowth palm in fragments of the Brazilian Atlantic Forest - Alexandre F. Souza; Fernando R. Martins (Plant Ecology, 2003)

Forest response to climate changes in Atlantic Equatorial Africa during the last 4000 years BP and inheritance on the modern landscapes - Annie Vincens; Dominique Schwartz; Hilaire Elenga; Isabelle Reynaud‐Farrera; Anne Alexandre; Jacques Bertaux; André Mariotti; Louis Martin; Jean‐Dominique Meunier; François Nguetsop; Michel Servant; Simone Servant‐Vildary; et al. (Journal of Biogeography, 1999)
Summary This review paper synthesizes the recent published palaeoecological results obtained in Atlantic Equatorial Africa (ECOFIT program) on the history of forest ecosystems and inferred climate changes during the past 4000 years. Evidence are mainly provided by pollen analysis carried out at nine sites from Congo, Cameroon and Ghana, locally supported by macroflora remains, phytoliths, diatoms, δ 13 C and mineralogical data. At all the sites, except Lake Bosumtwi (Ghana), following a large expansion of rain and mesophilous forests until 3000 years BP , a major change is registered, affecting floristic composition, structure and geographical distribution. According to the hydrological sensitivity of the different sites, local openings of the forests with development of heliophilous formations and/or isolated enclosed savannas are observed at the most humid sites; complete disappearance of forested formations at the driest. The agreement between pollen records, hydrological and hydrobiological data definitely demonstrates that an arid event has been the primary driving factor of this change and is responsable for the main features of the modern landscapes in Atlantic Equatorial Africa. Moreover, the most recent palaeoecological data obtained in Congo (Lake Sinnda), indicate that this Late Holocene increasing aridity was of longer duration, from 4000 to 1300 years BP , and more progressive than previously inferred. A new expansion of forests is locally detected c. 900–600 BP despite increased human impact.